Composite peeling method
The use of a precipitating agent to separate polymers from aqueous solvents by inducing bond rupture and structural transition in copolymers addresses inefficiencies in existing methods, ensuring rapid, clean, and effective polymer recovery.
Patent Information
- Application Number
- JP2022578586
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-02-10
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2041-02-10
AI Technical Summary
Existing methods for separating polymers from mixtures, particularly water-soluble polymers and aqueous solvents, are inefficient, lead to high energy consumption, contamination of other components, and require complex separation processes, often resulting in polymers with high impurity levels.
A method involving the use of a precipitating agent, such as strong or weak acids, to form a second suspension by adding the agent to a first suspension containing a polymer and an aqueous solvent, specifically targeting copolymers with structural units derived from acid and hydrophobic group-containing monomers, to induce bond rupture and structural transition for rapid polymer precipitation.
The method achieves complete separation of polymers from aqueous solvents in a short time, minimizing contamination and recovery loss, while avoiding undesirable chemical changes to other components, thus enhancing the efficiency and purity of polymer recovery.
Smart Images

Figure 0007612720000012 
Figure 0007612720000013 
Figure 0007612720000014
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of methods for recycling materials. In particular, the present invention relates to a method for precipitation of polymers. [Background technology]
[0002] Rapid urbanization, rapid technological innovation, and the frequent replacement of products or disposal of consumables that accompany them have led to shorter product life spans and / or excessive generation of waste. The excessive generation of waste has led to serious problems such as adverse effects on the human body and the environment, and resource depletion, and there is a global need to find a solution to these problems using various waste disposal methods.
[0003] Recycling is an important component of the waste reduction hierarchy, aiming to recover valuable materials from waste for reuse. Recycling of materials helps to conserve natural resources, reduces the energy consumption associated with the extraction of raw materials (thus reducing production costs), and reduces greenhouse gases and SO x This reduces the environmental impact by reducing emissions. As such, material recycling has great benefits, and developing highly effective and efficient methods for recycling materials is of utmost importance in realizing a circular economy.
[0004] Polymerization is a powerful and modular strategy for the generation of macromolecules with highly complex structures and diverse functions. Thus, polymers are useful in a wide variety of applications. They have been used as catalysts, paints, varnishes, protective coatings, dispersants, emulsifiers, surfactants, lubricants, flocculants, thickeners, delivery agents, adhesives, insulators, packaging materials, biomaterials, building materials, photosensitive materials, etc. As polymers are used in such a wide variety of fields, the separation of polymers contained in products is a technology that is closely related to material recycling.
[0005] However, when a product reaches the end of its life or has rejects during the manufacturing process and is ready to be recycled, there are some challenges involved in going through the process of separating the polymers contained in the product during recycling.
[0006] Various means have been proposed in achieving the extraction of polymers. For example, agents can be incorporated into the mixture containing the polymer to allow for the recovery of the polymer. However, the agents that act to react with or cause changes in the polymer to cause the separation of the polymer from the mixture may also undergo undesirable chemical reactions with other components in the mixture, which may cause irreversible chemical changes in the other components or allow the other components to be extracted from the mixture as well. The former will make the recovery of the other components in the mixture impossible, while the latter will cause ineffective separation of the polymer resulting in undesirable recovery losses of the other components in the mixture as well as resulting in a regenerated polymer with high levels of impurities that require a subsequent purification process. Furthermore, the separation of the polymer from the remaining mixture is very inefficient and can take several hours.
[0007] In a further embodiment, the method of the present invention is for achieving separation of the aqueous polymer from the aqueous solvent. Water-soluble polymers are known to be water-soluble and can be processed in aqueous media, but they show excellent dispersibility and stability in water. The ability of the polymer to be uniformly dispersed in water greatly enhances the specific functional performance of the polymer. However, the sufficient dispersion of the water-soluble polymer in the aqueous medium poses additional challenges in the subsequent separation of the water-soluble polymer from the respective aqueous solvent in the recycling step.
[0008] Commonly used organic polymers such as polyvinylidene fluoride (PVDF) have their own drawbacks, being insoluble in water and soluble only in some specific organic solvents such as N-methyl-2-pyrrolidone (NMP). NMP is flammable and toxic and requires specific handling. An NMP recovery device must be installed in the drying process to recover NMP vapor. Such a recovery device requires a large capital investment, which adds a large cost to the manufacturing process. Therefore, in applications where exposure to moisture in the manufacturing process is of less concern, the use of water-based polymers utilizing cheaper and more environmentally friendly aqueous solvents, most commonly water, is preferred because the use of water-based polymers can eliminate the large capital costs of the recovery system. In this regard, the present invention details a method for precipitating water-soluble polymers.
[0009] The separation of a polymer from a mixture is initiated by bond breaking and / or rupture between the polymer and the solvent contained in the mixture. However, since a large number of polymers of different compositions have been developed that exhibit various specific properties, it would be highly impractical to apply a single separation method in the separation of a polymer from a mixture, regardless of the composition of the polymers contained therein. For this reason, it is desirable that the selection of the method or agent added to the mixture be highly specific in achieving the separation of the target polymer without causing undesirable chemical and physical changes to other components in the mixture.
[0010] In view of the above, attempts have been made to develop methods to achieve complete separation of the polymer from the mixture.
[0011] KR Patent Application Publication No. 20130099568A discloses a method for separating a polymer from a polymer solution under supercritical conditions by introducing a supercritical fluid such as carbon dioxide (CO2) into the polymer solution, in which the polymer solution is an olefin monomer. -Oand polymers derived from alkyl or benzyl solvents. The polymer solution is first pressurized (500 bar or more, far above the critical pressure of CO2) at a constant temperature of 20-70°C by introducing carbon dioxide into the polymer solution to form a homogeneous solution. The liquid CO2 in the polymer solution can act as an anti-solvent and precipitate the polymer. The precipitated polymer can then be removed from the remaining polymer solution by lowering the pressure of the remaining solution and evaporating the CO2, solvent, and monomer. To create a supercritical state and allow CO2 to exert a good anti-solvent effect, very high pressures, far above atmospheric pressure, are required for the processes involved to initiate the precipitation of the polymer. This method incurs a large energy cost (arising from the large energy consumption) for the separation step. There are also safety issues due to the high pressure process.
[0012] In view of the above problems, there is a constant need to develop a unified and simple method to achieve a highly efficient and complete separation of a polymer from a mixture, the mixture comprising a polymer and an aqueous solvent. The present invention shows a method for precipitation of a polymer in which a precipitant is used to achieve a complete separation of the polymer from the mixture. Furthermore, the method disclosed herein is developed specifically for the optimization of polymer formulations. The method for precipitation of a polymer disclosed herein is developed to initiate bond breaking and / or rupture between the polymer and the aqueous solvent in the mixture. This involves a structural transition of the polymer driven by the intermolecular and intramolecular interactions of the polymer chains, which results in the precipitation of the polymer. Thus, the precipitation phenomenon is related to a phase conversion reaction in which the polymer in the liquid phase is rapidly converted to a solid phase. The polymer of the present invention includes a copolymer comprising a structural unit derived from an acid group-containing monomer and a structural unit derived from a hydrophobic group-containing monomer. The precipitation method of the present invention, which satisfies the properties of promoting the change in the interaction between the polymer and the aqueous solvent, is highly applicable to the recovery of the polymer from the mixture. This will avoid both the complicated separation process and the contamination of the polymer, allowing for excellent material recovery and achieving the precipitation of the polymer in a short time. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] KR Patent Application Publication No. 20130099568A Summary of the Invention
[0014] The aforementioned needs are met by various aspects and embodiments disclosed herein. In one aspect, provided herein is a method of precipitating a polymer by adding a precipitating agent to a first suspension to form a second suspension, the first suspension comprising a polymer and an aqueous solvent, the polymer comprising a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer.
[0015] In some embodiments, the precipitating agent is an acid, hi some embodiments, the acid is a strong acid, a weak acid, or a combination thereof.
[0016] In some embodiments, the strong acid is selected from the group consisting of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, hydrobromic acid, hydroiodic acid, chloric acid, bromic acid, iodic acid, dithionous acid, dithionous acid, sulfamic acid, trithionous acid, tetrathionic acid, methanesulfonic acid, p-toluenesulfonic acid, benzenesulfonic acid, trichloroacetic acid, trifluoroacetic acid, oxalic acid, propiolic acid, mesoxalic acid, mellitic acid, or combinations thereof. a In some embodiments, the pK of a strong acid is about -10 to about 2. a is between -10 and 2.
[0017] In some embodiments, the weak acid is formic acid, acetic acid, glycolic acid, glyoxylic acid, oxalic acid, propionic acid, acrylic acid, lactic acid, 3-hydroxypropionic acid, glyceric acid, pyruvic acid, 3-oxopropionic acid, 2,3-dioxopropionic acid, malonic acid, tartronic acid, dihydroxymalonic acid, mesoxalic acid, glycidic acid, butyric acid, isobutyric acid, crotonic acid, isocrotonic acid, methacrylic acid, vinylacetic acid, tetrolic acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-oxobutanoic acid, acetoacetic acid, 4-oxobutanoic acid, butanedioic acid, methylmalonic acid, fumaric acid, maleic acid, In some embodiments, the pK of the weak acid is selected from the group consisting of 2-hydroxybutanedioic acid, tartaric acid, oxaloacetic acid, dioxosuccinic acid, valeric acid, isovaleric acid, 2-methylbutyric acid, pivalic acid, 3-hydroxyvaleric acid, 4-hydroxypentanoic acid, 3-hydroxyisovaleric acid, glutaric acid, 2-oxoglutaric acid, 3-oxoglutaric acid, 2-furoic acid, tetrahydrofuroic acid, hexanoic acid, hexanedioic acid, citric acid, aconitic acid, isocitric acid, sorbic acid, pimelic acid, benzoic acid, salicylic acid, 4-carboxybenzoic acid, trimesic acid, mellitic acid, malic acid, dithionous acid, phosphoric acid, nitrous acid, orthosilicic acid, or a combination thereof. a In some embodiments, the pK of the weak acid is from about 2 to about 7. a is between 2 and 7.
[0018] In some embodiments, the pH of the second suspension is from about 0.2 to about 4.5.
[0019] The precipitation of polymer achieved using the methods provided herein is straightforward, occurs in a short time, and does not suffer from any drawbacks in terms of recovery loss of polymer and other components in the first suspension, damage to the recovered polymer, or introduction of impurities.
[0020] In another aspect, one application of the present invention is where the aforementioned method is employed as part of a battery electrode recycling process to achieve separation of the polymeric binder from the remainder of a second suspension, where the polymeric binder is a polymer.A method for precipitating a polymeric binder is provided, comprising adding a precipitating agent to a first suspension to form a second suspension, the first suspension comprising an electrode layer and an aqueous solvent, the electrode layer comprising a polymeric binder, the polymeric binder comprising a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer.
[0021] The simple utilization of a precipitant in the present invention to precipitate the polymer from the second suspension can help achieve complete separation of the polymer from the remainder of the second suspension, reduce the time it takes to precipitate the polymer, maximize recovery of valuable materials, eliminate contamination of the polymer and / or other components in the second suspension, and prevent the need for subsequent processing. Additionally, the methods disclosed herein have been found to be applicable to precipitate polymer binders in battery electrodes without inducing undesirable chemical changes and phase transitions in other components, such as the electrode active material, in the second suspension. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 shows a schematic diagram of one embodiment of the proposed interactions between the polymer and the aqueous solvent in the first suspension. [Diagram 2] FIG. 2 shows a schematic diagram of an embodiment of the proposed change in the interaction between the polymer and the aqueous solvent when a sufficient concentration of precipitant is added to the first suspension. [Diagram 3] 3A and 3B show one embodiment of the structural conformation of the polymer before and after addition of a precipitating agent, respectively, into the first suspension. [Figure 4] FIG. 4 shows a schematic diagram of an embodiment of the proposed change in the interaction between the polymer and the aqueous solvent when an insufficient concentration of precipitant is added to the first suspension. [Diagram 5] FIG. 5 shows a schematic diagram of an embodiment of the proposed change in the interaction between a polymer, including a copolymer that includes structural units derived from one or more carboxylic acid group-containing monomers, and an aqueous solvent when a sufficient concentration of a precipitating agent is added to the first suspension. [Figure 6] 6A and 6B show the physical state of the second suspensions of Comparative Example 1 and Example 2 having pH values of 6 and 3, respectively, after the addition of a precipitant to the first suspension in forming the second suspension. [Figure 7] 7A and 7B show infrared spectroscopy of the precipitated polymer of Example 38 and the remainder of the second suspension, respectively. [Figure 8] 8A and 8B show infrared spectroscopy of the precipitated polymer of Example 37 and the remainder of the second suspension, respectively. [Figure 9] FIG. 9 is a flow chart of one embodiment showing the steps for precipitating the polymer disclosed herein and subsequent further processing to extract the precipitated polymer. [Figure 10] FIG. 10 is a flow chart of one embodiment showing the steps for precipitating the polymeric binder disclosed herein and subsequent further processing to extract the precipitated polymer.
[0023] Detailed Description of the Invention
[0024] In one aspect, provided herein is a method of precipitating a polymer by adding a precipitating agent to a first suspension to form a second suspension; the first suspension comprises a polymer and an aqueous solvent; and the polymer comprises a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer.
[0025] In another embodiment, the method of the invention is used as part of a battery electrode recycling regime. Provided herein is a method of precipitating a polymeric binder by adding a precipitating agent to a first suspension to form a second suspension; the first suspension comprises an electrode layer and an aqueous solvent; the electrode layer comprises a polymeric binder; and the polymeric binder comprises a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer.
[0026] The term "electrode" refers to either a "cathode" or an "anode."
[0027] The term "positive electrode" is used interchangeably with cathode. Similarly, the term "negative electrode" is used interchangeably with anode.
[0028] The terms "polymeric binder", "binder" or "binder material" refer to a chemical compound, mixture of compounds, or polymer used to hold materials in place. In some embodiments, the polymeric binder is used to deposit materials onto a substrate to form a composite material. In some embodiments, the substrate is a conductive metal. In some embodiments, the substrate is a non-conductive metal. In some embodiments, the polymeric binder refers to a chemical compound, mixture of compounds, or polymer used to hold electrode materials and / or conductive agents in place and deposit onto conductive metal parts to form an electrode. In some embodiments, the electrode does not contain any conductive agents. In some embodiments, the polymeric binder forms a colloid, solution, or dispersion in an aqueous solvent, such as water.
[0029] The term "conductive agent" refers to a material that has good electrical conductivity. Thus, conductive agents are often mixed with the electrode active material during the formation of the electrode to improve the electrode's electrical conductivity. In some embodiments, the conductive agent is chemically active. In some, the conductive agent is chemically inactive.
[0030] The term "polymer" refers to a compound prepared by polymerizing monomers of the same or different types. The generic term "polymer" encompasses the terms "homopolymer" and "copolymer."
[0031] The term "homopolymer" refers to a polymer prepared by polymerization of the same type of monomers.
[0032] The term "coil" refers to a linear or nearly linear configuration of a polymer chain. In some embodiments, coiled polymer chains contain like charges along the chain that repel each other.
[0033] The term "copolymer" refers to a polymer prepared by the polymerization of two or more different types of monomers.
[0034] As used herein, the term "unsaturated" refers to a moiety having one or more units of unsaturation.
[0035] The term "alkyl" or "alkyl group" refers to a group of the general formula C derived from a saturated, unbranched or branched aliphatic hydrocarbon by removing a hydrogen atom. n H 2n+1where n is an integer, or an integer from 1 to 20, or an integer from 1 to 8. Examples of alkyl groups include (C1-C8) alkyl groups such as methyl, ethyl, propyl, isopropyl, 2-methyl-1-propyl, 2-methyl-2-propyl, 2-methyl-1-butyl, 3-methyl-1-butyl, 2-methyl-3-butyl, 2,2-dimethyl-1-propyl, 2-methyl-1-pentyl, 3-methyl-1-pentyl, 4-methyl-1-pentyl, 2-methyl-2-pentyl, 3-methyl-2-pentyl, 4-methyl-2-pentyl, 2,2-dimethyl-1-butyl, 3,3-dimethyl-1-butyl, 2-ethyl-1-butyl, butyl, isobutyl, t-butyl, pentyl, isopentyl, neopentyl, hexyl, heptyl, and octyl, but are not limited thereto. Examples of long chain alkyl groups include nonyl and decyl groups. An alkyl group can be unsubstituted or substituted with one or more suitable substituents. Further, an alkyl group can be branched or unbranched. In some embodiments, an alkyl group contains at least 2, 3, 4, 5, 6, 7, or 8 carbon atoms.
[0036] The term "cycloalkyl" or "cycloalkyl group" refers to a saturated or unsaturated cyclic non-aromatic hydrocarbon radical having a single ring or multiple condensed rings. Examples of cycloalkyl groups include, but are not limited to, (C3-C7) cycloalkyl groups such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl, as well as saturated cyclic and bicyclic terpenes, and (C3-C7) cycloalkenyl groups such as cyclopropenyl, cyclobutenyl, cyclopentenyl, cyclohexenyl, and cycloheptenyl, as well as unsaturated cyclic and bicyclic terpenes. Cycloalkyl groups may be unsubstituted or substituted with one or two suitable substituents. Furthermore, cycloalkyl groups may be monocyclic or polycyclic. In some embodiments, cycloalkyl groups contain at least 5, 6, 7, 8, 9, or 10 carbon atoms.
[0037] The term "alkoxy" refers to an alkyl group, as defined above, attached to the main carbon chain through an oxygen atom. Some non-limiting examples of alkoxy groups include methoxy, ethoxy, propoxy, butoxy, etc. Alkoxy, as defined above, may be substituted or unsubstituted, and the substituents may be, but are not limited to, deuterium, hydroxy, amino, halo, cyano, alkoxy, alkyl, alkenyl, alkynyl, mercapto, nitro, etc.
[0038] The term "alkenyl" refers to an unsaturated straight-chain, branched-chain, or cyclic hydrocarbon radical containing one or more carbon-carbon double bonds. Examples of alkenyl groups include, but are not limited to, ethenyl, 1-propenyl, or 2-propenyl, and one or more of the carbon atoms of the radical may be optionally substituted.
[0039] The term "aryl" or "aryl group" refers to an organic radical derived from a monocyclic or polycyclic aromatic hydrocarbon by removing a hydrogen atom. Non-limiting examples of aryl groups include phenyl, naphthyl, benzyl, or tolanyl groups, sexiphenylene, phenanthrenyl, anthracenyl, coronenyl, and tolanylphenyl. An aryl group may be unsubstituted or substituted with one or more suitable substituents. Furthermore, an aryl group may be monocyclic or polycyclic. In some embodiments, an aryl group contains at least 6, 7, 8, 9, or 10 carbon atoms.
[0040] The term "aliphatic" refers to C1-C 30 Alkyl groups, C2-C 30 Alkenyl groups, C2-C 30 Alkynyl groups, C1-C 30 Alkylene group, C2-C 30 Alkenylene group, or C2-C 30 It refers to an alkynylene group. In some embodiments, the alkyl group contains at least 2, 3, 4, 5, 6, 7, or 8 carbon atoms.
[0041] The term "aromatic" refers to a group containing an aromatic hydrocarbon ring, optionally containing a heteroatom or substituent. Examples of such groups include, but are not limited to, phenyl, tolyl, biphenyl, o-terphenyl, m-terphenyl, p-terphenyl, naphthyl, anthryl, phenanthryl, pyrenyl, triphenylenyl, and derivatives thereof.
[0042] The term "substituted" as used to describe a compound or chemical moiety means that at least one hydrogen atom of the compound or chemical moiety has been replaced with a second chemical moiety. Examples of substituents include halogen; alkyl; heteroalkyl; alkenyl; alkynyl; aryl, heteroaryl, hydroxyl; alkoxyl; amino; nitro; thiol; thioether; imine; cyano; amide; phosphonate; phosphine; carboxyl; thiocarbonyl; sulfonyl; sulfonamide; acyl; formyl; acyloxy; alkoxycarbonyl; oxo; haloalkyl (e.g., trifluoromethyl); carbocyclic cycloalkyl, which may be a single ring or multiple fused or non-fused rings (e.g., cyclopropyl, cyclobutyl, cyclopentyl or cyclohexyl) or heterocycloalkyl, which may be a single ring or multiple fused or non-fused rings (e.g., pyrrolidinyl, piperidinyl, piperazinyl, morpholinyl or thiazinyl); carbocyclic or heterocyclic, single ring or multiple fused or non-fused ring aryl (e.g., phenyl, naphthyl, pyrrolyl, indolyl, furanyl, thiophene ... nyl, imidazolyl, oxazolyl, isoxazolyl, thiazolyl, triazolyl, tetrazolyl, pyrazolyl, pyridinyl, quinolinyl, isoquinolinyl, acridinyl, pyrazinyl, pyridazinyl, pyrimidinyl, benzimidazolyl, benzothiophenyl or benzofuranyl); amino (primary, secondary or tertiary); o-lower alkyl; o-aryl, aryl; aryl-lower alkyl; -CO2CH3; -CONH2; -OCH2CONH2; -NH2; -SON2NH2; -OCHF2; -CF3; -OCF3; -NH(alkyl); -N(alkyl)2; -NH(aryl); -N(alkyl)(aryl); -N(aryl)2; -CHO; -CO(alkyl); -CO(aryl); -CO2(alkyl); and -CO2(aryl); and further, such moieties may be optionally substituted by fused ring structures or bridges, e.g., -OCHO-. These substituents may optionally be further substituted with a substituent selected from such groups. All chemical groups disclosed herein may be substituted unless otherwise specified.
[0043] The term "olefin" refers to an unsaturated hydrocarbon-based compound containing at least one carbon-carbon double bond.
[0044] The term “halogen” or “halo” refers to F, Cl, Br or I.
[0045] The term "monomer unit" refers to a building block contributed to the structure of a polymer by a single monomer.
[0046] The term "structural unit" refers to all monomer units contributed by the same monomer type in a polymer.
[0047] The term "acid-base" refers to an acid salt formed when an acid reacts with a base or when an acid dissociates in an aqueous solvent such as water. In some embodiments, the protons of the acid are replaced with metal cations. In some embodiments, the protons of the acid are replaced with ammonium ions.
[0048] The term "polyatomic" refers to an electrically neutral group of three or more atoms held together by covalent bonds.
[0049] The term "polyprotic acid" refers to an acid that has two or more ionizable hydrogen ions (ie, protons) per molecule.
[0050] The term "hydrophilic" refers to the tendency to dissolve in or interact with polar solvents, especially water, or polar functional groups. Hydrophilic groups are usually polar themselves, and in many cases, such hydrophilic groups are capable of forming hydrogen bonds with water molecules. Some non-limiting hydrophilic groups include acid, hydroxyl, and amide.
[0051] The term "hydrophobic group" refers to a functional group that tends not to dissolve or interact with polar solvents, especially water, or polar functional groups. Hydrophobic groups are typically non-polar.
[0052] The number average molecular weight (M n The term "square root" is mathematically defined as follows:
[0053]
number
[0054] Here, N i is a specific molecular weight M i is the number of polymer molecules having
[0055] The weight average molecular weight (M w The term "square root of all non-zero" is mathematically defined as follows:
[0056]
number
[0057] Here, N i is a specific molecular weight M i is the number of polymer molecules having
[0058] The term "polydispersity index" or "PDI" refers to the number average molecular weight (M n ) to the weight average molecular weight (M w ) which is a measure of the distribution of molecular weights within a given polymer sample.
[0059] The term "planetary mixer" refers to a device that can be used to mix or stir different materials to produce a homogenous mixture, and consists of blades that perform planetary motion within a vessel. In some embodiments, the planetary mixer includes at least one planetary blade and at least one high-speed dispersion blade. The planetary blade and the high-speed dispersion blade rotate on their respective axes and also rotate continuously around the vessel. The rotation speed can be expressed in units of revolutions per minute (rpm), which refers to the number of revolutions that the rotor completes in one minute.
[0060] The term "ultrasonicator" refers to a device that can apply ultrasonic energy to agitate particles in a sample. Any ultrasonicator capable of dispersing the mixtures, suspensions, solutions or slurries disclosed herein can be used herein. Some non-limiting examples of ultrasonicators include ultrasonic baths, probe-type ultrasonicators, and ultrasonic flow cells.
[0061] The term "ultrasonic bath" refers to an instrument in which ultrasonic energy is transmitted to a liquid sample through the walls of the ultrasonic bath container.
[0062] The term "probe-type sonicator" refers to an ultrasonic probe that is immersed in a medium to perform direct sonication. The term "direct sonication" means that ultrasonic waves are coupled directly into the treatment liquid.
[0063] The term "ultrasonic flow cell" or "ultrasonic reactor chamber" refers to an instrument capable of performing sonication in a flow-through mode. In some embodiments, the ultrasonic flow cell is in a single pass, multi-pass, or recirculation configuration.
[0064] The term "application" refers to the act of laying or spreading a substance on a surface.
[0065] The term "current collector" refers to any conductive substrate that can contact the electrode layer and conduct the current flowing to the electrode during discharge or charging of the secondary battery. Some non-limiting examples of current collectors include a single conductive metal layer or substrate, and a single conductive metal layer or substrate having a conductive coating layer thereon, such as a carbon black-based coating layer. The conductive metal layer or substrate may be in the form of a foil or a porous body having a three-dimensional network structure, and may be a polymeric material or a metallic material or a metallized polymer. In some embodiments, the three-dimensional porous current collector is coated with a conformal carbon layer.
[0066] The term "electrode layer" refers to a layer comprising an electrochemically active material in contact with a current collector. In some embodiments, the electrode layer is made by applying a coating onto the current collector. In some embodiments, the electrode layer is located on one or both sides of the current collector. In other embodiments, a three-dimensional porous current collector is conformally coated with the electrode layer.
[0067] The term "room temperature" refers to a room temperature of about 18° C. to about 30° C., e.g., 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, or 30° C. In some embodiments, room temperature refers to a temperature of about 20° C.±1° C. or±2° C. or±3° C. In other embodiments, room temperature refers to a temperature of about 22° C. or about 25° C.
[0068] The term "solids" refers to the amount of non-volatile material remaining after evaporation.
[0069] The term "peel strength" refers to the amount of force required to separate a current collector and an electrode layer that are bonded together. It is a measure of the bond strength between such two materials and is usually expressed in N / cm.
[0070] The term "adhesive strength" refers to the amount of force required to separate a current collector and a polymer binder coating that are bonded together. It is a measure of the strength of the bond between such two materials and is usually expressed in N / cm.
[0071] The term "water soluble" refers to the ability of a substance to dissolve in water in trace amounts or with no substance remaining undissolved in water. The term "water soluble" encompasses the terms "completely water soluble," "mostly water soluble," and "slightly water insoluble."
[0072] In the following description, all numerical values disclosed herein are approximate, regardless of whether the word "about" or "approximately" is used in connection therewith. They may vary by 1 percent, 2 percent, 5 percent, or in some cases by 10 to 20 percent. L, and upper limit R U Whenever a numerical range is disclosed, any number falling within that range is specifically disclosed. Specifically disclosed are numbers within the following ranges: R=R L +k * (R U -R L ), where k is a variable ranging from 0 percent to 100 percent. Additionally, any numerical range defined by two R numbers defined above is specifically disclosed.
[0073] As used herein, all words in the singular include the plural and vice versa.
[0074] The method of the present invention is uniquely tailored and developed for the specific need of extracting a polymer from a first suspension, the first suspension comprising a polymer and an aqueous solvent. The polymer is water-soluble and utilizes an aqueous solvent, most commonly water, which forms the basis for making a water-based solution. The polymer can achieve good dispersibility and stability in water, which can significantly enhance the functional performance of the polymer. For example, when the polymer is a polymer binder, the adhesive force of the polymer binder that is well dispersed in water is significantly increased, resulting in an improved binding capacity of the polymer binder.
[0075] In developing a method for separating the polymer from the first suspension, it is necessary to understand how the polymer of the present invention can be dissolved and / or dispersed in the aqueous solvent when the first suspension is formed in the first place.
[0076] The dissolution of the polymer in the aqueous solvent when forming the first suspension is promoted by (1) intermolecular interactions (e.g. hydrogen bonds and ion-dipole interactions) between the polymer and the aqueous solvent, more specifically between ionized and / or uncharged species in the monomer that contribute to the constitution of the polymer and the molecules contained in the aqueous solvent; and (2) the deconjugation of some of the interactions between the water molecules in the aqueous solvent, especially in the region close to the polymer. These interactions become dominant over the intermolecular interactions between the copolymer chains in the polymer and the intramolecular interactions within the copolymer chains, resulting in the dissolution of the polymer in the aqueous solvent when forming the first suspension. During the dissolution or solvation process, the polymer and the aqueous solvent are reconstituted into a solvation complex, in which the polymer is surrounded by a concentric shell of polar molecules in the aqueous solvent, leading to the stabilization of the polymer in the first suspension.
[0077] Hydrogen bonding between a polymer and an aqueous solvent depends on the ability of each to form (ie, accept and / or donate) hydrogen bonds.
[0078] In some embodiments, the polymer comprises a copolymer. In some embodiments, the copolymer comprises a structural unit (a) derived from an acid group-containing monomer and a structural unit (b) derived from a nitrile group-containing monomer. In some embodiments, the copolymer comprises a structural unit (a) derived from an acid group-containing monomer, a structural unit (b) derived from a nitrile group-containing monomer, a structural unit (c) derived from an amide group-containing monomer, or a combination thereof. In some embodiments, the copolymer further comprises a structural unit (d) derived from a hydroxyl group-containing monomer, a structural unit (e) derived from an ester group-containing monomer, a structural unit (f) derived from an epoxy group-containing monomer, a structural unit (g) derived from a fluorine-containing monomer, or a combination thereof.
[0079] Each of the above monomers that can potentially constitute the copolymer consists independently of a strongly electronegative atom, in particular a nitrogen (N), oxygen (O) or fluorine (F) atom (known as a hydrogen bond donor, Dn), covalently bonded to a hydrogen (H) atom or to another electronegative atom that has a lone pair of electrons in the outermost electron shell of the atom (known as a hydrogen bond acceptor, Ac). This allows for the formation of hydrogen bonds with another molecule that has the same characteristics (e.g., a water molecule present in an aqueous solvent). Thus, each of the above monomers independently contains at least one hydrogen bond-forming group. The hydrogen bond-forming system is generally represented by the following formula (1):
[0080] [ka]
[0081] where Dn is a hydrogen bond donor; Ac is a hydrogen bond acceptor; solid lines indicate polar covalent bonds and dotted lines indicate hydrogen bonds.
[0082] In some embodiments, the structural unit (a) derived from an acid group-containing monomer comprises an acid salt group. In some embodiments, the acid salt group is a salt of an acid group. The anion of the acid salt group can form an ion-dipole interaction with a partially positively charged species (e.g., a partial positive charge near a hydrogen atom of a water molecule resulting from an uneven distribution of electron density in the water molecule). In some embodiments, the structural unit (a) comprises an alkali metal acid salt group. Examples of alkali metals that form alkali metal salts include lithium, sodium, and potassium. In some embodiments, the structural unit (a) comprises an ammonium acid salt group.
[0083] In some embodiments, the aqueous solvent is a solution that contains water as a major component and, in addition to water, contains, as minor components, volatile solvents such as alcohols, lower aliphatic ketones, lower alkyl acetates, etc. In some embodiments, the aqueous solvent consists solely of water.
[0084] The hydroxyl group of water consists of an H atom covalently bonded to a more electronegative O atom and an electronegative O atom with a lone pair in its outermost electron shell, either of which can form hydrogen bonds with other species (e.g., monomers that aid in polymer structure) that can interact via hydrogen bonds (i.e., molecules that contain (i) an H atom covalently bonded to a hydrogen bond donor and / or (ii) a hydrogen bond acceptor). Water's ability to accept and donate hydrogen bonds makes it an excellent candidate for solvating polymers.
[0085] When an aqueous solvent contains, in addition to water, a minor component capable of forming hydrogen bonds, it is possible that hydrogen bonding interactions can occur between the minor component and another hydrogen bond-forming molecule (e.g., the hydrogen bond-forming group of a monomer that contributes to the formation of a polymer).
[0086] In regions where the hydrogen-bonding moieties in the aqueous solvent are in close proximity to the polymer (e.g., inside the solvation shell around the polymer), relatively strong interactions between the polymer and the aqueous solvent occur, disrupting the hydrogen bonds formed between the hydrogen-bonding molecules in the aqueous solvent. Conversely, hydrogen-bonding interactions between molecules in the aqueous solvent remain in regions where these molecules are distant from the polymer (e.g., the outer solvation shell around the polymer).
[0087] The polarity of an aqueous solvent is another most important factor that determines how well an aqueous solvent solvates a polymer. A polar molecule contains at least one polar bond formed by the difference in electronegativity between the bonded atoms. The electron pairs shared between the bonded atoms tend to be attracted to the more electronegative atom, resulting in a biased distribution of bond electron pairs. The more electronegative atom gains a partial negative charge, while the less electronegative atom has a partial positive charge. This separation of positive and negative charges results in a bond dipole moment. For polyatomic molecules, the dipole moment of the molecule is the vector sum of all the bond dipole moments present in the molecule. A polar molecule with two or more polar bonds has a net dipole due to the opposite charges from the polar bonds that are asymmetrically arranged in at least one direction, and the bond dipole moments do not cancel each other out. A water molecule, for example, is a polar molecule because the bond dipole moments present in the molecule do not cancel out, resulting in a net dipole.
[0088] Polar molecules in the aqueous solvent (e.g., water molecules) solvate the charged species in the polymer (e.g., anions of the acid-base groups of the monomers that help build the polymer) by directing the appropriate partially charged portion of the molecule toward the charged species through electrostatic attraction, forming a solvation shell (in the case of water, a hydration shell) around each charged species through ion-dipole interactions between the polymer and the aqueous solvent, allowing the polymer to dissolve in the aqueous solvent in forming the first suspension.
[0089] Hydrogen bonding and / or ion-dipole attraction are the two main types of interactions formed between the polymer and the aqueous solvent that lead to the formation of solvation complexes. Both contribute independently to different extents to the dissolution of the polymer, depending on the molecular structure, composition, and nature of the polymer and the aqueous solvent. The solvation of the polymer in the aqueous solvent can proceed through other means of intermolecular interactions, such as ionic interactions, London dispersion forces, dipole-dipole interactions, dipole-induced dipole interactions, and ion-induced dipole interactions. However, taking into account the molecular structure of the polymer, the main electrostatic interactions that lead to the solvation of the polymer by the aqueous solvent occur through hydrogen bonding and / or ion-dipole interactions. The other interactions mentioned above that may occur to a lesser extent between the polymer and the aqueous solvent can also be disrupted based on the proposed mechanism through the introduction of a precipitant that allows the precipitation of the polymer. These interactions are not shown for ease of interpretation.
[0090] Figure 1 shows a schematic diagram of one embodiment of a proposed interaction between the polymer and the aqueous solvent in the first suspension. The bold polymeric compound represents an embodiment of a polymer comprising a copolymer comprising structural units derived from a carboxylic acid group-containing monomer, a nitrile group-containing monomer, and an amide group-containing monomer. In this case, the structural units derived from the carboxylic acid group-containing monomer comprise a carboxylate salt group, which is a salt of a carboxylic acid group. The aqueous solvent in this case comprises water.
[0091] The oxygen (O), nitrogen (N) and hydrogen (H) atoms present in the copolymer of the polymer tend to interact with the O and / or H atoms of water molecules in the aqueous solvent by forming hydrogen bonds. Also, the carboxylate groups contained in the polymer, in this case COO -, and the partial positive charges near the hydrogen atoms of water molecules in the aqueous solvent through ion-dipole interactions. Hydrogen bonds and / or ion-dipole attractions are the two main types of interactions formed between the polymer and the aqueous solvent in the first suspension, and independently contribute greatly to the solvation and dissolution of the polymer by the aqueous solvent in the formation of the first suspension. Also, the hydrogen bonds initially formed between the water molecules in the aqueous solvent close to the polymer (i.e., the inner solvation shell around the polymer) will break down with the onset of a relatively strong interaction between the polymer and the aqueous solvent. Meanwhile, the hydrogen bonds between the water molecules located away from the polymer (i.e., the outer solvation shell around the polymer) will persist because these molecules are much less likely to be broken by the interaction between the polymer and the aqueous solvent.
[0092] It is found that the ability of a polymer to dissolve in water and distribute uniformly among water molecules substantially improves the specific functional performance of the polymer. The polymers disclosed herein are designed to have such ability in their dissolution and excellent dispersion in aqueous solvents through hydrogen bonding and / or ion-dipole interactions between the polymer and the aqueous solvent. The design of the polymers disclosed herein can be utilized as polymer binders to provide exceptionally strong binding capacity for various applications. In some embodiments, the copolymer of the polymer comprises structural units derived from acid group-containing monomers and structural units derived from hydrophobic group-containing monomers. In some embodiments, the polymers can be used for other purposes besides as polymer binders.
[0093] However, a dissolved and well-dispersed polymer within the first suspension poses additional challenges in the separation of the water-soluble polymer from the respective first suspension in a subsequent recycling step when the polymer-containing product reaches the end of its life or when product rejection occurs during production.
[0094] Copolymers in polymers of different compositions exhibiting various specific properties will require different approaches in extraction by breaking the initially formed solvation complex to allow the release of the copolymer from the aqueous solvent. Therefore, the method of the present invention has been developed specifically for precipitating a polymer from a first suspension. More specifically, the method of the present invention has been developed for precipitating a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer from a first suspension. Optionally, the copolymer further comprises structural units derived from a hydrogen bond-forming group-containing monomer. The hydrogen bond-forming group-containing monomer may be an amide group-containing monomer, a hydroxyl group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, a fluorine-containing monomer, or a combination thereof.
[0095] The precipitation of the polymers disclosed herein is driven by two main events: (1) various types of interactions that result in the separation of the polymer from the aqueous medium, and (2) the subsequent conformational transition of the polymer.
[0096] Upon addition of the precipitant, the polymer is separated from the aqueous solvent in the first suspension via (i) bond breaking and / or scission between the copolymer of polymers and the aqueous solvent, (ii) weakening of the intermolecular attractive forces between the molecules in the aqueous solvent in the formation of a solvation complex, (iii) protonation of the conjugate base of the acid group-containing monomer that contributes to the constitution of the polymer, (iv) formation of intramolecular interactions between various functional groups in the copolymer chain, and (v) development of intermolecular interactions between the copolymer chains. Following the initiation of bond breaking between the copolymer of polymers and the aqueous solvent, the other types of interactions mentioned above occur in any order, resulting in the separation of the polymer from the aqueous solvent. The polymers disclosed herein then undergo a coil-to-globule structural transition.
[0097] The present invention provides a method of precipitating a polymer by adding a precipitating agent to a first suspension to form a second suspension; the first suspension comprises a polymer and an aqueous solvent; and the polymer comprises a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer.
[0098] In some embodiments, the precipitating agent is an acid, hi some embodiments, the precipitating agent is a strong acid.
[0099] The strength of an acid refers to the tendency of the acid to dissociate in a solvent (most commonly water) into a proton and the acid's conjugate base. The degree of ionization of an acid is usually measured using the acid dissociation constant (K a ) Strong acids have a larger K a Therefore, the negative logarithm of the acid dissociation constant (pK a , -logK a The stronger the acid, the more protons (i.e., hydrogen ions, H + ) and vice versa.
[0100] In some embodiments, the first suspension disclosed herein comprises an aqueous solvent comprising water. When a strong acid is added to the first suspension disclosed herein in forming the second suspension, dissociation of the strong acid in water occurs when the acid loses a proton and the water molecule becomes a hydroxonium ion (HO + The dissociation reaction of the strong acids mentioned above is generally represented as follows:
[0101] [ka]
[0102] Here, HA1 is a strong acid used as a precipitant, HO is a water molecule, and HO + is a hydroxonium ion, and A1 - is the conjugate base of acid HA1.
[0103] In some embodiments, the precipitating agent is a weak acid.
[0104] Upon incorporation of the weak acid into the first suspension in forming the second suspension, the weak acid only partially dissociates with both the undissociated weak acid and its dissociation products present in the second suspension, the dissociation of said weak acid being represented by the following reaction:
[0105] [ka]
[0106] Here, HA2 is a weak acid used as a precipitant, and A2 - is the conjugate base of the acid HA2.
[0107] Dissociation of the weak acid in the second suspension involves reaction of a water molecule with a proton from the acid in the production of a hydroxonium ion.
[0108] The presence of hydroxonium ions in the second suspension, whether generated from the dissociation of a strong or weak acid, removes the hydrogen bond formation sites and ion-dipole interaction sites originally present in the water molecules, disrupting and breaking down the electrostatic attraction (i.e., hydrogen bonds and / or ion-dipole interactions) initially formed between the polymer and the water molecules in the aqueous solvent, resulting in the collapse of the solvation shell formed around the polymer and the reduced solubility of the polymer in the aqueous solvent.
[0109] Furthermore, with the formation of hydroxonium ions accompanied by a significant decrease in water molecules in the surrounding area of the polymer in the second suspension, hydrogen bonds between water molecules in the solvation shell around the polymer are sharply decreased, further collapsing the solvation shell developed around the polymer.
[0110] On the other hand, the formed hydroxonium ion may protonate ionized species in the monomers that contribute to the formation of the polymer (e.g., anions of acid-group-containing monomers), potentially facilitating the conversion of negatively charged species to their protonated, uncharged forms, as shown in the following reaction scheme:
[0111] [ka]
[0112] where HA3 is a monomer that helps build the polymer, and A3 - is the conjugate base of monomeric HA3.
[0113] When the hydroxonium ion protonates the anion of an acid salt group-containing monomer that constitutes the building block of the polymer, the acid salt group is converted into an acid group.
[0114] To promote preferential dissociation of the acid used as a precipitant and uptake of protons in the second suspension by the ionized species in the monomer that contribute to the construction of the polymer, (1) the pK a The value is the pK of the acid group-containing monomer that constitutes the polymer. a (2) when the precipitant is added to the first suspension to form the second suspension, the pH value of the second suspension is preferably lower than the pK value of the acid group-containing monomer that constitutes the polymer; a It is desirable to have a value well below this.
[0115] pK a The pK value quantifies the degree of dissociation of an acid in a solvent such as water. a The pK value of the acid group-containing monomer that contributes to the formation of the polymer aIf the pK of the acid used as the precipitant is lower than this value, the acid will tend to dissociate, shifting the equilibrium position of the reaction in Equation 2 to the right, and the acid will likely ionize upon contact with the first suspension, resulting in the formation of hydroxonium ions. On the other hand, the acid-containing monomer will have a higher pK than the acid used as the precipitant. a Since the value is relatively high, the conjugate base of the acid group-containing monomer is easily protonated, and the equilibrium position of the reaction in Reaction Scheme 3 is located on the right side, and some of the hydroxonium ions produced by the dissociation of the acid used as the precipitant are absorbed.
[0116] When an acid serving as a precipitant is added to the first suspension, the acid undergoes dissociation to generate hydroxonium ions to form the second suspension. In the present invention, it would be highly preferred to increase the concentration of hydroxonium ions in the second suspension by using a stronger acid and / or the amount of acid serving as a precipitant added to the first suspension. The presence of a high concentration of hydroxonium ions in the second suspension not only aids in the separation of the polymer from the aqueous medium by aiding in the bond breaking process, but also shifts the equilibrium position of the reaction of Equation 3 further to the right, protonating the conjugate base of the acid group-containing monomer that contributes to the construction of the polymer.
[0117] The pH value indicates the concentration of hydroxonium ions (equivalent to hydrogen ions) in a solution, and is expressed as pH=log[HO + It can be calculated by the formula: pH = 1 / 2. It is used to specify the acidity or alkalinity of a solution. A solution with a high concentration of hydroxonium ions will have a low pH value and vice versa. Therefore, to achieve a high concentration of hydroxonium ions, it is desirable for the pH of the second suspension to be low enough to allow protonation of most of the conjugate bases of the acid group-containing monomers. This can potentially wipe out the presence of the charged conjugate bases of the acid group-containing monomers (e.g., acid-base-containing monomers) and eliminate further ion-dipole interactions between the polymer originally present in the first suspension and the aqueous solvent.
[0118] Due to the destruction of the electrostatic attraction between the polymer and the aqueous solvent caused by the addition of the precipitant, the functional groups contained within the polymer have a higher affinity to interact with each other. For example, the H atom of the carboxyl group in a polymer is more likely to interact with the N atom of the nitrile group in the same polymer through hydrogen bonding interactions. There may also be dipole-dipole interactions between the O atom of the carboxyl group in a polymer and the C atom of the nitrile group in the same polymer.
[0119] Furthermore, as the intermolecular interactions between the polymer and the aqueous solvent become weaker, the copolymer chains within the polymer tend to interact with each other. For example, the arrangement of interaction pairs between the nitrile (C≡N) group of one copolymer chain and the carboxyl (COOH) group of another copolymer chain may proceed via the formation of hydrogen bonds. Also, dipole-dipole interactions may be found between the nitrile (C≡N) groups of different copolymer chains. Hydrogen bonds may also be formed between the hydroxyl (OH) groups in the carboxyl (COOH) groups of different copolymer chains.
[0120] The separation of the polymers disclosed herein from the aqueous medium is achieved upon addition of a precipitant through the involvement of the various types of interactions described above. This effect, combined with the specific preparation of the polymers of the present invention, allows for the structural conformation of the polymer from coil to globule. The polymer can then be precipitated.
[0121] By controlling the pH of the second suspension sufficiently low, the conjugate base of the acid group-containing monomer that contributes to the construction of the polymer is highly protonated, which promotes the coil-to-globule structural transition of the polymer disclosed herein.
[0122] Prior to the addition of the precipitant, negatively charged species in monomers that contribute to the formation of the polymer with similar charges (e.g., anions of acid-group containing monomers) effectively repel each other. The electrostatic repulsion of the ionized groups causes the charged polymer to expand into a fully solvated open-coil conformation.
[0123] Upon addition of a precipitant that produces a second suspension of sufficiently low pH, protonation of most of the conjugate bases of the acid group-containing monomers that contribute to the formation of the polymer converts the originally charged polymer into an uncharged form in which electrostatic repulsion is no longer exerted, which significantly weakens the intermolecular interactions (especially ion-dipole interactions) between the structural units derived from the acid group-containing monomers and the aqueous solvent, initiating the aggregation of the polymer.
[0124] Furthermore, the apparent intramolecular interactions between the functional groups within the copolymer chains and the intermolecular interactions between the copolymer chains further promote the winding of the polymer and aid in the transition of the polymer into a compact globular conformation.
[0125] In some embodiments, the polymers disclosed herein include copolymers that include structural units derived from acid group-containing monomers and structural units derived from hydrophobic group-containing monomers.
[0126] Acid groups (e.g., carboxylic acid groups) are one of the important functional groups present in polymers that are polar in nature due to the electronegativity difference between the carbon (C) and oxygen (O) atoms in the carbonyl group and between the oxygen (O) and hydrogen (H) atoms in the hydroxyl group. These atoms have an unequal charge distribution, which gives them a net dipole moment, making the acid group polar. Thus, the acid group can participate in hydrogen bond formation and / or dipole-dipole interactions. Acid groups are highly hydrophilic, which means that acid groups are highly soluble in aqueous solvents (e.g., water).
[0127] An example of a hydrophobic group-containing monomer is a nitrile group-containing monomer. Nitrile groups are polar in nature because the nitrogen (N) atom contained within them is more electronegative than the carbon (C) atom. The electrons shared between the covalently bonded C and N are more strongly attracted to the N atom than to the C atom. Thus, δ+ C≡N δ- As shown in the form, the N atom carries a partial negative charge and the C atom carries a partial positive charge.
[0128] Most literature classifies polar groups or compounds as hydrophilic and non-polar groups or compounds as hydrophobic. This clear classification is valid for most polar compounds such as alcohols and amides, but not for some other polar compounds, except for nitriles.
[0129] The nitrogen (N) atom of the nitrile group (-C≡N) has the potential to act as a proton (i.e., hydrogen ion) acceptor to form hydrogen bonds with water molecules in aqueous solvents due to the presence of one lone pair orbital. However, since there is only one hydrogen acceptor per nitrile group, the interaction that occurs between the nitrile group and water molecules is significantly weaker than the interaction between water molecules and other polar groups (e.g., acid and amide groups) that contain at least one hydrogen bond donor and acceptor per group. This provides an explanation for the extremely low water solubility of nitriles such as polyacrylonitrile (PAN), which is dominated by the behavior of the hydrophobic alkyl backbone. Thus, the nitrile group is hydrophobic.
[0130] The presence of hydrophobic functional groups in the structural units (e.g., structural units derived from nitrile group-containing monomers) in the polymers disclosed herein exerts a hydrophobic tendency on the entire copolymer of the polymer. The degree of hydrophobicity of the polymer can be determined according to the proportion of hydrophobic groups contained in the polymer. The higher the proportion of hydrophobic groups contained in the polymer, the more hydrophobic the polymer is, and therefore the more insoluble it is in water. The hydrophobicity of the polymers disclosed herein, which include structural units derived from nitrile group-containing monomers, minimizes the contact surface area between the polymer and water molecules in an aqueous solvent, and the polymer collapses into a more dense globular structure.
[0131] As a result, the combined effects of (1) various types of interactions resulting in the separation of the polymer from the aqueous medium, (2) the presence of hydrophobic structural units in the polymer, and (3) the subsequent conformational transition of the polymer induces a phase transition of the polymer into a compact solid globule, resulting in the precipitation of the polymer. This pH-induced conformational transition of the polymer minimizes the contact between the polymer and water molecules in the aqueous medium, causing a decrease in the permeability of the polymer to the flow of water molecules.
[0132] Figure 2 shows a schematic diagram of one embodiment of the proposed change in the interaction between the polymer and the aqueous solvent outlined in Figure 1 when a sufficient concentration of a precipitating agent is added to the first suspension. The bolded polymeric compound shows an embodiment of a polymer that includes a copolymer that includes structural units derived from a carboxylic acid group-containing monomer, a nitrile group-containing monomer, and an amide group-containing monomer. The precipitating agent in this case includes hydrochloric acid, which is a strong acid, and the aqueous solvent in this case includes.
[0133] When hydrochloric acid is added to the first suspension, complete dissociation of the hydrochloric acid in water occurs: the acid loses a proton and the water molecule picks up a proton to form a hydroxonium ion, as shown below.
[0134] [ka]
[0135] The hydroxonium ions produced by the ionization of hydrochloric acid eliminate most of the hydrogen bond formation and ion-dipole interaction sites built into the water molecules, which significantly disrupts the intermolecular interactions that would otherwise be established between the polymer and the water molecules, as shown in Figure 1. This reduces the degree of solvation of the polymer by the water molecules in the second suspension.
[0136] The significant reduction in water molecules in the area surrounding the polymer in the second suspension due to the formation of hydroxonium ions significantly weakens the strength of the hydrogen bonds between the water molecules in the solvation shell around the polymer, resulting in the destruction of the solvation shell formed around the polymer, allowing the polymer to be closer to or more exposed to other polymer chains in generating electrostatic attraction.
[0137] The hydroxonium ion formed from the dissociation of hydrochloric acid tends to protonate the anion of the carboxylate group-containing monomer (in this case, the salts of acrylic and methacrylic acids shown in FIG. 2) that contributes to the formation of the polymer illustrated in FIG. 1. The protonation reaction of the carboxylate group-containing monomer is shown in Equation 5 below.
[0138] [ka]
[0139] where R1COOH is a carboxylic acid group-containing monomer that aids in the construction of the polymer, and R1COO - is the conjugate base of the monomer RCOOH (i.e., the carboxylate group-containing monomer).
[0140] Before the introduction of hydrochloric acid into the first suspension, the anions of the carboxylate-containing monomers that contribute to the construction of the polymer exert electrostatic repulsion with each other, resulting in a charged polymer with a fully solvated coil structure. The coil structure of the charged polymer can be visualized in FIG. 3A. However, when the carboxylate-containing monomers are protonated, the negatively charged acid groups are transformed into uncharged acid groups in the monomers, which become the building blocks of the polymer. Since there is no repulsive force within the polymer, the winding motion of the polymer is initiated.
[0141] As shown in Figure 2, acid group-containing monomers that aid in the construction of polymers include acrylic acid and methacrylic acid. Acrylic acid has a pK a value is 4.3, and methacrylic acid has a pK a The pK value of hydrochloric acid is 4.7. a The pK of hydrochloric acid (HCI) is -6.3. a Values are the pK values for both acrylic acid and methacrylic acid. a significantly smaller than the pK value (i.e., −6.3 ( a ) << 4.3 (pK of acrylic acid a ) and 4.7 (pK of methacrylic acid a ), whereas hydrochloric acid has a much stronger tendency to dissociate to produce hydroxonium ions. The strength of hydrochloric acid is so high that it has been confirmed to completely dissociate, as shown in reaction 4. Conversely, salts of acrylic acid and methacrylic acid are more likely to be protonated, shifting the reaction equilibrium in reaction 5 to the right. The protonation of salts of acrylic acid and methacrylic acid involves the incorporation of some of the protons generated by the dissociation of hydrochloric acid when producing acrylic acid and methacrylic acid.
[0142] In FIG. 2, when hydrochloric acid is added to the first suspension, the acid undergoes ionization to produce hydroxonium ions, leading to the formation of a second suspension. The pH of the second suspension in this case is 2, meaning that there is a high concentration of hydroxonium ions in the second suspension. This shifts the equilibrium position of the reaction in Equation 5 further to the right, converting most of the acrylic and methacrylic acid salts to their uncharged acid forms and breaking up further ion-dipole interactions between the carboxylate group-containing monomers and water molecules originally present in the first suspension.
[0143] Following the destruction of the electrostatic interaction between the polymer and the water molecules in the aqueous solvent resulting from the addition of hydrochloric acid, the N atom of the nitrile group in the copolymer chain 101 is found to interact with the H atom of the carboxyl group in the same copolymer chain through hydrogen bonding interactions. Furthermore, it is found that a hydrogen bond is formed between the H atom of the amide group in the copolymer chain 101 and the O atom of the carbonyl group of the carboxyl group. Meanwhile, a hydrogen bond also occurs between the H atom of the carboxyl group in the copolymer chain 201 and the O atom of the amide group.
[0144] The interactions occur not only between various functional groups within the same copolymer chain, but also between different copolymer chains. Hydrogen bonds are formed between the hydroxyl (OH) group in the carboxyl group of copolymer chain 101 and the carbonyl (C=O) group in the carboxyl group of copolymer chain 201. Also, the NH group of the amide group of copolymer chain 101 interacts with the nitrile (C≡N) group of copolymer chain 201 through hydrogen bond interactions.
[0145] The independent intramolecular interactions between the functional groups in copolymer chain 101 and copolymer chain 201 and the intermolecular interactions between the copolymer chains further promote the coiling of the polymer into a compact globular conformation, inducing precipitation of the polymer. This globular structure of the uncharged polymer can be visualized in FIG. 3B, which displays an embodiment of the structural conformation of the polymer after addition of a precipitating agent to the first suspension.
[0146] Figure 4 outlines one embodiment of the proposed change in the interaction between the polymer and the aqueous solvent outlined in Figure 1 by adding an insufficient amount or concentration of precipitant to the first suspension to form a second suspension with a higher pH. The bolded polymeric compound illustrates one embodiment of a polymer that includes a copolymer that includes structural units derived from a carboxylic acid group-containing monomer, a nitrile group-containing monomer, and an amide group-containing monomer. The precipitant in this case includes hydrochloric acid, a strong acid, and the aqueous solvent in this case includes water.
[0147] Hydrochloric acid dissociates to produce hydroxonium ions when the acid is added to the first suspension in forming the second suspension. Despite the use of a strong acid as the precipitant, the acid used is quite dilute, so the pH of the second suspension in this case is 5, which means that the hydroxonium ion concentration in the second suspension is much lower than in Figure 2.
[0148] The low concentration of hydroxonium ions in the second suspension is insufficient to break the intermolecular attraction previously created between the polymer and water molecules, as shown in Figure 1. There are parts of the polymer that are still solvated by the water molecules. In addition, some of the hydrogen bonds formed between the water molecules remain in the solvation shell around the copolymer chains, inhibiting the access of the copolymer chains to other copolymer chains in the occurrence of interactions. The acid group-containing monomers that help in the construction of the polymer as shown in Figure 4 include acrylic acid and methacrylic acid. The small amount of hydroxonium ions in the second suspension can only change some of the salts of acrylic acid and methacrylic acid to their uncharged acid forms. Thus, some of the ion-dipole interactions between the acid-base-containing monomers and the water molecules persist in the first suspension. Furthermore, due to insufficient bond breaking between the polymer and the water molecules, the intramolecular attraction between the functional groups in the same copolymer chain does not occur much. This situation makes the structural conformation of the polymer from a coil to a globule particularly difficult, and the precipitation of the polymer could not be achieved.
[0149] FIG. 5 shows a schematic of one embodiment of a proposed change in the interaction between a polymer, including a copolymer including structural units derived from one or more carboxylic acid group-containing monomers, and an aqueous solvent when a sufficient concentration of a precipitant is added to the first suspension. The bold polymeric compounds represent polymers. The precipitant in this case includes hydrochloric acid, a strong acid, and the aqueous solvent in this case includes water. The symbols R1, R2, R3, and R4 in FIG. 5 each independently represent a compound of the general formula C n H 2n where n is an integer greater than 0. The H atoms in the above general formula may be unsubstituted or substituted with one or more suitable substituents without affecting the functionality of the overall polymer. Each of R1, R2, R3, and R4 may independently be the same or different from each other.
[0150] When hydrochloric acid is added to the first suspension, the acid dissociates and hydroxonium ions are generated, leading to the formation of the second suspension. However, if the entire copolymer chain contains structural units derived only from acid group-containing monomers, a large amount of protons are taken up to protonate the acid-base of the polymer to acid groups. Therefore, in the area near the polymer, a significant amount of hydroxonium ions return to water molecules, and hydrogen bonds are formed between the acid group-containing monomer and water molecules that help build the polymer. Also, since the entire copolymer chain contains structural units derived only from acid group-containing monomers, there may be some parts of the acid-base of the polymer that do not undergo protonation due to the nature of equilibrium, the orientation of the entities involved, and the relatively high demand in protonation. Therefore, the acid-base-containing monomers are still able to interact with the water molecules via ion-dipole interactions. The electrostatic attraction between the polymer and the water molecules cannot be completely broken, so the precipitation of the polymer cannot be achieved. This justifies the inability of polyacrylic acid (PAA) to precipitate in the first suspension.
[0151] The method of the present invention is specifically developed for precipitating polymers, including copolymers containing structural units (a) derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer. According to our research, if either the structural units derived from the acid group-containing monomer or the hydrophobic group-containing monomer are not present in the polymer, precipitation of the polymer will not occur. An example of a hydrophobic group-containing monomer is a nitrile group-containing monomer. If the structural units derived from the acid group-containing monomer are not present in the polymer, the polymer containing only structural units derived from the nitrile group-containing monomer will not be miscible with water in the first place, since the entire polymer chain is essentially hydrophobic. This type of polymer is known as a non-aqueous polymer. The method of the present invention is not applicable to the precipitation of non-aqueous polymers. In another case where structural units derived from hydrophobic group-containing monomers such as nitrile group-containing monomers are released from the polymer, when a precipitant is added in the first suspension, the polymer containing only structural units derived from the acid group-containing monomer cannot be separated from the aqueous solvent and may not be able to undergo a coil-to-globule structural transition, and therefore precipitation of the polymer is not observed. Thus, even if a precipitant is added to the first suspension, the intermolecular attraction between the polymer and water molecules persists, so separation of the acid group-containing monomer from the aqueous solvent could not be achieved. The inability to undergo structural conformation is due to the absence of hydrophobic functional groups in the structural units of the polymer that are required to trigger the polymer structural transition, initiate the phase transition process, and result in the precipitation of the polymer. Therefore, for successful precipitation of the polymer, it is recommended that the structural units (a) derived from the acid group-containing monomer and the structural units derived from the hydrophobic group-containing monomer are both present in the copolymer of the polymer.
[0152] In some embodiments, the first suspension comprises a polymer and an aqueous solvent. In some embodiments, the polymer comprises a copolymer. The polymer is soluble in water and some other aqueous solvents.
[0153] In some embodiments, the copolymer comprises at least one structural unit derived from a polar group-containing monomer, which determines the type and strength of intermolecular interactions (e.g., dipole-dipole interactions and hydrogen bonds) that develop between the polymer and the aqueous solvent, and can potentially facilitate dissolution of the polymer in the aqueous solvent when forming the first suspension.
[0154] Structural units derived from acid group-containing monomers, nitrile group-containing monomers, amide group-containing monomers, hydroxyl group-containing monomers, ester group-containing monomers, epoxy group-containing monomers, fluorine-containing monomers, or combinations thereof, contained within the copolymer in the polymer constitute some non-limiting examples of functional groups capable of forming intermolecular interactions (e.g., hydrogen bonds) with components of the aqueous solvent.
[0155] In some embodiments, the polar group-containing monomer is selected from the group consisting of an acid group-containing monomer and a nitrile group-containing monomer. In some embodiments, the polar group-containing monomer is selected from the group consisting of an acid group-containing monomer, a nitrile group-containing monomer, an amide group-containing monomer, or a combination thereof. In some embodiments, the polar group-containing monomer is selected from the group consisting of an acid group-containing monomer, a nitrile group-containing monomer, an amide group-containing monomer, a hydroxyl group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, a fluorine-containing monomer, or a combination thereof. In some embodiments, the polar group-containing monomer is selected from the group consisting of an amide group-containing monomer, a hydroxyl group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, a fluorine-containing monomer, or a combination thereof. In some embodiments, the copolymer does not include structural units derived from an amide group-containing monomer, a hydroxyl group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, a fluorine-containing monomer, or a combination thereof.
[0156] In some embodiments, the proportion of structural units derived from polar group-containing monomers is about 40 mol% to about 100 mol%, about 45 mol% to about 100 mol%, about 50 mol% to about 100 mol%, about 55 mol% to about 100 mol%, about 60 mol% to about 100 mol%, about 65 mol% to about 100 mol%, about 70 mol% to about 100 mol%, about 40 mol% to about 95 mol%, about 45 mol% to about 95 mol%, about 50 mol% to about 95 mol%, about 55 mol% to about 95 mol%, about 60 ...70 mol% to about 100 mol%, about 40 mol% to about 95 mol%, about 45 mol% to about 95 mol%, about 50 mol% to about 95 mol%, about 55 mol% to about 95 mol%, about 70 mol% to about 100 mol%, about 40 mol% to about 95 mol%, about 40 mol% to about 95 mol%, about 40 mol% to about 95 mol%, about 95 mol%, about 65 mol% to about 95 mol%, about 40 mol% to about 90 mol%, about 45 mol% to about 90 mol%, about 50 mol% to about 90 mol%, about 55 mol% to about 90 mol%, about 60 mol% to about 90 mol%, about 40 mol% to about 85 mol%, about 45 mol% to about 85 mol%, about 50 mol% to about 85 mol%, about 55 mol% to about 85 mol%, about 40 mol% to about 80 mol%, about 45 mol% to about 80 mol%, about 50 mol% to about 80 mol%, about 40 mol% to about 75 mol%, about 40 mol% to about 70 mol%, or about 45 mol% to about 75 mol%.
[0157] In some embodiments, the percentage of structural units derived from polar group-containing monomers is less than 100 mol%, less than 95 mol%, less than 90 mol%, less than 85 mol%, less than 80 mol%, less than 75 mol%, less than 70 mol%, less than 65 mol%, less than 60 mol%, less than 55 mol%, less than 50 mol%, or less than 45 mol%, based on the total number of moles of monomer units in the copolymer within the polymer. In some embodiments, the percentage of structural units derived from polar group-containing monomers is greater than 40 mol%, greater than 45 mol%, greater than 50 mol%, greater than 55 mol%, greater than 60 mol%, greater than 65 mol%, greater than 70 mol%, greater than 75 mol%, greater than 80 mol%, greater than 85 mol%, greater than 90 mol%, or greater than 95 mol%, based on the total number of moles of monomer units in the copolymer within the polymer.
[0158] In some embodiments, the polymer comprises a copolymer comprising at least one structural unit derived from a hydrophilic group-containing monomer and at least one structural unit derived from a hydrophobic group-containing monomer.
[0159] In some embodiments, the hydrophilic group-containing monomer is selected from the group consisting of an acid group-containing monomer. In some embodiments, the hydrophilic group-containing monomer is selected from the group consisting of an acid group-containing monomer, an amide group-containing monomer, a hydroxyl group-containing monomer, or a combination thereof. In some embodiments, the hydrophilic group-containing monomer is selected from the group consisting of an amide group-containing monomer, a hydroxyl group-containing monomer, or a combination thereof. In some embodiments, the hydrophobic group-containing monomer is selected from the group consisting of a nitrile group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, a fluoro group-containing monomer, or a combination thereof. content a monomer having a carboxylic acid, a carboxylic acid derivative, a carboxylic acid ester ...
[0160] Hydrophilic functional groups are highly soluble in water. The presence of hydrophilic functional groups in structural units in a polymer can provide a degree of hydrophilic character to the overall properties of the entire copolymer chain of the polymer, potentially improving the solubility of the polymer in water. Therefore, the proportion of structural units derived from hydrophilic group-containing monomers in the copolymer is important in controlling the solubility of the polymer in aqueous solvents. If an insufficient proportion of hydrophilic group-containing monomers contributes to the constitution of the polymer, solvation of the polymer will not occur and the polymer may remain undissolved in the aqueous solvent. This polymer type is called a non-aqueous polymer. Therefore, it is not necessary to apply the method of the present invention to precipitate non-aqueous polymers. However, if the proportion of structural units derived from hydrophilic group-containing monomers in the copolymer is excessively high, the polymer will remain dissolved in the aqueous solvent even if a precipitating agent is added to the first suspension, since separation of the excess amount of hydrophilic group-containing monomer from the aqueous solvent is not possible.
[0161] On the other hand, the hydrophobic functional groups in the polymer give the polymer a degree of hydrophobic effect, allowing the polymer segments to aggregate and avoid contact with water molecules and aqueous solvents. The structural units derived from hydrophobic group-containing monomers cause the polymer to bend into a globular structural conformation. A lack of structural units derived from hydrophobic group-containing monomers in the copolymer will result in a lack of hydrophobic functional groups required to cause a change in the polymer's conformation and initiate the polymer's phase transition, and the polymer will not be able to undergo a coil-to-globule structural transition. On the other hand, an excessively high ratio of structural units derived from hydrophobic group-containing monomers in the copolymer will make the polymer highly insoluble in water and will be considered a non-aqueous polymer. Such polymers will not fall within the scope of the present invention.
[0162] In some embodiments, the respective proportions of structural units derived from hydrophilic group-containing monomers and structural units derived from hydrophobic group-containing monomers are independently from about 0 mol % to about 85 mol %, from about 0 mol % to about 80 mol %, from about 0 mol % to about 75 mol %, from about 0 mol % to about 70 mol %, from about 0 mol % to about 65 mol %, from about 0 mol % to about 60 mol %, from about 0 mol % to about 55 mol %, from about 0 mol % to about 50 mol %, from about 0 mol % to about 45 mol %, from about 0 mol % to about 40 mol %, from about 0 mol % to about 35 mol %, from about ... mol% to about 85 mol%, about 5 mol% to about 80 mol%, about 5 mol% to about 75 mol%, about 5 mol% to about 70 mol%, about 5 mol% to about 65 mol%, about 5 mol% to about 60 mol%, about 5 mol% to about 55 mol%, about 5 mol% to about 50 mol%, about 5 mol% to about 45 mol%, about 5 mol% to about 40 mol%, about 5 mol% to about 35 mol%, about 10 mol% to about 85 mol%, about 10 mol% to about 80 mol%, about 10 mol% to about 75 mol%, about 10 mol% to about 70 mol%, about 10 mol% to about 65 mol%, about 10 mol% to about 60 mol%, about 10 mol% to about 55 mol%, about 10 mol% to about 5 0 mol%, about 10 mol% to about 45 mol%, about 10 mol% to about 40 mol%, about 10 mol% to about 35 mol%, about 15 mol% to about 85 mol%, about 15 mol% to about 80 mol%, about 15 mol% to about 75 mol%, about 15 mol% to about 70 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 60 mol%, about 15 mol% to about 55 mol%, about 15 mol% to about 50 mol%, about 15 mol% to about 45 mol%, about 15 mol% to about 40 mol%, about 15 mol% to about 35 mol%, about 20 mol% to about 85 mol%, about 20 mol% to about 80 mol%, about 20 mol% to about 75 mol%, about 20 ...5 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 6 % to about 70 mol%, about 20 mol% to about 65 mol%, about 20 mol% to about 60 mol%, about 20 mol% to about 55 mol%, about 20 mol% to about 50 mol%, about 25 mol% to about 85 mol%, about 25 mol% to about 80 mol%, about 25 mol% to about 75 mol%, about 25 mol% to about 70 mol%, about 25 mol% to about 65 mol%, about 25 mol% to about 60 mol%, about 25 mol% to about 55 mol%, about 25 mol% to about 50 mol%, about 30 mol% to about 85 mol%, about 30 mol% to about 80 mol%, about 30 mol% to about 75 mol%, about 30 mol% to about 70 mol%, about 30 mol% to about 65 mol%,about 30 mol% to about 60 mol%, about 30 mol% to about 55 mol%, about 30 mol% to about 50 mol%, about 35 mol% to about 85 mol%, about 35 mol% to about 80 mol%, about 35 mol% to about 75 mol%, about 35 mol% to about 70 mol%, about 35 mol% to about 65 mol%, about 35 mol% to about 60 mol%, about 35 mol% to about 55 mol%, about 40 mol% to about 85 mol%, about 40 mol% to about 80 mol%, about 40 mol% to about 75 mol%, about 40 mol% to about 70 mol%, about 40 mol% to about 65 mol%, about 40 mol% to about 60 mol%, about 4 5 mol% to about 85 mol%, about 45 mol% to about 80 mol%, about 45 mol% to about 75 mol%, about 45 mol% to about 70 mol%, about 45 mol% to about 65 mol%, about 50 mol% to about 85 mol%, about 50 mol% to about 80 mol%, about 50 mol% to about 75 mol%, about 50 mol% to about 70 mol%, about 55 mol% to about 85 mol%, about 55 mol% to about 80 mol%, about 55 mol% to about 75 mol%, about 60 mol% to about 85 mol%, about 60 mol% to about 80 mol%, about 65 mol% to about 85 mol%, or about 70 mol% to about 85 mol%.
[0163] In some embodiments, the proportion of each of the structural units derived from hydrophilic group-containing monomers and the structural units derived from hydrophobic group-containing monomers is, independently, less than 85 mol%, less than 80 mol%, less than 75 mol%, less than 70 mol%, less than 65 mol%, less than 60 mol%, less than 55 mol%, less than 50 mol%, less than 45 mol%, less than 40 mol%, less than 35 mol%, less than 30 mol%, less than 25 mol%, less than 20 mol%, less than 15 mol%, less than 10 mol%, or less than 5 mol%, based on the total number of moles of monomer units in the copolymer within the polymer. In some embodiments, the respective proportions of structural units derived from hydrophilic group-containing monomers and structural units derived from hydrophobic group-containing monomers are, independently, greater than 0 mol%, greater than 5 mol%, greater than 10 mol%, greater than 15 mol%, greater than 20 mol%, greater than 25 mol%, greater than 30 mol%, greater than 35 mol%, greater than 40 mol%, greater than 45 mol%, greater than 50 mol%, greater than 55 mol%, greater than 60 mol%, greater than 65 mol%, greater than 70 mol%, greater than 75 mol%, or greater than 80 mol%, based on the total number of moles of monomer units in the copolymer within the polymer.
[0164] In some embodiments, the hydrophilic group-containing monomer is selected from the group consisting of an acid group-containing monomer, an amide group-containing monomer, a hydroxyl group-containing monomer, or a combination thereof. The ratio of the proportion of structural units derived from the hydrophilic group-containing monomer to the proportion of structural units derived from the hydrophobic group-containing monomer in the copolymer is delicate and essential to the ability of the polymer to undergo a conformational change due to the addition of a precipitating agent to the first suspension. In some embodiments, the molar ratio of the structural units derived from the hydrophilic group-containing monomer to the structural units derived from the hydrophobic group-containing monomer in the copolymer is from about 0.1 to about 6.5, from about 0.1 to about 6.4, from about 0.1 to about 6.2, from about 0.1 to about 6, from about 0.1 to about 5.8, from about 0.1 to about 5.6, from about 0.1 to about 5.4, from about 0.1 to about 5.2, from about 0.1 to about 5, from about 0.1 to about 4.8, from about 0.1 to about 4.6, from about 0.1 to about 4.4, from about 0.1 to about 4.2, from about 0.1 to about 4, about 0.1 to about 3.8, about 0.1 to about 3.6, about 0.1 to about 3.4, about 0.1 to about 3.2, about 0.1 to about 3, about 0.1 to about 2.8, about 0.1 to about 2.6, about 0.1 to about 2.4, about 0.1 to about 2.2, about 0.1 to about 2, about 0.2 to about 6.5, about 0.2 to about 6.4, about 0.2 to about 6.2, about 0.2 to about 6, about 0.2 to about 5.8, about 0.2 to about 5.6, about 0.2 to about 5.4, about 0.2 to about 5.2, about 0.2 to about 5, about 0.2 to about 4.8, about 0.2 to about 4.6, about 0.2 to about 4.4, about 0.2 to about 4.2, about 0.2 to about 4, about 0.2 to about 3.8, about 0.2 to about 3.6, about 0.2 to about 3.4, about 0.2 to about 3.2, about 0.2 to about 3, about 0.2 to about 2.8, about 0.2 to about 2.6, about 0.2 to about 2.4, about 0.2 to about 2.2, about 0.2 to about 2, about 0.3 to about 6.5, about 0.3 to about 6.4, about 0.3 to about 6.2, about 0.3 to about 6, about 0.3 to about 5.8, about 0.3 to about 5.6, about 0.3 to about 5.4, about 0.3 to about 5.2, about 0.3 to about 5, about 0.3 to about 4.8, about 0.3 to about 4.6, about 0.3 to about 4.4, about 0.3 to about 4.2, about 0.3 to about 4, about 0.3 to about 3.8, about 0.3 to about 3.6, about 0.3 to about 3.4, about 0.3 to about 3.2, about 0.3 to about 3, about 0.3 to about 2.8, about 0.3 to about 2.6, about 0.3 to about 2.4, about 0.3 to about 2.2, about 0.3 to about 2, about 0.4 to about 6.5, about 0.4 to about 6.4, about 0.4 to about 6.2, about 0.4 to about 6, about 0.4 to about 5.8, about 0.4 to about 5.6, about 0.4 to about 5.4, about 0.4 to about 5.2, about 0.4 to about 5, about 0.4 to about 4.8, about 0.4 to about 4.6, about 0.4 to about 4.4, about 0.4 to about 4.2, about 0.4 to about 4, about 0.4 to about 3.8, about 0.4 to about 3.6, about 0.4 to about 3.4, about 0.4 to about 3.2, about 0.4 to about 3, about 0.4 to about 2.8, about 0.4 to about 2.6, about 0.4 to about 2.4, about 0.4 to about 2.2, about 0.4 to about 2, about 0.5 to about 6.5, about 0.5 to about 6.4, about 0.5 to about 6.2, about 0.5 to about 6, about 0.5 to about about 4.8, about 0.5 to about 4.6, about 0.5 to about 4.4, about 0.5 to about 4.2, about 0.5 to about 4, about 0.5 to about 3.8, about 0.5 to about 3.6, about 0.5 to about 3.4, about 0.5 to about 3.2, about 0.5 to about 3, about 0.5 to about 2.8, about 0.5 to about 2.6, about 0.5 to about 2.4, about 0.5 to about 2.2, about 0.5 to about 2, about 0.7 to about 6, about 0.7 to about 5.5, about 0.7 to about 5, about 0.7 to about 4.5, about 0.7 to about 4, about 0.7 to about 3.5, about 1 to about 6, about 1 to about 5.5, about 1 to about 5, about 1 to about 4.5, about 1 to about 4, or about 1 to about 3.5.
[0165] In some embodiments, the molar ratio of structural units derived from hydrophilic group-containing monomers to structural units derived from hydrophobic group-containing monomers in the copolymer is less than 6.5, less than 6.4, less than 6.3, less than 6.2, less than 6.1, less than 6, less than 5.9, less than 5.8, less than 5.7, less than 5.6, less than 5.5, less than 5.4, less than 5.3, less than 5.2, less than 5.1, less than 5, less than 4.9, less than 4.8, less than 4.7, less than 4.6, less than 4.5, less than 4.4, less than 4.3, less than 4.2, less than 4.1, less than 4, less than 3.9 less than 3.8, less than 3.7, less than 3.6, less than 3.5, less than 3.4, less than 3.3, less than 3.2, less than 3.1, less than 3, less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1, less than 0.9, less than 0.8, less than 0.7, less than 0.6, less than 0.5, less than 0.4, less than 0.3, or less than 0.2.In some embodiments, the molar ratio of structural units derived from hydrophilic group-containing monomers to structural units derived from hydrophobic group-containing monomers in the copolymer is greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, greater than 1.9, greater than 2, greater than 2.1, greater than 2.2, greater than 2.3, greater than 2.4, greater than 2.5, greater than 2.6, greater than 2.7, greater than 2.8 , greater than 2.9, greater than 3, greater than 3.1, greater than 3.2, greater than 3.3, greater than 3.4, greater than 3.5, greater than 3.6, greater than 3.7, greater than 3.8, greater than 3.9, greater than 4, greater than 4.1, greater than 4.2, greater than 4.3, greater than 4.4, greater than 4.5, greater than 4.6, greater than 4.7, greater than 4.8, greater than 4.9, greater than 5, greater than 5.1, greater than 5.2, greater than 5.3, greater than 5.4, greater than 5.5, greater than 5.6, greater than 5.7, greater than 5.8, greater than 5.9, greater than 6, greater than 6.1, greater than 6.2, greater than 6.3, or greater than 6.4.
[0166] In some embodiments, the molar ratio of the structural units derived from the acid group-containing monomer to the structural units derived from the hydrophobic group-containing monomer in the copolymer is from about 0.1 to about 3, from about 0.1 to about 2.9, from about 0.1 to about 2.8, from about 0.1 to about 2.7, from about 0.1 to about 2.6, from about 0.1 to about 2.5, from about 0.1 to about 2.4, from about 0.1 to about 2.3, from about 0.1 to about 2.2, from about 0.15 to about 3, from about 0.15 to about 2.9, from about 0.15 to about 2.8, from about 0.15 to about 2.7, from about 0.15 to about 2.6, from about 0.15 to about 2.5, from about 0.15 to about 2.4, about 0.15 to about 2.3, about 0.15 to about 2.2, about 0.2 to about 3, about 0.2 to about 2.9, about 0.2 to about 2.8, about 0.2 to about 2.7, about 0.2 to about 2.6, about 0.2 to about 2.5, about 0.2 to about 2.4, about 0.2 to about 2.3, about 0.2 to about 2.2, about 0.25 to about 3, about 0.25 to about 2.9, about 0.25 to about 2.8, about 0.25 to about 2.7, about 0.25 to about 2.6, about 0.25 to about 2.5, about 0.25 to about 2.4, about 0.25 to about 2.3, or about 0.25 to about 2.2.
[0167] In some embodiments, the molar ratio of structural units derived from acid group-containing monomers to structural units derived from hydrophobic group-containing monomers in the copolymer is less than 3, less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1, less than 0.9, less than 0.8, less than 0.7, less than 0.6, less than 0.5, less than 0.4, less than 0.3, or less than 0.2. In some embodiments, the molar ratio of structural units derived from acid group-containing monomers to structural units derived from hydrophobic group-containing monomers in the copolymer is greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, or greater than 1.9.
[0168] In some embodiments, the copolymer comprises a structural unit (a) derived from an acid group-containing monomer and a structural unit (b) derived from a nitrile group-containing monomer. In some embodiments, the copolymer comprises a structural unit (a) derived from an acid group-containing monomer, a structural unit (b) derived from a nitrile group-containing monomer, a structural unit (c) derived from an amide group-containing monomer, or a combination thereof. In some embodiments, the copolymer further comprises a structural unit (d) derived from a hydroxyl group-containing monomer, a structural unit (e) derived from an ester group-containing monomer, a structural unit (f) derived from an epoxy group-containing monomer, a structural unit (g) derived from a fluorine-containing monomer, or a combination thereof.
[0169] The structural unit (a) is derived from an acid group-containing monomer. Any monomer having at least one acid group can be used as the acid group-containing monomer without particular limitation.
[0170] In some embodiments, the acid group-containing monomer is a carboxylic acid group-containing monomer, hi some embodiments, the carboxylic acid group-containing monomer is acrylic acid, methacrylic acid, crotonic acid, 2-butylcrotonic acid, cinnamic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, tetraconic acid, or a combination thereof. In certain embodiments, the carboxylic acid group-containing monomer is 2-ethylacrylic acid, isocrotonic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, acrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, or combinations thereof.In some embodiments, the carboxylic acid group-containing monomer is methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, bromomaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, difluoromaleic acid, nonyl hydrogen maleate, decyl hydrogen maleate, dodecyl hydrogen maleate, octadecyl hydrogen maleate, fluoroalkyl hydrogen maleate, or a combination thereof. In some embodiments, the carboxylic acid group-containing monomer is maleic anhydride, methylmaleic anhydride, dimethylmaleic anhydride, acrylic anhydride, methacrylic anhydride, methacrolein, methacryloyl chloride, methacryloyl fluoride, methacryloyl bromide, or a combination thereof.
[0171] In some embodiments, the structural unit (a) derived from the carboxylic acid group-containing monomer comprises a carboxylate salt group. In some embodiments, the carboxylate salt group is a salt of a carboxylic acid group. In some embodiments, the structural unit (a) derived from the carboxylic acid group-containing monomer comprises an alkali metal carboxylate salt group. Examples of alkali metals that form alkali metal carboxylate salts include lithium, sodium, and potassium. In some embodiments, the structural unit (a) derived from the carboxylic acid group-containing monomer comprises an ammonium carboxylate salt group. In some embodiments, the structural unit (a) derived from the carboxylic acid group-containing monomer comprises a combination of a carboxylate salt group and a carboxylic acid group.
[0172] As the carboxylate group-containing monomer, any monomer having at least one carboxylate group can be used without any particular limitation.In some embodiments, the carboxylate group-containing monomer is an acrylate, a methacrylate, a crotonate, a 2-butyl crotonate, a cinnamate, a maleate, a maleic anhydride, a fumarate, an itaconate, an itaconic anhydride, a tetraconate, or a combination thereof. In certain embodiments, the carboxylate salt group-containing monomer is 2-ethylacrylate, isocrotonic acid salt, cis-2-pentenoate, trans-2-pentenoate, angelic acid salt, tiglic acid salt, 3,3-dimethylacrylate, 3-propylacrylate, trans-2-methyl-3-ethylacrylate, cis-2-methyl-3-ethylacrylate, 3-isopropylacrylate, trans-3-methyl-3-ethylacrylate, cis-3-methyl-3-ethylacrylate, 2-isopropylacrylate, trimethylacrylate, 2-methyl-3,3-diethylacrylate, 3-butylacrylate, 2-butylacrylate, 2-pentylacrylate, 2-methyl-2-hexenoate, trans-3-methyl-2-hexenoate, 3-methyl-3-propylacrylate, 2-ethyl-3-propylacrylate, acrylate, 2,3-diethylacrylate, 3,3-diethylacrylate, 3-methyl-3-hexylacrylate, 3-methyl-3-tert-butylacrylate, 2-methyl-3-pentylacrylate, 3-methyl-3-pentylacrylate, 4-methyl-2-hexenoate, 4-ethyl-2-hexenoate, 3-methyl-2-ethyl-2-hexenoate, 3-tert-butylacrylate, 2,3-dimethyl-3-ethylacrylate, 3,3-dimethyl-2-ethylacrylate, 3-methyl-3-isopropylacrylate, 2-methyl-3-isopropylacrylate, trans-2-octenoate, cis-2-octenoate, trans-2-decenoate, α-acetoxyacrylate, β-trans-aryloxyacrylate, α-chloro-β-E-methoxyacrylate, or combinations thereof.In some embodiments, the carboxylate group-containing monomer is a methylmaleate, a dimethylmaleate, a phenylmaleate, a bromomaleate, a chloromaleate, a dichloromaleate, a fluoromaleate, a difluoromaleate, or a combination thereof.
[0173] In some embodiments, the acid group-containing monomer is a sulfonic acid group-containing monomer. In some embodiments, the sulfonic acid group-containing monomer is vinyl sulfonic acid, methyl vinyl sulfonic acid, allyl vinyl sulfonic acid, allyl sulfonic acid, methallyl sulfonic acid, styrene sulfonic acid, 2-sulfoethyl methacrylic acid, 2-methylprop-2-ene-1-sulfonic acid, 2-acrylamido-2-methyl-1-propanesulfonic acid, 3-allyloxy-2-hydroxy-1-propanesulfonic acid, or a combination thereof.
[0174] In some embodiments, the structural unit (a) derived from the sulfonic acid group-containing monomer comprises a sulfonate group. In some embodiments, the sulfonate group is a salt of a sulfonic acid group. In some embodiments, the structural unit (a) derived from the sulfonic acid group-containing monomer comprises an alkali metal sulfonate group. Examples of alkali metals that form alkali metal sulfonates include lithium, sodium, and potassium. In some embodiments, the structural unit (a) derived from the sulfonic acid group-containing monomer comprises an ammonium sulfonate group. In some embodiments, the structural unit (a) derived from the sulfonic acid group-containing monomer comprises a combination of a sulfonate group and a sulfonic acid group.
[0175] As the sulfonate group-containing monomer, any monomer having at least one sulfonate group can be used without any particular limitation.In some embodiments, the sulfonate group-containing monomer is vinyl sulfonate, methyl vinyl sulfonate, allyl vinyl sulfonate, allyl sulfonate, methallyl sulfonate, styrene sulfonate, 2-sulfoethyl methacrylate, 2-methylprop-2-ene-1-sulfonate, 2-acrylamido-2-methyl-1-propanesulfonate, 3-allyloxy-2-hydroxy-1-propanesulfonate or a combination thereof.
[0176] In some embodiments, the acid group-containing monomer is a phosphonic acid group-containing monomer. In some embodiments, the phosphonic acid group-containing monomer is vinyl phosphonic acid, allyl phosphonic acid, vinylbenzyl phosphonic acid, acrylamido alkyl phosphonic acid, methacrylamide alkyl phosphonic acid, acrylamido alkyl diphosphonic acid, acryloyl phosphonic acid, 2-methacryloyloxyethyl phosphonic acid, bis(2-methacryloyloxyethyl) phosphonic acid, ethylene 2-methacryloyloxyethyl phosphonic acid, ethyl-methacryloyloxyethyl phosphonic acid, or a combination thereof.
[0177] In some embodiments, the structural unit (a) derived from the phosphonic acid group-containing monomer comprises a phosphonate group. In some embodiments, the phosphonate group is a salt of a phosphonic acid group. In some embodiments, the structural unit (a) derived from the phosphonic acid group-containing monomer comprises an alkali metal phosphonate group. Examples of alkali metals that form alkali metal phosphonates include lithium, sodium, and potassium. In some embodiments, the structural unit (a) derived from the phosphonic acid group-containing monomer comprises an ammonium phosphonate group. In some embodiments, the structural unit (a) derived from the phosphonic acid group-containing monomer comprises a combination of a phosphonate group and a phosphonic acid group.
[0178] As the phosphonate group-containing monomer, any monomer having at least one phosphonate group can be used without any particular limitation.In some embodiments, the phosphonate group-containing monomer is a salt of vinyl phosphonic acid, a salt of allyl phosphonic acid, a salt of vinylbenzyl phosphonic acid, a salt of an acrylamide alkyl salt of phosphonic acid, a salt of methacrylamide alkyl phosphonic acid, a salt of an acrylamide alkyl diphosphonic acid, a salt of acryloyl phosphonic acid, a salt of 2-methacryloyloxyethyl phosphonic acid, a salt of bis(2-methacryloyloxyethyl) phosphonic acid, a salt of ethylene 2-methacryloyloxyethyl phosphonic acid, a salt of ethyl-methacryloyloxyethyl phosphonic acid, or a combination thereof.
[0179] In some embodiments, structural unit (a) is derived from a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphonic acid group-containing monomer, or a combination thereof.
[0180] In some embodiments, the structural unit (a) derived from the acid group-containing monomer comprises an acid salt group. In some embodiments, the acid salt group is a salt of an acid group. As the acid group-containing monomer, any monomer having at least one acid salt group can be used without particular limitation. In some embodiments, the acid group-containing monomer is selected from the group consisting of a carboxylate group-containing monomer, a sulfonate group-containing monomer, a phosphonate group-containing monomer, or a combination thereof. In some embodiments, the structural unit (a) derived from the acid group-containing monomer comprises an alkali metal acid salt group. Examples of alkali metals that form alkali metal salts include lithium, sodium, and potassium. In some embodiments, the structural unit (a) derived from the acid group-containing monomer comprises an ammonium acid salt group. In some embodiments, the structural unit (a) derived from the acid group-containing monomer comprises a combination of an acid salt group and an acid group.
[0181] In some embodiments, the structural unit (a) derived from the acid group-containing monomer comprises an atom capable of forming a hydrogen bond. In some embodiments, the structural unit (a) derived from the acid group-containing monomer further comprises a charged species capable of inducing ion-dipole interactions and / or forming ionic bonds. For example, the acid group undergoes partial dissociation upon contact with water to generate acid-base containing charged species, resulting in ion-dipole interactions and / or the formation of ionic bonds.
[0182] In some embodiments, the proportion of structural units (a) derived from acid group-containing monomers in the polymer is from about 15 mol % to about 85 mol %, from about 15 mol % to about 84 mol %, from about 15 mol % to about 83 mol %, from about 15 mol % to about 82 mol %, from about 15 mol % to about 81 mol %, from about 15 mol % to about 80 mol %, from about 15 mol % to about 79 mol %, from about 15 mol % to about 78 mol %, from about 15 mol % to about 77 mol %, from about 15 mol % to about 76 mol %, from about 15 mol % to about 88 mol %, from about 15 mol % to about 89 ... mol%, about 15 mol% to about 75 mol%, about 15 mol% to about 74 mol%, about 15 mol% to about 73 mol%, about 15 mol% to about 72 mol%, about 15 mol% to about 71 mol%, about 15 mol% to about 70 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 60 mol%, about 15 mol% to about 55 mol%, about 15 mol% to about 50 mol%, about 16 mol% to about 85 mol%, about 17 mol% to about 85 mol%, about 18 mol% to about 85 mol%, about 19 mol% to about 85 mol%, about 20 mol% to about 85 mol%, about 21 mol% to about 85 mol%, about 22 mol% to about 85 mol%, about 25 mol% to about 85 mol%, about 30 mol% to about 85 mol%, about 35 mol% to about 85 mol%, about 40 mol% to about 85 mol%, about 45 mol% to about 85 mol%, about 50 mol% to about 85 mol%, about 55 mol% to about 85 mol%, about 16 mol% to about 80 mol%, about 16 mol% to about 75 mol%, about 16 mol% to about 70 mol%, about 16 mol% to about 65 mol%, about 16 mol% to about 60 mol%, about 18 mol% about 80 mol%, about 18 mol% to about 75 mol%, about 18 mol% to about 70 mol%, about 18 mol% to about 65 mol%, about 18 mol% to about 60 mol%, about 20 mol% to about 80 mol%, about 20 mol% to about 75 mol%, about 20 mol% to about 70 mol%, about 20 mol% to about 65 mol%, about 20 mol% to about 60 mol%, about 22 mol% to about 80 mol%, about 22 mol% to about 75 mol%, about 22 mol% to about 70 mol%, about 22 mol% to about 65 mol%, or about 22 mol% to about 60 mol%.
[0183] In some embodiments, the percentage of structural units (a) derived from acid group-containing monomers in the polymer is less than 85 mol%, less than 84 mol%, less than 82 mol%, less than 80 mol%, less than 78 mol%, less than 76 mol%, less than 74 mol%, less than 72 mol%, less than 70 mol%, less than 68 mol%, less than 66 mol%, less than 64 mol%, less than 62 mol%, less than 60 mol%, less than 58 mol%, less than 56 mol%, less than 54 mol%, less than 52 mol%, less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 44 mol%, less than 42 mol%, less than 40 mol%, less than 38 mol%, less than 36 mol%, less than 34 mol%, less than 32 mol%, less than 30 mol%, less than 28 mol%, less than 26 mol%, less than 24 mol%, less than 22 mol%, less than 20 mol%, or less than 18 mol% based on the total number of moles of monomer units in the copolymer. In some embodiments, the proportion of structural units (a) derived from acid group-containing monomers in the polymer is greater than 15 mol%, greater than 16 mol%, greater than 18 mol%, greater than 20 mol%, greater than 22 mol%, greater than 24 mol%, greater than 26 mol%, greater than 28 mol%, greater than 30 mol%, greater than 32 mol%, greater than 34 mol%, greater than 36 mol%, greater than 38 mol%, greater than 40 mol%, greater than 42 mol%, greater than 46 mol%, greater than 48 ... %, greater than 44 mol%, greater than 46 mol%, greater than 48 mol%, greater than 50 mol%, greater than 52 mol%, greater than 54 mol%, greater than 56 mol%, greater than 58 mol%, greater than 60 mol%, greater than 62 mol%, greater than 64 mol%, greater than 66 mol%, greater than 68 mol%, greater than 70 mol%, greater than 72 mol%, greater than 74 mol%, greater than 76 mol%, greater than 78 mol%, greater than 80 mol% or greater than 82 mol%.
[0184] pK a pK determines the strength of an acid. aA lower pK value indicates a stronger acid, i.e., an acid that dissociates more completely in an aqueous solvent such as water. It is desirable for the strength of the acid group-containing monomer that contributes to the formation of the polymer to be lower than the strength of the acid used as the precipitant, in order to facilitate deprotonation of the precipitant and protonation of the conjugate base of the acid group-containing monomer. For this reason, the pK value of the acid group-containing monomer is a The value is the pK of the acid used as the precipitant. a In some embodiments, the pK value of the acid group-containing monomer is preferably greater than 1. ais about 2.5 to about 7, about 2.5 to about 6.8, about 2.5 to about 6.6, about 2.5 to about 6.4, about 2.5 to about 6.2, about 2.5 to about 6, about 2.5 to about 5.8, about 2.5 to about 5.6, about 2.5 to about 5.4, about 2.5 to about 5.2, about 2.5 to about 5, about 2.5 to about 4.8, about 2.5 to about 4. 6, about 2.5 to about 4.4, about 2.5 to about 4.2, about 2.5 to about 4, about 2.6 to about 7, about 2.6 to about 6.8, about 2.6 to about 6.6, about 2.6 to about 6.4, about 2.6 to about 6.2, about 2.6 to about 6, about 2.6 to about 5.8, about 2.6 to about 5.6, about 2.6 to about 5.4, about 2.6 to about 5. 2, about 2.6 to about 5, about 2.6 to about 4.8, about 2.6 to about 4.6, about 2.6 to about 4.4, about 2.6 to about 4.2, about 2.6 to about 4, about 2.8 to about 7, about 2.8 to about 6.8, about 2.8 to about 6.6, about 2.8 to about 6.4, about 2.8 to about 6.2, about 2.8 to about 6, about 2.8 to about 5.8 , about 2.8 to about 5.6, about 2.8 to about 5.4, about 2.8 to about 5.2, about 2.8 to about 5, about 2.8 to about 4.8, about 2.8 to about 4.6, about 2.8 to about 4.4, about 2.8 to about 4.2, about 2.8 to about 4, about 3 to about 7, about 3 to about 6.8, about 3 to about 6.6, about 3 to about 6.4, about 3 to about 6.2 , about 3 to about 6, about 3 to about 5.8, about 3 to about 5.6, about 3 to about 5.4, about 3 to about 5.2, about 3 to about 5, about 3 to about 4.8, about 3 to about 4.6, about 3 to about 4.4, about 3 to about 4.2, about 3 to about 4, about 3.2 to about 7, about 3.2 to about 6.8, about 3.2 to about 6.6, about 3.2 to about 6.4, about 3 0.2 to about 6.2, about 3.2 to about 6, about 3.2 to about 5.8, about 3.2 to about 5.6, about 3.2 to about 5.4, about 3.2 to about 5.2, about 3.2 to about 5, about 3.4 to about 7, about 3.4 to about 6.8, about 3.4 to about 6.6, about 3.4 to about 6.4, about 3.4 to about 6.2, about 3.4 to about 6, about 3.4 ~ about 5.8, about 3.4 to about 5.6, about 3.4 to about 5.4, about 3.4 to about 5.2, about 3.4 to about 5, about 3.6 to about 7, about 3.6 to about 6.8, about 3.6 to about 6.6, about 3.6 to about 6.4, about 3.6 to about 6.2, about 3.6 to about 6, about 3.6 to about 5.8, about 3.6 to about 5.6, about 3. 6 to about 5.4, about 3.6 to about 5.2, about 3.6 to about 5, about 3.8 to about 7, about 3.8 to about 6.8, about 3.8 to about 6.6, about 3.8 to about 6.4, about 3.8 to about 6.2, about 3.8 to about 6, about 3.8 to about 5.8, about 3.8 to about 5.6, about 3.8 to about 5.4, about 3.8 to about 5.2, about 3.8 to about 5, about 4 to about 7, about 4 to about 6.8, about 4 to about 6.6, about 4 to about 6.4, about 4 to about 6.2, about 4 to about 6, about 4 to about 5.8, about 4 to about 5.6, about 4 to about 5.4, about 4 to about 5.2, or about 4 to about 5.
[0185] In some embodiments, the pK of the acid group-containing monomer a is less than 7, less than 6.8, less than 6.6, less than 6.4, less than 6.2, less than 6, less than 5.8, less than 5.6, less than 5.4, less than 5.2, less than 5, less than 4.8, less than 4.6, less than 4.4, less than 4.2, less than 4, less than 3.8, less than 3.6, less than 3.4, less than 3.2, less than 3, less than 2.8, or less than 2.6. a is greater than 2.5, greater than 2.6, greater than 2.8, greater than 3, greater than 3.2, greater than 3.4, greater than 3.6, greater than 3.8, greater than 4, greater than 4.2, greater than 4.4, greater than 4.6, greater than 4.8, greater than 5, greater than 5.2, greater than 5.4, greater than 5.6, greater than 5.8, greater than 6, greater than 6.2, greater than 6.4, greater than 6.6, or greater than 6.8.
[0186] The structural unit (b) is derived from a nitrile group-containing monomer. As the nitrile group-containing monomer, any monomer having at least one nitrile group can be used without any particular limitation. In some embodiments, the nitrile group-containing monomer comprises an α,β-ethylenically unsaturated nitrile monomer. In some embodiments, the nitrile group-containing monomer is acrylonitrile, α-halogenoacrylonitrile, α-alkylacrylonitrile, or a combination thereof. In some embodiments, the nitrile group-containing monomer is α-chloroacrylonitrile, α-bromoacrylonitrile, α-fluoroacrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-n-hexylacrylonitrile, α-methoxyacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile, α-acetoxyacrylonitrile, α-phenylacrylonitrile, α-tolylacrylonitrile, α-(methoxyphenyl)acrylonitrile, α-(chlorophenyl)acrylonitrile, α-(cyanophenyl)acrylonitrile, vinylidene cyanide, or a combination thereof.
[0187] In some embodiments, the proportion of structural units (b) derived from nitrile group-containing monomers in the polymer is from about 15 mol % to about 85 mol %, from about 15 mol % to about 84 mol %, from about 15 mol % to about 83 mol %, from about 15 mol % to about 82 mol %, from about 15 mol % to about 81 mol %, from about 15 mol % to about 80 mol %, from about 15 mol % to about 79 mol %, from about 15 mol % to about 78 mol %, from about 15 mol % to about 77 mol %, from about 15 mol % to about 79 mol %, from about 15 mol % to about 78 ... 6 mol%, about 15 mol% to about 75 mol%, about 15 mol% to about 74 mol%, about 15 mol% to about 73 mol%, about 15 mol% to about 72 mol%, about 15 mol% to about 71 mol%, about 15 mol% to about 70 mol%, about 15 mol% to about 65 mol%, about 15 mol% to about 60 mol%, about 15 mol% to about 55 mol%, about 15 mol% to about 50 mol%, about 16 mol% to about 85 mol%, about 17 mol% to about 85 mol%, about 18 mol% to about 85 mol%, about 19 mol% to about 85 mol%, about 20 mol% to about about 85 mol%, about 21 mol% to about 85 mol%, about 22 mol% to about 85 mol%, about 25 mol% to about 85 mol%, about 30 mol% to about 85 mol%, about 35 mol% to about 85 mol%, about 40 mol% to about 85 mol%, about 45 mol% to about 85 mol%, about 50 mol% to about 85 mol%, about 55 mol% to about 85 mol%, about 16 mol% to about 80 mol%, about 16 mol% to about 75 mol%, about 16 mol% to about 70 mol%, about 16 mol% to 65 mol%, about 16 mol% to about 60 mol%, about 18 mol% about 18 mol% to about 80 mol%, about 18 mol% to about 75 mol%, about 18 mol% to about 70 mol%, about 18 mol% to about 65 mol%, about 18 mol% to about 60 mol%, about 20 mol% to about 80 mol%, about 20 mol% to about 75 mol%, about 20 mol% to about 70 mol%, about 20 mol% to about 65 mol%, about 20 mol% to about 60 mol%, about 22 mol% to about 80 mol%, about 22 mol% to about 75 mol%, about 22 mol% to about 70 mol%, about 22 mol% to about 65 mol%, or about 22 mol% to about 60 mol%.
[0188] In some embodiments, the proportion of structural units (b) derived from nitrile group-containing monomers in the polymer is less than 85 mol%, less than 84 mol%, less than 82 mol%, less than 80 mol%, less than 78 mol%, less than 76 mol%, less than 74 mol%, less than 72 mol%, less than 70 mol%, less than 68 mol%, less than 66 mol%, less than 64 mol%, less than 62 mol%, less than 60 mol%, based on the total number of moles of monomer units in the copolymer. less than 58 mol%, less than 56 mol%, less than 54 mol%, less than 52 mol%, less than 50 mol%, less than 48 mol%, less than 46 mol%, less than 44 mol%, less than 42 mol%, less than 40 mol%, less than 38 mol%, less than 36 mol%, less than 34 mol%, less than 32 mol%, less than 30 mol%, less than 28 mol%, less than 26 mol%, less than 24 mol%, less than 22 mol%, less than 20 mol%, less than 18 mol%, or less than 16 mol%. In some embodiments, the proportion of structural units (b) derived from nitrile group-containing monomers in the polymer is greater than 15 mol%, greater than 16 mol%, greater than 18 mol%, greater than 20 mol%, greater than 22 mol%, greater than 24 mol%, greater than 26 mol%, greater than 28 mol%, greater than 30 mol%, greater than 32 mol%, greater than 34 mol%, greater than 36 mol%, greater than 38 mol%, greater than 40 mol%, greater than 42 mol%, greater than 46 mol%, greater than 48 ... %, greater than 44 mol%, greater than 46 mol%, greater than 48 mol%, greater than 50 mol%, greater than 52 mol%, greater than 54 mol%, greater than 56 mol%, greater than 58 mol%, greater than 60 mol%, greater than 62 mol%, greater than 64 mol%, greater than 66 mol%, greater than 68 mol%, greater than 70 mol%, greater than 72 mol%, greater than 74 mol%, greater than 76 mol%, greater than 78 mol%, greater than 80 mol%, or greater than 82 mol%.
[0189] The structural unit (c) is derived from an amide group-containing monomer. As the amide group-containing monomer, any monomer having at least one amide group can be used without particular limitation. In some embodiments, the amide group-containing monomer is acrylamide, methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, Nn-propyl methacrylamide, N-isopropyl methacrylamide, isopropyl acrylamide, Nn-butyl methacrylamide, N-isobutyl methacrylamide, N,N-dimethyl acrylamide, N,N-dimethyl methacrylamide, N,N-diethyl acrylamide, N,N-diethyl methacrylamide, N-methylol methacrylamide, N-(methoxymethyl) methacrylamide, N-(ethoxymethyl) methacrylamide, N-(propoxymethyl) methacrylamide, N-(butoxymethyl) methacrylamide. 、N , N-dimethylaminopropyl methacrylamide, N,N-dimethylaminoethyl methacrylamide, N,N-dimethylol methacrylamide, diacetone methacrylamide, diacetone acrylamide, methacryloylmorpholine, N-hydroxyl methacrylamide, N-methoxymethylacrylamide, N-methoxymethyl methacrylamide, N,N'-methylene-bis-acrylamide (MBA), N-hydroxymethylacrylamide or combinations thereof.
[0190] In some embodiments, the proportion of structural units (c) derived from an amide group-containing monomer in the polymer is from about 0 mol % to about 35 mol %, from about 1 mol % to about 35 mol %, from about 2 mol % to about 35 mol %, from about 3 mol % to about 35 mol %, from about 4 mol % to about 35 mol %, from about 5 mol % to about 35 mol %, from about 6 mol % to about 35 mol %, from about 7 mol % to about 35 mol %, from about 8 mol % to about 35 mol %, from about 9 mol % to about 35 mol %, from about 10 mol % to about 35 mol %, from about 11 mol % to about 35 mol %, from about 12 mol % to about 35 mol %, from about 13 mol % to about 35 mol %, from about 14 mol % to about 35 mol %, from about 15 mol % to about 35 mol %, from about 16 mol % to about 35 mol %, from about 17 mol % to about 35 mol %, %, about 18 mol% to about 35 mol%, about 19 mol% to about 35 mol%, about 20 mol% to about 35 mol%, about 20 mol% to about 34 mol%, about 20 mol% to about 33 mol%, about 20 mol% to about 32 mol%, about 20 mol% to about 31 mol%, about 20 mol% to about 30 mol%, about 0 mol% to about 34 mol%, about 0 mol% to about 33 mol%, about 0 mol% to about 32 ... % to about 31 mol%, about 0 mol% to about 30 mol%, about 1 mol% to about 29 mol%, about 1 mol% to about 28 mol%, about 1 mol% to about 27 mol%, about 1 mol% to about 26 mol%, about 1 mol% to about 25 mol%, about 1 mol% to about 24 mol%, about 1 mol% to about 23 mol%, about 1 mol% to about 22 mol%, about 1 mol% to about 21 mol%, or about 1 mol% to about 20 mol%.
[0191] In some embodiments, the proportion of structural units (c) derived from amide group-containing monomers in the polymer is less than 35 mol%, less than 34 mol%, less than 33 mol%, less than 32 mol%, less than 31 mol%, less than 30 mol%, less than 29 mol%, less than 28 mol%, less than 27 mol%, less than 26 mol%, less than 25 mol%, less than 24 mol%, less than 23 mol%, less than 22 mol%, less than 21 mol%, less than 20 mol%, less than 19 mol%, less than 18 mol%, less than 17 mol%, less than 16 mol%, less than 15 mol%, less than 14 mol%, less than 13 mol%, less than 12 mol%, less than 11 mol%, or less than 10 mol%, based on the total number of moles of monomer units in the copolymer. In some embodiments, the percentage of structural units (c) derived from amide group-containing monomers is greater than 0 mol%, greater than 1 mol%, greater than 2 mol%, greater than 3 mol%, greater than 4 mol%, greater than 5 mol%, greater than 6 mol%, greater than 7 mol%, greater than 8 mol%, greater than 9 mol%, greater than 10 mol%, greater than 11 mol%, greater than 12 mol%, greater than 13 mol%, greater than 14 mol%, greater than 15 mol%, greater than 16 mol%, greater than 17 mol%, greater than 18 mol%, greater than 19 mol%, greater than 20 mol%, greater than 21 mol%, greater than 22 mol%, greater than 23 mol%, greater than 24 mol%, or greater than 25 mol%, based on the total number of moles of copolymer monomer units in the polymer.
[0192] The structural unit (d) is derived from a hydroxyl group-containing monomer. As the hydroxyl group-containing monomer, any monomer having at least one hydroxyl group can be used without particular limitation. In some embodiments, the hydroxyl group-containing monomer is a C1-C hydroxyl group-containing monomer. 20 Alkyl group or C5-C 20In some embodiments, the hydroxyl group-containing monomer is 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 2-hydroxybutyl methacrylate, 3-hydroxypropyl acrylate, 3-hydroxypropyl methacrylate, 4-hydroxybutyl methacrylate, 5-hydroxypentyl acrylate, 6-hydroxyhexyl methacrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, 3-chloro-2-hydroxypropyl methacrylate, diethylene glycol mono(meth)acrylate, allyl alcohol or combinations thereof.
[0193] The structural unit (e) is derived from an ester group-containing monomer. As the ester group-containing monomer, any monomer having at least one ester group can be used without particular limitation. In some embodiments, the ester group-containing monomer is a C1 to C 20 Alkyl acrylate, C1-C 20The alkyl (meth)acrylate may be an alkyl (meth)acrylate, a cycloalkyl acrylate, or a combination thereof. In some embodiments, the ester group-containing monomer is methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, tert-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, 3,3,5-trimethylhexyl acrylate, 2-ethylhexyl acrylate, nonyl acrylate, decyl acrylate, lauryl acrylate, n-tetradecyl acrylate, octadecyl acrylate, cyclohexyl acrylate, phenyl acrylate, methoxymethyl acrylate, methoxyethyl acrylate, ethoxymethyl acrylate, ethoxyethyl acrylate, perfluorooctyl acrylate, stearyl acrylate, or a combination thereof. In some embodiments, the ester group-containing monomer is cyclohexyl acrylate, cyclohexyl methacrylate, isobornyl acrylate, isobornyl methacrylate, 3,3,5-trimethylcyclohexyl acrylate, or a combination thereof. In some embodiments, the ester group-containing monomer is methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, isopentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, 2-ethylhexyl methacrylate, nonyl methacrylate, decyl methacrylate, lauryl methacrylate, n-tetradecyl methacrylate, stearyl methacrylate, 2,2,2-trifluoroethyl methacrylate, phenyl methacrylate, benzyl methacrylate, or a combination thereof.
[0194] The structural unit (f) is derived from an epoxy group-containing monomer. As the epoxy group-containing monomer, any monomer having at least one epoxy group can be used without any particular limitation. In some embodiments, the epoxy group-containing monomer is vinyl glycidyl ether, allyl glycidyl ether, allyl 2,3-epoxypropyl ether, butenyl glycidyl ether, butadiene monoepoxide, chloroprene monoepoxide, 3,4-epoxy-1-butene, 4,5-epoxy-2-pentene, 3,4-epoxy-1-vinylcyclohexane, 1,2-epoxy-4-vinylcyclohexane, 3,4-epoxycyclohexylethylene, epoxy-4-vinylcyclohexene, 1,2-epoxy-5,9-cyclododecadiene or a combination thereof.
[0195] In some embodiments, the epoxy group-containing monomer includes 3,4-epoxy-1-butene, 1,2-epoxy-5-hexene, 1,2-epoxy-9-decene, glycidyl acrylate, glycidyl methacrylate, glycidyl crotonate, glycidyl 2,4-dimethylpentenoate, glycidyl 4-hexenoate, glycidyl 4-heptenoate, glycidyl 5-methyl-4-heptenoate, glycidyl sorbate, glycidyl linoleate, glycidyl oleate, glycidyl 3-butenoate, glycidyl 3-pentenoate, glycidyl-4-methyl-3-pentenoate, or combinations thereof.
[0196] The structural unit (g) is derived from a fluorine-containing monomer. As the fluorine-containing monomer, any monomer having at least one fluorine atom can be used without particular limitation. In some embodiments, the fluorine-containing monomer is a C1-C fluorine-containing monomer having at least one fluorine atom. 20Alkyl group-containing acrylate, methacrylate or combination thereof. In some embodiments, the fluorine-containing monomer is perfluoroalkyl acrylate such as perfluorododecyl acrylate, perfluoro n-octyl acrylate, perfluoro n-butyl acrylate, perfluorohexyl ethyl acrylate and perfluorooctyl ethyl acrylate; perfluoroalkyl methacrylate such as perfluorododecyl methacrylate, perfluoro n-octyl methacrylate, perfluoro n-butyl methacrylate, perfluorohexyl ethyl methacrylate and perfluorooctyl ethyl methacrylate; perfluorooxyalkyl acrylate such as perfluorododecyloxyethyl acrylate and perfluorodecyloxyethyl acrylate; perfluorooxyalkyl methacrylate such as perfluorododecyloxyethyl methacrylate and perfluorodecyloxyethyl methacrylate and combination thereof. In some embodiments, the fluorine-containing monomer is at least one C1-C 20 A carboxylate comprising an alkyl group and at least one fluorine atom; wherein the carboxylate is selected from the group consisting of crotonate, malate, fumarate, itaconate or a combination thereof. In some embodiments, the fluorine-containing monomer is vinyl fluoride, trifluoroethylene, trifluorochloroethylene, fluoroalkyl vinyl ether, perfluoroalkyl vinyl ether, hexafluoropropylene, 2,3,3,3-tetrafluoropropene, vinylidene fluoride, tetrafluoroethylene, 2-fluoroacrylate and a combination thereof.
[0197] In some embodiments, the proportion of each of the structural units (d) derived from a hydroxyl group-containing monomer, the structural units (e) derived from an ester group-containing monomer, the structural units (f) derived from an epoxy group-containing monomer, and the structural units (g) derived from a fluorine-containing monomer is, independently, from about 0 mol % to about 50 mol %, from about 1 mol % to about 50 mol %, from about 2 mol % to about 50 mol %, from about 3 mol % to about 50 mol %, from about 4 mol % to about 50 mol %, from about 5 mol % to about 50 mol %, from about 6 mol % to about 50 mol %, based on the total number of moles of monomer units in the copolymer in the polymer. 50 mol%, about 7 mol% to about 50 mol%, about 8 mol% to about 50 mol%, about 9 mol% to about 50 mol%, about 10 mol% to about 50 mol%, about 11 mol% to about 50 mol%, about 12 mol% to about 50 mol%, about 13 mol% to about 50 mol%, about 14 mol% to about 50 mol%, about 15 mol% to about 50 mol%, about 16 mol% to about 50 mol%, about 17 mol% to about 50 mol%, about 18 mol% to about 50 mol%, about 19 mol% to about 50 mol%, about 20 mol% to about 50 mol%, about 20 mol% to about 49 mol%, about 20 mol% to about 48 mol%, about 20 mol% to about 47 mol%, about 20 mol% to about 50 ... about 46 mol%, about 20 mol% to about 45 mol%, about 20 mol% to about 44 mol%, about 20 mol% to about 43 mol%, about 20 mol% to about 42 mol%, about 20 mol% to about 41 mol%, about 20 mol% to about 40 mol%, about 0 mol% to about 45 mol%, about 0 mol% to about 44 mol%, about 0 mol% to about 43 mol%, about 0 mol% to about 42 mol%, about 0 mol% to about 41 mol%, about 0 mol% to about 40 mol%, about 0 mol% to about 39 mol%, about 0 mol% to about 38 mol%, about 0 mol% to about 37 mol%, about 0 mol% to about 36 mol%, about 0 mol% to about 35 mol%, about 0 mol% to about 34 mol%, about 0 mol% to about 33 mol%, about 0 mol% to about 32 mol%, about 0 mol% to about 31 mol%, about 0 mol% to about 30 mol%, about 2 mol% to about 50 mol%, about 2 mol% to about 45 mol%, about 2 mol% to about 40 mol%, about 2 mol% to about 35 mol%, about 2 mol% to about 30 mol%, about 2 mol% to about 25 mol%, about 5 mol% to about 50 mol%, about 5 mol% to about 45 mol%, about 5 mol% to about 40 mol%, about 5 mol% to about 35 mol%, about 5 mol% to about 30 mol%, about 5 mol% to about 25 mol%, about 10 mol% to about 50 mol%, about 10 mol% to about 45 mol%, about 10 mol% to about 40 mol%,About 10 mol% to about 35 mol% or about 10 mol% to about 30 mol%.
[0198] In some embodiments, the proportion of each of the structural units (d) derived from a hydroxyl group-containing monomer, the structural units (e) derived from an ester group-containing monomer, the structural units (f) derived from an epoxy group-containing monomer, and the structural units (g) derived from a fluorine-containing monomer, based on the total number of moles of monomer units in the copolymer in the polymer, is independently less than 50 mol%, less than 49 mol%, less than 48 mol%, less than 47 mol%, less than 46 mol%, less than 45 mol%, less than 44 mol%, less than 43 mol%, less than 42 mol%, less than 41 mol%, less than 40 mol%, less than 39 mol%, less than 38 mol%, or less than 50 mol%, based on the total number of moles of monomer units in the copolymer in the polymer. %, less than 37 mol%, less than 36 mol%, less than 35 mol%, less than 34 mol%, less than 33 mol%, less than 32 mol%, less than 31 mol%, less than 30 mol%, less than 29 mol%, less than 28 mol%, less than 27 mol%, less than 26 mol%, less than 25 mol%, less than 24 mol%, less than 23 mol%, less than 22 mol%, less than 21 mol%, less than 20 mol%, less than 19 mol%, less than 18 mol%, less than 17 mol%, less than 16 mol%, less than 15 mol%, less than 14 mol%, less than 13 mol%, less than 12 mol%, less than 11 mol%, less than 10 mol%, less than 8 mol%, less than 6 mol%, less than 4 mol%, or less than 2 mol%.
[0199] In some embodiments, the proportion of each of the structural units (d) derived from a hydroxyl group-containing monomer, the structural units (e) derived from an ester group-containing monomer, the structural units (f) derived from an epoxy group-containing monomer, and the structural units (g) derived from a fluorine-containing monomer, independently, based on the total number of moles of monomer units in the copolymer in the polymer, is greater than 0 mol%, greater than 1 mol%, greater than 2 mol%, greater than 3 mol%, greater than 4 mol%, greater than 5 mol%, greater than 6 mol%, greater than 7 mol%, greater than 8 mol%, greater than 9 mol%, greater than 10 mol%, greater than 11 mol%, greater than 12 mol%, greater than 13 mol%, greater than 14 mol%, greater than 15 mol%, greater than 16 mol%, greater than 17 mol%, greater than 18 mol%, greater than 19 mol%, greater than 20 mol%, greater than 21 mol%, greater than 22 mol%, greater than 23 mol%, greater than 24 mol%, greater than 25 mol%, greater than 26 mol%, greater than 27 mol%, greater than 28 mol%, greater than 29 mol%, greater than 30 mol%, greater than 31 mol%, greater than 32 mol%, greater than 33 mol%, greater than 34 mol%, greater than 35 mol%, greater than 36 mol%, greater than 37 mol%, greater than 38 mol%, greater than 39 mol%, greater than 40 mol%, greater than 41 mol%, greater than 42 mol%, greater than 43 mol%, greater than 44 mol%, greater than 45 mol%, greater than 46 mol%, greater than 47 mol%, greater than 48 mol%, greater than 49 mol%, greater than 50 mol%, greater than 51 mol%, greater than 52 mol%, greater than greater than 18 mol%, greater than 19 mol%, greater than 20 mol%, greater than 21 mol%, greater than 22 mol%, greater than 23 mol%, greater than 24 mol%, greater than 25 mol%, greater than 26 mol%, greater than 27 mol%, greater than 28 mol%, greater than 29 mol%, greater than 30 mol%, greater than 31 mol%, greater than 32 mol%, greater than 33 mol%, greater than 34 mol%, greater than 35 mol%, greater than 36 mol%, greater than 37 mol%, greater than 38 mol%, greater than 39 mol%, greater than 40 mol%, greater than 41 mol%, greater than 42 mol%, greater than 43 mol%, greater than 44 mol%, greater than 45 mol%, greater than 46 mol%, greater than 47 mol%, or greater than 48 mol%.
[0200] In other embodiments, the copolymer may further comprise structural units derived from an olefin. As the olefin, any hydrocarbon having at least one carbon-carbon double bond can be used without particular limitation. In some embodiments, the olefin is a C2-C 20 Aliphatic compounds, C8~C 20 Aromatic or cyclic compounds containing vinyl unsaturation, C4-C 40In some embodiments, the olefin is styrene, ethylene, propylene, isobutylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, cyclobutene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4,6-dimethyl-1-heptene, 4-vinylcyclohexene, vinylcyclohexane, norbornene, norbornadiene, ethylidenenorbornene, cyclopentene, cyclohexene, dicyclopentadiene, cyclooctene, or a combination thereof. In some embodiments, the copolymer does not include structural units derived from an olefin. In some embodiments, the copolymer does not comprise styrene, ethylene, propylene, isobutylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, 1-eicosene, 3-methyl-1-butene, cyclobutene, 3-methyl-1-pentene, 4-methyl-1-pentene, 4,6-dimethyl-1-heptene, 4-vinylcyclohexene, vinylcyclohexane, norbornene, norbornadiene, ethylidenenorbornene, cyclopentene, cyclohexene, dicyclopentadiene, or cyclooctene.
[0201] The conjugated diene group-containing monomer is configured as an olefin. In some embodiments, the conjugated diene group-containing monomer is configured as a C4-C 40 Dienes, aliphatic conjugated diene monomers such as 1,3-butadiene, 1,3-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,7-octadiene, 1,9-decadiene, isoprene, myrcene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene, substituted side chain conjugated hexadiene, or combinations thereof. In some embodiments, the copolymers are C4-C 40Does not contain aliphatic conjugated diene monomers such as diene, 1,3-butadiene, 1,3-pentadiene, 1,4-hexadiene, 1,5-hexadiene, 1,7-octadiene, 1,9-decadiene, isoprene, myrcene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted linear conjugated pentadiene or substituted side chain conjugated hexadiene.
[0202] In other embodiments, the copolymer may further include structural units derived from an aromatic vinyl group-containing monomer. In some embodiments, the aromatic vinyl group-containing monomer is styrene, α-methylstyrene, vinyltoluene, divinylbenzene, or a combination thereof. In some embodiments, the copolymer does not include structural units derived from an aromatic vinyl group-containing monomer. In some embodiments, the copolymer does not include styrene, α-methylstyrene, vinyltoluene, or divinylbenzene.
[0203] In some embodiments, the weight average molecular weight of the polymer is from about 50,000 g / mol to about 200,000 g / mol, from about 55,000 g / mol to about 200,000 g / mol, from about 60,000 g / mol to about 200,000 g / mol, from about 65,000 g / mol to about 200,000 g / mol, from about 70,000 g / mol to about 200,000 g / mol, from about 75,000 g / mol to about 200,000 g / mol, from about 80,000 g / mol to about 200,000 g / mol, from about 85,000 g / mol to about 200,000 g / mol, from about 90,000 g / mol to about 200,000 g / mol, or from about 90,000 g / mol to about 200,000 g / mol. 00 g / mol to about 190,000 g / mol, about 90,000 g / mol to about 180,000 g / mol, about 90,000 g / mol to about 170,000 g / mol, about 90,000 g / mol to about 160,000 g / mol, about 95,000 g / mol to about 160,000 g / mol, about 100,000 g / mol to about 160,000 g / mol, about 100,000 g / mol to about 155,000 g / mol, about 100,000 g / mol to about 15,000 g / mol, about 100,000 g / mol to about 145,000 g / mol, or about 100,000 g / mol to about 140,000 g / mol.
[0204] In some embodiments, the weight average molecular weight of the polymer is less than 200,000 g / mol, less than 195,000 g / mol, less than 190,000 g / mol, less than 185,000 g / mol, less than 180,000 g / mol, less than 175,000 g / mol, less than 170,000 g / mol, less than 165,000 g / mol, less than 160,000 g / mol, less than 155,000 g / mol, less than 150,000 g / mol, less than 145,000 g / mol, less than 140,000 g / mol, less than 135,000 g / mol, less than 130,000 g / mol, less than 125,000 g / mol, less than 120,000 g / mol, less than 115,000 g / mol, less than 110,000 g / mol, less than 105,000 g / mol, less than 100,000 g / mol, less than 95,000 g / mol, less than 90,000 g / mol, less than 85,000 g / mol, less than 80,000 g / mol, less than 75,000 g / mol, less than 70,000 g / mol, less than 65,000 g / mol, or less than 60,000 g / mol.In some embodiments, the weight average molecular weight of the polymer is greater than 50,000 g / mol, greater than 55,000 g / mol, greater than 60,000 g / mol, greater than 65,000 g / mol, greater than 70,000 g / mol, greater than 75,000 g / mol, greater than 80,000 g / mol, greater than 85,000 g / mol, greater than 90,000 g / mol, greater than 95,000 g / mol, greater than 100,000 g / mol, greater than 105,000 g / mol, greater than 110,000 g / mol, greater than 115,000 g / mol, greater than 120,000 g / mol, or greater than 130,000 g / mol. greater than 125,000 g / mol, greater than 130,000 g / mol, greater than 135,000 g / mol, greater than 140,000 g / mol, greater than 145,000 g / mol, greater than 150,000 g / mol, greater than 155,000 g / mol, greater than 160,000 g / mol, greater than 165,000 g / mol, greater than 170,000 g / mol, greater than 175,000 g / mol, greater than 180,000 g / mol, greater than 185,000 g / mol, greater than 190,000 g / mol, or greater than 195,000 g / mol.
[0205] In some embodiments, the number average molecular weight of the polymer is from about 10,000 g / mol to about 100,000 g / mol, from about 15,000 g / mol to about 100,000 g / mol, from about 20,000 g / mol to about 100,000 g / mol, from about 25,000 g / mol to about 100,000 g / mol, from about 30,000 g / mol to about 100,000 g / mol, from about 35,000 g / mol to about 100,000 g / mol, from about 40,000 g / mol to about 100,000 g / mol, from about 45,000 g / mol to about 100,000 g / mol, about 50,000 g / mol to about 100,000 g / mol, about 50,000 g / mol to about 95,000 g / mol, about 50,000 g / mol to about 90,000 g / mol, about 50,000 g / mol to about 85,000 g / mol, about 50,000 g / mol to about 80,000 g / mol, about 55,000 g / mol to about 80,000 g / mol, about 60,000 g / mol to about 80,000 g / mol, about 65,000 g / mol to about 75,000 g / mol, or about 60,000 g / mol to about 90,000 g / mol.
[0206] In some embodiments, the number average molecular weight of the polymer is less than 100,000 g / mol, less than 95,000 g / mol, less than 90,000 g / mol, less than 85,000 g / mol, less than 80,000 g / mol, less than 75,000 g / mol, less than 70,000 g / mol, less than 65,000 g / mol, less than 60,000 g / mol, less than 55,000 g / mol, less than 50,000 g / mol, less than 45,000 g / mol, less than 40,000 g / mol, less than 35,000 g / mol, less than 30,000 g / mol, less than 25,000 g / mol, less than 20,000 g / mol, or less than 15,000 g / mol. In some embodiments, the number average molecular weight of the polymer is greater than 10,000 g / mol, greater than 15,000 g / mol, greater than 20,000 g / mol, greater than 25,000 g / mol, greater than 30,000 g / mol, greater than 35,000 g / mol, greater than 40,000 g / mol, greater than 45,000 g / mol, greater than 50,000 g / mol, greater than 55,000 g / mol, greater than 60,000 g / mol, greater than 65,000 g / mol, greater than 70,000 g / mol, greater than 75,000 g / mol, greater than 80,000 g / mol, greater than 85,000 g / mol, greater than 90,000 g / mol, or greater than 95,000 g / mol.
[0207] In some embodiments, the polydispersity index (PDI) of the polymer is from about 1 to about 5, from about 1 to about 4.8, from about 1 to about 4.6, from about 1 to about 4.4, from about 1 to about 4.2, from about 1 to about 4, from about 1 to about 3.8, from about 1 to about 3.6, from about 1 to about 3.4, from about 1 to about 3.2, from about 1 to about 3, from about 1.1 to about 3, from about 1.2 to about 3, from about 1.3 to about 3, from about 1.4 to about 3, from about 1.5 to about 3, from about 1.6 to about 3, from about 1.6 to about 2.8, from about 1.6 to about 2.6, from about 1.8 to about 2.6, or from about 1.8 to about 2.8.
[0208] In some embodiments, the polydispersity index of the polymer is less than 5, less than 4.8, less than 4.6, less than 4.4, less than 4.2, less than 4, less than 3.8, less than 3.6, less than 3.4, less than 3.2, less than 3, less than 2.8, less than 2.6, less than 2.4, less than 2.2, less than 2, less than 1.8, less than 1.6, less than 1.4, or less than 1.2. In some embodiments, the polydispersity index of the polymer is greater than 1, greater than 1.2, greater than 1.4, greater than 1.6, greater than 1.8, greater than 2, greater than 2.2, greater than 2.4, greater than 2.6, greater than 2.8, greater than 3, greater than 3.2, greater than 3.4, greater than 3.6, greater than 3.8, greater than 4, greater than 4.2, greater than 4.4, greater than 4.6, or greater than 4.8.
[0209] In some embodiments, the aqueous solvent is a solution containing water as a main component and, in addition to water, a volatile solvent such as an alcohol, a lower aliphatic ketone, or a lower alkyl acetate as a trace component. In some embodiments, the proportion of water in the aqueous solvent is about 51% by weight to about 100% by weight, about 51% by weight to about 95% by weight, about 51% by weight to about 90% by weight, about 51% by weight to about 85% by weight, about 51% by weight to about 80% by weight, about 51% by weight to about 75% by weight, about 51% by weight to about 70% by weight, about 55% by weight to about 100% by weight, about 55% by weight to about 95% by weight, about 55% by weight to about 90% by weight, about 55% by weight to about 85% by weight, about 55% by weight to about 80% by weight, about 60% by weight to about 10 ... % to about 95% by weight, about 60% to about 90% by weight, about 60% to about 85% by weight, about 60% to about 80% by weight, about 65% to about 100% by weight, about 65% to about 95% by weight, about 65% to about 90% by weight, about 65% to about 85% by weight, about 70% to about 100% by weight, about 70% to about 95% by weight, about 70% to about 90% by weight, about 70% to about 85% by weight, about 75% to about 100% by weight, about 75% to about 95% by weight, or about 80% to about 100% by weight.
[0210] In some embodiments, the percentage of water in the aqueous solvent is greater than 50% by weight, greater than 55% by weight, greater than 60% by weight, greater than 65% by weight, greater than 70% by weight, greater than 75% by weight, greater than 80% by weight, greater than 85% by weight, greater than 90% by weight, or greater than 95% by weight. In some embodiments, the percentage of water in the aqueous solvent is less than 55% by weight, less than 60% by weight, less than 65% by weight, less than 70% by weight, less than 75% by weight, less than 80% by weight, less than 85% by weight, less than 90% by weight, or less than 95% by weight. In some embodiments, the aqueous solvent consists only of water, i.e., the percentage of water in the aqueous solvent is 100% by weight.
[0211] Some non-limiting examples of water include tap water, bottled water, purified water, pure water, distilled water, deionized water, DO, or combinations thereof. In some embodiments, the aqueous solvent is deionized water. Water forms a solvation shell around the various charged, partially charged, or polar species present in the polymer, thereby facilitating dissolution of the polymer in the first suspension.
[0212] As a minor component of the aqueous solvent (i.e., a solvent other than water), any water-miscible or volatile solvent can be used. Some non-limiting examples of water-miscible or volatile solvents include alcohols, lower aliphatic ketones, lower alkyl acetates, and combinations thereof. The addition of alcohols can improve the solubility of the polymer and lower the freezing point of water. Some non-limiting examples of alcohols include C1-C4 alcohols, such as methanol, ethanol, isopropanol, n-propanol, tert-butanol, n-butanol, and combinations thereof. Some non-limiting examples of lower aliphatic ketones include acetone, dimethyl ketone, methyl ethyl ketone (MEK), and combinations thereof. Some non-limiting examples of lower alkyl acetates include ethyl acetate (EA), isopropyl acetate, propyl acetate, butyl acetate (BA), and combinations thereof. In some embodiments, the aqueous solvent does not include alcohols, lower aliphatic ketones, lower alkyl acetates, or combinations thereof.
[0213] The methods of the present invention are carried out to achieve precipitation of the polymer by (1) disrupting and / or breaking the intermolecular attractions (e.g., hydrogen bonds and / or ion-dipole interactions) between the polymer and the aqueous solvent using a precipitating agent, and (2) inducing a resulting coil-to-globule conformational transition of the polymer.
[0214] In some embodiments, a precipitating agent is added to the first suspension to form a second suspension.
[0215] In some embodiments, the precipitating agent is an acid, hi some embodiments, the precipitating agent is a strong acid, a weak acid, or a combination thereof.
[0216] In some embodiments, the precipitating agent is a strong acid. A strong acid is one that completely or nearly completely dissociates in water producing hydrogen ions as described in Equation 1. In some embodiments, the strong acid is an inorganic acid. In some embodiments, the inorganic acid is selected from the group consisting of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, hydrobromic acid, hydroiodic acid, chloric acid, bromic acid, iodic acid, dithionous acid, dithionous acid, sulfamic acid, trithionic acid, tetrathionic acid, or combinations thereof.
[0217] In some embodiments, the strong acid is selected from the group consisting of methanesulfonic acid, p-toluenesulfonic acid, benzenesulfonic acid, trichloroacetic acid, trifluoroacetic acid, oxalic acid, propiolic acid, mesoxalic acid, mellitic acid, or combinations thereof.
[0218] It is highly recommended that the strength of the acid utilized as the precipitant be higher than the strength of the acid group-containing monomer that aids in the construction of the polymer in order to promote preferential dissociation of the precipitant and protonation of the conjugate base of the acid group-containing monomer. Thus, the pK a The value is the pK of the acid group-containing monomer. a It is desirable that the value be lower than this.
[0219] In some embodiments, the pK of a strong acid a about -10 to about 2, about -9.5 to about 2, about -9 to about 2, about -8.5 to about 2, about -8 to about 2, about -7.5 to about 2, about -7 to about 2, about -6.5 to about 2, about -6 to about 2, about -5.5 to about 2, about -5 to about 2, about -4.8 to about 2, about -4.6 to about 2, about -4.4 to about 2, about -4.2 to about 2, about -4 to about 2, about -3.8 to about 2, about -3.6 to about 2, about -3.4 to about 2, about -3.2 to about 2, about -3 to about 2 ,about-2.8 to about 2, about -2.6 to about 2, about -2.4 to about 2, about -2.2 to about 2, about -2 to about 2, about -1.8 to about 2, about -1.6 to about 2, about -1.4 to about 2, about -1.2 to about 2, about -1 to about 2, about -0.8 to about 2, about -0.6 to about 2, about -0.4 to about 2, about -0.2 to about 2, about 0 to about 2, -10 to about 1.5, about -9.5 to about 1.5, about -9 to about 1.5, about -8.5 to about 1.5, about -8 ~ about 1.5, about -7.5 to about 1.5, about -7 to about 1.5, about -6.5 to about 1.5, about -6 to about 1.5, about -5.5 to about 1.5, about -5 to about 1.5, about -4.8 to about 1.5, about -4.6 to about 1.5, about -4.4 to about 1.5, about -4.2 to about 1.5, about -4 to about 1.5, about -3.8 to about 1.5, about -3.6 to about 1.5, about -3.4 to about 1.5, about -3.2 to about 1.5, about -3 to about 1.5 ,about -2.8 to about 1.5, about -2.6 to about 1.5, about -2.4 to about 1.5, about -2.2 to about 1.5, about -2 to about 1.5, about -1.8 to about 1.5, about -1.6 to about 1.5, about -1.4 to about 1.5, about -1.2 to about 1.5, about -1 to about 1.5, about -0.8 to about 1.5, about -0.6 to about 1.5, about -0.4 to about 1.5, about -0.2 to about 1.5, about 0 to about 1.5, about -10 to about 1, about -9.5 to about 1, about -9 to about 1, about -8.5 to about 1, about -8 to about 1, about -7.5 to about 1, about -7 to about 1, about -6.5 to about 1, about -6 to about 1, about -5.5 to about 1, about -5 to about 1, about -4.8 to about 1, about -4.6 to about 1, about -4.4 to about 1, about -4.2 to about 1, about -4 to about 1, about -3.8 to about 1, about -3.6 to about 1, about -3.4 to about 1, about -3.2 to about 1, about -3 to about 1 ,about It is −2.8 to about 1, about −2.6 to about 1, about −2.4 to about 1, about −2.2 to about 1, about −2 to about 1, about −1.8 to about 1, about −1.6 to about 1, about −1.4 to about 1, about −1.2 to about 1, about −1 to about 1, about −0.8 to about 1, about −0.6 to about 1, about −0.4 to about 1, about −0.2 to about 1, or about 0 to about 1.
[0220] In some embodiments, the pK of a strong acid ais less than 2, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1, less than 0.9, less than 0.8, less than 0.7, less than 0.6, less than 0.5, less than 0.4, less than 0.3, less than 0.2, less than 0.1, less than 0, less than -0.5, less than -1, less than -1.5, less than -2, less than -2.5, less than -3, less than -3.5, less than -4, less than -4.5, less than -5, less than -5.5, less than -6, less than -6.5, less than -7, less than -8, less than -8.5, less than -9, or less than -9.5. a is greater than -10, greater than -9.5, greater than -9, greater than -8.5, greater than -8, greater than -7.5, greater than -7, greater than -6.5, greater than -6, greater than -5.5, greater than -5, greater than -4.5, greater than -4, greater than -3.5, greater than -3, greater than -2.5, greater than -2, greater than -1.5, greater than -1, greater than -0.5, greater than 0, greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, or greater than 1.9.
[0221] In some embodiments, the pK of a strong acid a is between -10 and 2, - between 9.5 and 2, between -9 and 2, between -8.5 and 2, between -8 and 2, between -7.5 and 2, between -7 and 2, between -6.5 and 2, between -6 and 2, between -5.5 and 2, between -5 and 2, between -4.5 and 2, between -4 and 2, between -3.5 and 2, between -3 and 2, between -2.5 and 2, or between -2 and 2.
[0222] In some embodiments, polybasic acids are utilized as precipitants. Polybasic acids refer to acids that have more than one ionizable hydrogen ion (i.e., proton) per molecule. Some non-limiting examples of polybasic acids are sulfuric acid, dithionous acid, dithionous acid, trithionic acid, tetrathionic acid, oxalic acid, malonic acid, tartronic acid, dihydroxymalonic acid, mesooxalic acid, butanedioic acid, methylmalonic acid, fumaric acid, maleic acid, 2-hydroxybutanedioic acid, tartaric acid, oxaloacetic acid, dioxosuccinic acid, glutaric acid, 2-oxoglutaric acid, 3-oxoglutaric acid, hexanedioic acid, citric acid, aconitic acid, isocitric acid, pimelic acid, trimesic acid, mellitic acid, malic acid, and orthosilicic acid. Some non-limiting examples of strong polyprotic acids are sulfuric acid, oxalic acid, mellitic acid, mesoxalic acid, dithionous acid, dithionous acid, trithionic acid, and tetrathionic acid.
[0223] In sulfuric acid, there are two protons that can dissociate per molecule. The pK value at which the first proton dissociates is a The second proton of sulfuric acid has a pK of -2.80, making it a strong acid. a Since sulfuric acid dissociates at a pK of 1.99, the sulfuric acid after the first proton dissociates is also a strong acid, and the dissociation of the second proton must be taken into consideration. Therefore, the proton concentration assuming dissociation from sulfuric acid is calculated based on the fact that both protons dissociate from one molecule of sulfuric acid. In the present invention, a strong acid is specifically an acid having a pK a In some embodiments, a strong polyprotic acid has a pK of about -10 to about 2 for dissociation of a first proton, a second proton, a third proton, or a combination thereof. a In some embodiments, the strong polyprotic acid has a pK between -10 and 2 for dissociation of the first proton, the second proton, the third proton, or a combination thereof. a It is an acid having the formula:
[0224] The pH value of the second suspension determines the concentration of hydroxonium ions contained therein. The pH value of the second suspension governs the state in which the various acids will primarily exist (i.e., protonated or deprotonated form) when placed in the second suspension. For example, if the pH of the second suspension is greater than the pK a lower than the pK of acid B a , acid A will be present in the second suspension primarily in its protonated form and acid B will be present primarily in its deprotonated form.
[0225] pK of the acid used as the precipitant a and the pH of the second suspension is determined by the pK a It would be highly preferred for the pH to be lower than 0.1, which allows dissociation of the precipitant and preferential protonation of the conjugate base of the acid group-containing monomer (present in the second suspension in protonated form), thereby facilitating the separation of the polymer from the aqueous medium and the structural transformation of the polymer.
[0226] The strength of the response of individual monomer units to changes in the pH of the second suspension may be weak in isolation. However, these weak responses add up to hundreds or thousands in the polymer assembly, providing a significant force driving structural transitions throughout the polymer. Thus, large changes in the polymer's conformation can be induced by small changes in the pH of the second suspension. In some embodiments, when the strong acid utilized as a precipitant is added to the first suspension to form the second suspension, the pH of the second suspension is about 0.2 to about 4.5, about 0.2 to about 4.4, about 0.2 to about 4.3, about 0.2 to about 4.1, about 0.2 to about 4, about 0.2 to about 3.8, about 0.2 to about 3.6, about 0.2 to about 3.4, about 0.2 to about 3.2, about 0.2 to about 3, about 0.2 to about 2.8, about 0.2 to about 2.6, about 0.2 to about 2.4, about 0.2 to about 2.2, about 0.2 to about 2, about 0.2 to about 1.8, about 0.2 to about 1.6, about 0.2 to about 1.4, about 0.2 to about 1.2, about 0.4 to about 4.5. ,about0.4 to about 4.3, about 0.4 to about 4.1, about 0.4 to about 4, about 0.4 to about 3.8, about 0.4 to about 3.6, about 0.4 to about 3.4, about 0.4 to about 3.2, about 0.4 to about 3, about 0.4 to about 2.8, about 0.4 to about 2.6, about 0.4 to about 2.4, about 0.4 to about 2.2, about 0.4 to about 2, about 0.4 to about 1.8, about 0.4 to about 1.6, about 0.4 to about 1.4, about 0.6 to about 4.5 ,about 0.6 to about 4.3, about 0.6 to about 4.1, about 0.6 to about 4, about 0.6 to about 3.8, about 0.6 to about 3.6, about 0.6 to about 3.4, about 0.6 to about 3.2, about 0.6 to about 3, about 0.6 to about 2.8, about 0.6 to about 2.6, about 0.6 to about 2.4, about 0.6 to about 2.2, about 0.6 to about 2, about 0.6 to about 1.8, about 0.6 to about 1.6, about 0.8 to about 4.5 ,about 0.8 to about 4.3, about 0.8 to about 4.1, about 0.8 to about 4, about 0.8 to about 3.8, about 0.8 to about 3.6, about 0.8 to about 3.4, about 0.8 to about 3.2, about 0.8 to about 3, about 0.8 to about 2.8, about 0.8 to about 2.6, about 0.8 to about 2.4, about 0.8 to about 2.2, about 0.8 to about 2, about 0.8 to about 1.8, about 1 to about 4. 5, about 1 to about 4.3, about 1 to about 4.1, about 1 to about 4, about 1 to about 3.8, about 1 to about 3.6, about 1 to about 3.4, about 1 to about 3.2, about 1 to about 3, about 1 to about 2.8, about 1 to about 2.6, about 1 to about 2.4, about 1 to about 2.2, about 1 to about 2, about 1.2 to about 4.5, about 1.2 to about 4, about 1.2 to about 3.8, about 1.2 to about 3.6, about 1 0.2 to about 3.4, about 1.2 to about 3.2, about 1.2 to about 3, about 1.2 to about 2.8, about 1.4 to about 4.5, about 1.2 to about 4, about 1.4 to about 3.8, about 1.4 to about 3.6, about 1.4 to about 3.4, about 1.4 to about 3.2, about 1.4 to about 3, about 1.4 to about 2.8, about 1.6 to about 4.5, about 1.6 to about 4, about 1.6 to about 3.8 , about 1.6 to about 3.6, about 1.6 to about 3.4, about 1.6 to about 3.2, about 1.6 to about 3, about 1.8 to about 4.5, about 1.8 to about 4, about 1.8 to about 3.8, about 1.8 to about 3.6, about 1.8 to about 3.4, about 1.8 to about 3.2, about 2 to about 4.5, about 2 to about 4, about 2 to about 3.8, about 2 to about 3.6, or about 2 to about 3.4.
[0227] In some embodiments, when the strong acid utilized as a precipitant is added to the first suspension to form the second suspension, the pH of the second suspension is less than 4.5, less than 4.4, less than 4.3, less than 4.2, less than 4.1, less than 4, less than 3.9, less than 3.8, less than 3.7, less than 3.6, less than 3.5, less than 3.4, less than 3.3, less than 3.2, less than 3.1, less than 3, less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1, less than 0.9, less than 0.8, less than 0.7, less than 0.6, less than 0.5, less than 0.4, or less than 0.3. In some embodiments, when the strong acid utilized as a precipitant is added to the first suspension to form the second suspension, the pH of the second suspension is greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, greater than 1.9 ... , greater than 2, greater than 2.1, greater than 2.2, greater than 2.3, greater than 2.4, greater than 2.5, greater than 2.6, greater than 2.7, greater than 2.8, greater than 2.9, greater than 3, greater than 3.1, greater than 3.2, greater than 3.3, greater than 3.4, greater than 3.5, greater than 3.6, greater than 3.7, greater than 3.8, greater than 3.9, greater than 4, greater than 4.1, greater than 4.2, greater than 4.3, or greater than 4.4.
[0228] 6A and 6B show the physical state of the second suspensions of Comparative Example 1 and Example 2, which have pH values of 6 and 3, respectively, after adding a precipitant to the first suspension to form the second suspension. aThe polymers include copolymers containing structural units derived from carboxylic acid group-containing monomers, nitrile group-containing monomers, and amide group-containing monomers. The structural units derived from carboxylic acid group-containing monomers include acrylate salts. Acrylic acid has a pK a The value is 4.3.
[0229] In Figure 6A, sulfuric acid is added to the first suspension to form a second suspension with a pH of 6. A relatively clear second suspension is observed with no visible signs of precipitation. This is due to the pK of acrylic acid. a This is due to the pH value (i.e. 4.3) of the second suspension being lower than that of the second suspension (i.e. 6). Thus, acrylic acid would remain mainly in the second suspension in a deprotonated form (i.e. as acrylate salts). The same goes for sulfuric acid. However, the presence of acrylate salts, which have a charge that contributes to the constitution of the polymer, allows the continuation of ion-dipole interactions between the polymer and the aqueous solvent, while at the same time providing electrostatic repulsion to the entire copolymer chain, inhibiting the structural transition from coil to globule of the polymer. Therefore, it was not possible to precipitate the polymer from the second suspension.
[0230] Meanwhile, in Figure 6B, sulfuric acid is added to the first suspension to form a second suspension with a pH of 3. There is clear evidence of a precipitate forming due to precipitation, indicating that the separation of the polymer from the aqueous solvent and the conformational change of the polymer are deemed successful. In this example, the pK of acrylic acid a value (i.e., 4.3) is higher than the pH of the second suspension (i.e., 3). Therefore, acrylic acid will be present primarily in its protonated form (i.e., as acrylic acid) in the second suspension. Meanwhile, the pK aSince the value of the pH of the second suspension (i.e., −2.8) is lower than that of the pH of the second suspension (i.e., 3), sulfuric acid will be present in its deprotonated form in the second suspension. The presence of uncharged acrylic acid, which aids in the construction of the polymer, helps to eliminate or significantly reduce the ion-dipole interactions between the polymer and the aqueous solvent, while at the same time initiating the aggregation of the polymer. As a result, precipitation of the polymer occurs.
[0231] Figures 7A and 7B show infrared spectroscopy of the precipitated polymer and the remaining second suspension, respectively, of Example 38. The polymer comprises structural units derived from carboxylic acid group-containing monomers, nitrile group-containing monomers, and amide group-containing monomers.
[0232] Figure 7A is used to identify the precipitated chemicals by detecting the various functional groups present within. The figure shows the 2242 cm observed in transmittance. -1 (C≡N), 3400cm -1 (NH), 1600cm -1 (C=O), 1500cm -1 (COOH) and 1403 cm -1 (COOH) peaks, which are consistent with the nitrile, amide and carboxyl groups contained within the polymer originally present in the first suspension, verifying that the precipitated chemical is, in fact, the polymer disclosed in this invention.
[0233] Meanwhile, FIG. 7B is used to clarify the effectiveness and quality of the precipitation of the polymer from the second suspension, i.e., to check whether the polymer is still present in the remainder of the second suspension. In the infrared spectrum of FIG. 7B, none of the characteristic peaks associated with the nitrile, amide, and carboxyl groups corresponding to the polymer are found. This is evidence that there is no observable polymer in the remainder of the second suspension. This provides evidence that the method of the present invention has a high polymer precipitation effect, avoids polymer contamination, and allows for excellent material recovery. At the same time, FIGS. 8A and 8B show infrared spectroscopy of the precipitated polymer of Example 37 and the remainder of the second suspension, respectively, showing results similar to those of FIGS. 7A and 7B, which further confirms the applicability and effectiveness of the method disclosed herein in precipitating polymers.
[0234] In some embodiments, the precipitating agent is a weak acid. A weak acid is one that does not completely ionize or dissociate to produce hydrogen ions when dissolved in water. In some embodiments, the weak acid is an organic acid. In some embodiments, the organic acid is formic acid, acetic acid, glycolic acid, glyoxylic acid, oxalic acid, propionic acid, acrylic acid, lactic acid, 3-hydroxypropionic acid, glyceric acid, pyruvic acid, 3-oxopropionic acid, 2,3-dioxopropionic acid, malonic acid, tartronic acid, dihydroxymalonic acid, mesoxalic acid, glycidic acid, butyric acid, isobutyric acid, crotonic acid, isocrotonic acid, methacrylic acid, vinylacetic acid, tetrolic acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-oxobutanoic acid, acetoacetic acid, 4-oxobutanoic acid, butanedioic acid, methylmalonic acid, fluorous ... The acidic acid is selected from the group consisting of malic acid, maleic acid, 2-hydroxybutanedioic acid, tartaric acid, oxaloacetic acid, dioxosuccinic acid, valeric acid, isovaleric acid, 2-methylbutyric acid, pivalic acid, 3-hydroxyvaleric acid, 4-hydroxypentanoic acid, 3-hydroxyisovaleric acid, glutaric acid, 2-oxoglutaric acid, 3-oxoglutaric acid, 2-furoic acid, tetrahydrofuroic acid, hexanoic acid, hexanedioic acid, citric acid, aconitic acid, isocitric acid, sorbic acid, pimelic acid, benzoic acid, salicylic acid, 4-carboxybenzoic acid, trimesic acid, mellitic acid, malic acid, dithionous acid, or a combination thereof.
[0235] In some embodiments, the weak acid is phosphoric acid, nitrous acid, orthosilicic acid, or a combination thereof.
[0236] In some embodiments, the pK of the weak acid ais about 2 to about 7, about 2.2 to about 7, about 2.4 to about 7, about 2.6 to about 7, about 2.8 to about 7, about 3 to about 7, about 3.2 to about 7, about 3.4 to about 7, about 3.6 to about 7, about 3.8 to about 7, about 4 to about 7, about 2 to about 6.5, about 2.2 to about 6.5, about 2.4 to about 6.5, about 2.6 to about 6.5, about 2.8 ~ about 6.5, about 3 to about 6.5, about 3.2 to about 6.5, about 3.4 to about 6.5, about 3.6 to about 6.5, about 3.8 to about 6.5, about 4 to about 6.5, about 2 to about 6, about 2.2 to about 6, about 2.4 to about 6, about 2.6 to about 6, about 2.8 to about 6, about 3 to about 6, about 3.2 to about 6, about 3.4 to about 6, about 3. 6 to about 6, about 3.8 to about 6, about 4 to about 6, about 2 to about 5.5, about 2.1 to about 5.5, about 2.2 to about 5.5, about 2.3 to about 5.5, about 2.4 to about 5.5, about 2.5 to about 5.5, about 2.6 to about 5.5, about 2.7 to about 5.5, about 2.8 to about 5.5, about 2.9 to about 5.5, about 3 to about 5.5, About 3.1 to about 5.5, about 3.2 to about 5.5, about 3.3 to about 5.5, about 3.4 to about 5.5, about 3.5 to about 5.5, about 3.6 to about 5.5, about 3.7 to about 5.5, about 3.8 to about 5.5, about 3.9 to about 5.5, about 4 to about 5.5, about 2 to about 5.4, about 2.1 to about 5.4, about 2.2 to about 5.4 , about 2.3 to about 5.4, about 2.4 to about 5.4, about 2.5 to about 5.4, about 2.6 to about 5.4, about 2.7 to about 5.4, about 2.8 to about 5.4, about 2.9 to about 5.4, about 3 to about 5.4, about 3.1 to about 5.4, about 3.2 to about 5.4, about 3.3 to about 5.4, about 3.4 to about 5.4, about 3.5 to about 5.4, about 3.6 to about 5.4, about 3.7 to about 5.4, about 3.8 to about 5.4, about 3.9 to about 5.4, about 4 to about 5.4, about 2 to about 5.2, about 2.1 to about 5.2, about 2.2 to about 5.2, about 2.3 to about 5.2, about 2.4 to about 5.2, about 2.5 to about 5.2, about 2.6 to about 5.2, about 2.7 to about 5.2, about 2.8 to about 5.2, about 2.9 to about 5.2, about 3 to about 5.2, about 3.1 to about 5.2, about 3.2 to about 5.2, about 3.3 to about 5.2, about 3.4 to about 5.2, about 3.5 to about 5.2, about 3.6 to about 5.2, about 3.7 to about 5.2, about 3.8 to about 5.2, about 3.9 to about 5.2, about 4 ~ about 5.2, about 2 to about 5, about 2.1 to about 5, about 2.2 to about 5, about 2.3 to about 5, about 2.4 to about 5, about 2.5 to about 5, about 2.6 to about 5, about 2.7 to about 5, about 2.8 to about 5, about 2.9 to about 5, about 3 to about 5, about 3.1 to about 5, about 3.2 to about 5, about 3.3 to about 5, about 3.4 to about 5, about 3.5 to about 5, about 3.6 to about 5, about 3.7 to about 5, about 3.8 to about 5, about 3.9 to about 5, about 4 to about 5, about 2 to about 4.9, about 2 to about 4.8, about 2 to about 4.7, about 2 to about 4.6, about 2 to about 4.5, about 2 to about 4.4, about 2 to about 4.3, about 2 to about 4.2, about 2 to about 4.1, about 2 to about 4, about 2 to about 3.9, about 2 to about 3.8, about 2 to about 3.7, about 2 to about 3.6, about 2 to about It is about 3.5, about 2 to about 3.4, about 2 to about 3.3, about 2 to about 3.2, about 2 to about 3.1, about 2 to about 3, about 2.2 to about 4.8, about 2.2 to about 4.6, about 2.2 to about 4.4, about 2.2 to about 4.2, about 2.5 to about 4.8, about 2.5 to about 4.6, about 2.5 to about 4.4, about 2.5 to about 4.2, about 2.5 to about 4, about 2.5 to about 3.8, or about 2.5 to about 3.6.
[0237] In some embodiments, the pK of the weak acid a is less than 7, less than 6.5, less than 6, less than 5.5, less than 5.4, less than 5.3, less than 5.2, less than 5.1, less than 5, less than 4.9, less than 4.8, less than 4.7, less than 4.6, less than 4.5, less than 4.4, less than 4.3, less than 4.2, less than 4.1, less than 4, less than 3.9, less than 3.8, less than 3.7, less than 3.6, less than 3.5, less than 3.4, less than 3.3, less than 3.2, less than 3.1, less than 3, less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, or less than 2.1. a is greater than 2, greater than 2.1, greater than 2.2, greater than 2.3, greater than 2.4, greater than 2.5, greater than 2.6, greater than 2.7, greater than 2.8, greater than 2.9, greater than 3, greater than 3.1, greater than 3.2, greater than 3.3, greater than 3.4, greater than 3.5, greater than 3.6, greater than 3.7, greater than 3.8, greater than 3.9, greater than 4, greater than 4.1, greater than 4.2, greater than 4.3, greater than 4.4, greater than 4.5, greater than 4.6, greater than 4.7, greater than 4.8, greater than 4.9, greater than 5, greater than 5.1, greater than 5.2, greater than 5.3, greater than 5.4, greater than 5.5, greater than 6, or greater than 6.5.
[0238] In some embodiments, the pK of the weak acid a is between 2 and 7, between 2 and 6.5, between 2 and 6, between 2 and 5.5, between 2 and 5.4, between 2 and 5.2, between 2 and 5, between 2 and 4.8, between 2 and 4.6, between 2 and 4.4, between 2 and 4.2, or between 2 and 4.
[0239] Some non-limiting examples of polybasic weak acids are oxalic acid, malonic acid, tartronic acid, dihydroxymalonic acid, mesoxalic acid, butanedioic acid, methylmalonic acid, fumaric acid, maleic acid, 2-hydroxybutanedioic acid, tartaric acid, oxaloacetic acid, dioxosuccinic acid, glutaric acid, 2-oxoglutaric acid, 3-oxoglutaric acid, hexanedioic acid, citric acid, aconitic acid, isocitric acid, pimelic acid, trimesic acid, mellitic acid, malic acid, dithionous acid, and orthosilicic acid.
[0240] Phosphate has three protons that can dissociate per molecule. Phosphate has a pK of 2.12 to achieve dissociation of the first proton. a It is considered a weak acid because it has a pK of 7.21. a , the third proton has a pK of 12.32 a Since phosphoric acid is no longer a weak acid after the first proton dissociates, there is no need to consider the dissociation of the second and subsequent protons. Therefore, the proton concentration assuming dissociation from phosphoric acid is calculated on the assumption that only one proton dissociates from one molecule of phosphoric acid.
[0241] In the present invention, a weak acid is specifically an acid having a pK a refers to an acid having a pK of about 2 to about 7 or between 2 and 7. In some embodiments, a polyprotic weak acid has a pK of about 2 to about 7 upon dissociation of a first proton, a second proton, a third proton, or a combination thereof. a In some embodiments, the polyprotic weak acid is an acid having a pK for dissociation of the first proton, the second proton, the third proton, or a combination thereof. a is an acid between 2 and 7.
[0242] In the case of oxalic acid, there are two protons that can dissociate per molecule. Oxalic acid has a pK of 1.25 to achieve dissociation of the first proton. a Oxalic acid is considered a strong acid because it has a pK of 3.81. a Since oxalic acid dissociates at 1 proton, after the first proton dissociates, it is a weak acid. Therefore, the proton concentration assuming dissociation from oxalic acid is calculated based on the dissociation of the first proton and the partial dissociation of the second proton from one molecule of oxalic acid. Therefore, oxalic acid can be considered both as a strong polyprotic acid (related to the dissociation of the first proton) and as a weak polyprotic acid (related to the dissociation of the second proton).
[0243] In some embodiments, when the weak acid utilized as a precipitant is added to the first suspension to form the second suspension, the pH of the second suspension is about 0.5 to about 3, about 0.5 to about 2.9, about 0.5 to about 2.8, about 0.5 to about 2.7, about 0.5 to about 2.6, about 0.5 to about 2.5, about 0.5 to about 2.4, about 0.5 to about 2.3, about 0.5 to about 2.2, about 0.5 to about 2.1, about 0.5 to about 2, about 0.5 to about 1.9, about 0.5 to about 1.8, about 0.5 to about 1.7, about 0.5 to about 1.6, about 0.5 to about 1.5, about 0.6 to about 3. , about 0.6 to about 2.9, about 0.6 to about 2.8, about 0.6 to about 2.7, about 0.6 to about 2.6, about 0.6 to about 2.5, about 0.6 to about 2.4, about 0.6 to about 2.3, about 0.6 to about 2.2, about 0.6 to about 2.1, about 0.6 to about 2, about 0.6 to about 1.9, about 0.6 to about 1.8, about 0.6 to about 1.7, about 0.6 to about 1.6, about 0.7 to about 3, about 0.7 to about 2.9, about 0.7 to about 2.8, about 0.7 to about 2.7, about 0.7 to about 2.6, about 0.7 to about 2.5, about 0.7 to about 2.4, about 0.7 to about 2.3, about 0.7 to about 2.2, about 0.7 to about 2.1, about 0.7 to about 2, about 0.7 to about 1.9, about 0.7 to about 1.8, about 0.7 to about 1.7, about 0.8 to about 3, about 0.8 to about 2.9, about 0.8 to about 2.8, about 0.8 to about 2.7, about 0.8 to about 2.6, about 0.8 to about 2.5, about 0.8 to about 2.4, about 0.8 to about 2.3, about 0.8 to about 2.2, about 0.8 to about 2.1, about 0.8 to about 2, about 0.8 to about 1.9, about 0.8 to about 1.8, about 0.9 to about 3, about 0.9 to about 2.9, about 0.9 to about 2.8, about 0.9 to about 2.7, about 0.9 to about 2.6, about 0.9 to about about 2.5, about 0.9 to about 2.4, about 0.9 to about 2.3, about 0.9 to about 2.2, about 0.9 to about 2.1, about 0.9 to about 2, about 0.9 to about 1.9, about 1 to about 3, about 1 to about 2.9, about 1 to about 2.8, about 1 to about 2.7, about 1 to about 2.6, about 1 to about 2.5, about 1 to about 2.4, about 1 to about 2.3, about 1 to about 2.2, about 1 to about 2.1, about 1 to about 2, about 1.2 to about 3, about 1.2 to about 2.8, about 1.2 to about 2.6, about 1.2 to about 2.4, about 1.2 to about 2.2, about 1.5 to about 3, about 1.5 to about 2.8, or about 1.5 to about 2.6.
[0244] In some embodiments, when a weak acid utilized as a precipitant is added to a first suspension to form a second suspension, the pH of the second suspension is less than 3, less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1, less than 0.9, less than 0.8, less than 0.7, or less than 0.6. In some embodiments, when a weak acid utilized as a precipitant is added to a first suspension to form a second suspension, the pH of the second suspension is greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, greater than 1.9, greater than 2, greater than 2.1, greater than 2.2, greater than 2.3, greater than 2.4, greater than 2.5, greater than 2.6, greater than 2.7, greater than 2.8, or greater than 2.9.
[0245] In some embodiments, the pH of the second suspension is from about 0.2 to about 4.5, from about 0.2 to about 4.4, from about 0.2 to about 4.3, from about 0.2 to about 4.1, from about 0.2 to about 4, from about 0.2 to about 3.8, from about 0.2 to about 3.6, from about 0.2 to about 3.4, from about 0.2 to about 3.2, from about 0.2 to about 3, from about 0.2 to about 2.8, from about 0.2 to about 2.6, from about 0.2 to about 2.4, from about 0.2 to about 2.2, from about 0.2 to about 2, from about 0.2 to about 1.8, from about 0.2 to about 1.6, or from about 0.2 to about 1. 4, about 0.2 to about 1.2, about 0.4 to about 4.5, about 0.4 to about 4.5, about 0.4 to about 4.3, about 0.4 to about 4.1, about 0.4 to about 4, about 0.4 to about 3.8, about 0.4 to about 3.6, about 0.4 to about 3.4, about 0.4 to about 3.2, about 0.4 to about 3, about 0.4 to about 2.8, about 0.4 to about 2.6, about 0.4 to about 2.4, about 0.4 to about 2.2, about 0.4 to about 2, about 0.4 to about 1.8, about 0.4 to about 1.6, about 0.4 to about 1.4, about 0.6 to about 4.5 ,about0.6 to about 4.3, about 0.6 to about 4.1, about 0.6 to about 4, about 0.6 to about 3.8, about 0.6 to about 3.6, about 0.6 to about 3.4, about 0.6 to about 3.2, about 0.6 to about 3, about 0.6 to about 2.8, about 0.6 to about 2.6, about 0.6 to about 2.4, about 0.6 to about 2.2, about 0.6 to about 2, about 0.6 to about 1.8, about 0.6 to about 1.6, about 0.8 to about 4.5 ,about 0.8 to about 4.3, about 0.8 to about 4.1, about 0.8 to about 4, about 0.8 to about 3.8, about 0.8 to about 3.6, about 0.8 to about 3.4, about 0.8 to about 3.2, about 0.8 to about 3, about 0.8 to about 2.8, about 0.8 to about 2.6, about 0.8 to about 2.4, about 0.8 to about 2.2, about 0.8 to about 2, about 0.8 to about 1.8, about 1 to about 4.5, about 1 to about 4.3, about 1 to about 4.1, about 1 to about 4, about 1 to about 3.8, about 1 to about 3.6, about 1 to about 3.4, about 1 to about 3.2, about 1 to about 3, about 1 to about 2.8, about 1 to about 2.6, about 1 to about 2.4, about 1 to about 2.2, about 1 to about 2, about 1.2 to about 4.5, about 1.2 to about 4, about 1.2 to about 3.8, about 1.2 to about 3.6, about 1.2 to about 3.4, about 1.2 to about 3.2, about 1.2 to about 3, about 1.2 to about 2.8, about 1.4 to about 4.5, about 1. 4 about 1.8 to about 4.5, about 1.6 to about 4, about 1.6 to about 3.8, about 1.4 to about 3.6, about 1.4 to about 3.4, about 1.4 to about 3.2, about 1.4 to about 3, about 1.4 to about 2.8, about 1.6 to about 4.5, about 1.6 to about 4, about 1.6 to about 3.8, about 1.6 to about 3.6, about 1.6 to about 3.4, about 1.6 to about 3.2, about 1.6 to about 3, about 1.8 to about 4.5, about 1.8 to about 4, about 1.8 to about 3.8, about 1.8 to about 3.6, about 1.8 to about 3.4, about 1.8 to about 3.2, about 2 to about 4.5, about 2 to about 4, about 2 to about 3.8, about 2 to about 3.6, or about 2 to about 3.4.
[0246] In some embodiments, the pH of the second suspension is less than 4.5, less than 4.4, less than 4.3, less than 4.2, less than 4.1, less than 4, less than 3.9, less than 3.8, less than 3.7, less than 3.6, less than 3.5, less than 3.4, less than 3.3, less than 3.2, less than 3.1, less than 3, less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, less than 1.1, less than 1, less than 0.9, less than 0.8, less than 0.7, less than 0.6, less than 0.5, less than 0.4, or less than 0.3. In some embodiments, the pH of the second suspension is greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5, greater than 0.6, greater than 0.7, greater than 0.8, greater than 0.9, greater than 1, greater than 1.1, greater than 1.2, greater than 1.3, greater than 1.4, greater than 1.5, greater than 1.6, greater than 1.7, greater than 1.8, greater than 1.9, greater than 2, greater than 2.1, greater than 2.2 greater than 2.3, greater than 2.4, greater than 2.5, greater than 2.6, greater than 2.7, greater than 2.8, greater than 2.9, greater than 3, greater than 3.1, greater than 3.2, greater than 3.3, greater than 3.4, greater than 3.5, greater than 3.6, greater than 3.7, greater than 3.8, greater than 3.9, greater than 4, greater than 4.1, greater than 4.2, greater than 4.3, or greater than 4.4.
[0247] In some embodiments, the pH of the second suspension is between about 0.2 pH units and about 6.8 pH units, between about 0.2 pH units and about 6.5 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 5.5 pH units, between about 0.2 pH units and about 5 pH units, between about 0.2 pH units and about 4.5 pH units, between about 0.2 pH units and about 4 pH units, between about 0.2 pH units and about 3 ...6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH units, between about 0.2 pH units and about 6 pH about 0.5pH units to about 3pH units, about 0.2pH units to about 2.5pH units, about 0.2pH units to about 2pH units, about 0.5pH units to about 6.8pH units, about 0.5pH units to about 6.5pH units, about 0.5pH units to about 6pH units, about 0.5pH units to about 5.5pH units, about 0.5pH units to about 5pH units, about 0.5pH units to about 4.5pH units, about 0.5pH units to about 4pH units, about 0.5pH units H units to about 3.5 pH units, about 0.5 pH units to about 3 pH units, about 0.5 pH units to about 2.5 pH units, about 1 pH unit to about 6.8 pH units, about 1 pH unit to about 6.5 pH units, about 1 pH unit to about 6 pH units, about 1 pH unit to about 5.5 pH units, about 1 pH unit to about 5 pH units, about 1 pH unit to 4.5 pH units, about 1 pH unit to about 4 pH units, about 1 pH unit to about 3.5 pH units, about 1 pH unit to about 3 pH units, about 1.5 pH units to about 6.8 pH units, about 1.5 pH units to about 6.5 pH units, about 1.5 pH units to about 6 pH units, about 1.5 pH units to about 5.5 pH units, about 1.5 pH units to about 5 pH units, about 1.5 pH units to about 4.5 pH units, about 1.5 pH units to about 4 pH units, or about 1.5 pH units to about 3.5 pH units; and a Less than.
[0248] In some embodiments, the pH of the second suspension is at least 0.2 pH units, at least 0.5 pH units, at least 1 pH unit, at least 1.5 pH units, at least 2 pH units, at least 2.5 pH units, at least 3 pH units, at least 3.5 pH units, at least 4 pH units, at least 4.5 pH units, at least 5 pH units, at least 5.5 pH units, at least 6 pH units, or at least 6.5 pH units and is greater than or equal to the pK aIn some embodiments, the pH of the second suspension is at most 6.8 pH units, at most 6.5 pH units, at most 6 pH units, at most 5.5 pH units, at most 5 pH units, at most 4.5 pH units, at most 4 pH units, at most 3.5 pH units, at most 3 pH units, at most 2.5 pH units, at most 2 pH units, at most 1.5 pH units, at most 1 pH unit, or at most 0.5 pH units and the pK a Less than.
[0249] In some embodiments, the concentration of the precipitating agent is about 1M to about 8M, about 1M to about 7.5M, about 1M to about 7M, about 1M to about 6.5M, about 1M to about 6M, about 1M to about 5.5M, about 1M to about 5M, about 1M to about 4.5M, about 1M to about 4M, about 1.5M to about 8M, about 1.5M to about 7.5M, about 1.5M to about 7M, about 1.5M to about 6.5M, about 1.5M to about 6M, about 1.5M to about 5.5M, about 1.5M to about 5M, about 1.5M to about 4.5M, about 2M to about 8M, about 2M to about 7.5M, about 2M to about 7M ,about 2M to about 6.5M, about 2M to about 6M, about 2M to about 5.5M, about 2M to about 5M, about 2.5M to about 8M, about 2.5M to about 7.5M, about 2.5M to about 7M, about 2.5M to about 6.5M, About 2.5M to about 6M, about 2.5M to about 5.5M, about 3M to about 8M, about 3M to about 7.5M, about 3M to about 7M, about 3M to about 6.5M, about 3M to about 6M, or about 4M to about 8M.
[0250] In some embodiments, the concentration of the precipitating agent is less than 8 M, less than 7.5 M, less than 7 M, less than 6.5 M, less than 6 M, less than 5.5 M, less than 5 M, less than 4.5 M, less than 4 M, less than 3.5 M, less than 3 M, less than 2.5 M, less than 2 M, or less than 1.5 M. In some embodiments, the concentration of the precipitating agent is greater than 1 M, greater than 1.5 M, greater than 2 M, greater than 2.5 M, greater than 3 M, greater than 3.5 M, greater than 4 M, greater than 4.5 M, greater than 5 M, greater than 5.5 M, greater than 6 M, greater than 6.5 M, greater than 7 M, or greater than 7.5 M.
[0251] After the addition of the precipitant to the first suspension in forming the second suspension, the time allowed for the precipitant to induce precipitation of the polymer is important to achieve precipitation of the polymer in the second suspension. If there is insufficient contact time between the precipitant and the components of the first suspension, the precipitant may not have enough time to destabilize, disrupt and break the bonds that are initially formed between the polymer and the aqueous solvent to an extent that allows precipitation of the polymer. In some embodiments, after the addition of the precipitant to the first suspension in forming the second suspension, the precipitant is allowed to react for about 1 minute to about 180 minutes, about 1 minute to about 160 minutes, about 1 minute to about 140 minutes, about 1 minute to about 120 minutes, about 1 minute to about 110 minutes, about 1 minute to about 100 minutes, about 1 minute to about 90 minutes, about 1 minute to about 80 minutes, about 1 minute to about 70 minutes, about 1 minute to about 60 minutes, about 3 minutes to about 120 minutes, about 3 minutes to about 110 minutes, about 3 minutes to about 100 minutes, about 3 minutes to about 90 minutes, about 3 minutes to about 80 minutes, about 3 minutes to about 70 minutes, about 3 minutes to about 60 minutes, about 5 minutes to about 120 minutes, about 5 minutes to about 110 minutes, about 5 minutes to about 100 minutes, about 5 minutes to about 90 minutes, about 5 minutes to about 80 minutes, about 5 minutes to about 70 minutes, about 5 minutes to about 60 minutes, about 10 minutes to about 120 minutes, about 10 minutes to about 110 minutes, about 10 minutes to about 100 minutes, about 10 minutes to about 90 minutes, about 10 minutes to about 80 minutes ,about 10 minutes to about 70 minutes, about 10 minutes to about 60 minutes, about 15 minutes to about 120 minutes, about 15 minutes to about 110 minutes, about 15 minutes to about 100 minutes, about 15 minutes to about 90 minutes, about 15 minutes to about 80 minutes, about 15 minutes to about 70 minutes, about 15 minutes to about 60 minutes, about 20 minutes to about 120 minutes, about 20 minutes to about 110 minutes, about 20 minutes to about 100 minutes, about 20 minutes to about 90 minutes, about 20 minutes to about 80 minutes, about 20 minutes to about 70 minutes, about 20 minutes to about 60 minutes, about 25 minutes The suspension is left in the second suspension without stirring for about 120 minutes, about 25 minutes to about 110 minutes, about 25 minutes to about 100 minutes, about 25 minutes to about 90 minutes, about 25 minutes to about 80 minutes, about 25 minutes to about 70 minutes, about 25 minutes to about 60 minutes, about 30 minutes to about 120 minutes, about 30 minutes to about 110 minutes, about 30 minutes to about 100 minutes, about 30 minutes to about 90 minutes, about 30 minutes to about 80 minutes, about 30 minutes to about 70 minutes, or about 30 minutes to about 60 minutes.
[0252] In some embodiments, following addition of the precipitating agent to the first suspension in forming the second suspension, the precipitating agent is allowed to sit in the second suspension without stirring for less than 180 minutes, less than 160 minutes, less than 140 minutes, less than 120 minutes, less than 110 minutes, less than 100 minutes, less than 90 minutes, less than 80 minutes, less than 70 minutes, less than 60 minutes, less than 50 minutes, less than 40 minutes, less than 30 minutes, less than 20 minutes, less than 15 minutes, less than 10 minutes, or less than 5 minutes. In some embodiments, following addition of the precipitating agent to the first suspension in forming the second suspension, the precipitating agent is allowed to sit in the second suspension without stirring for more than 1 minute, more than 3 minutes, more than 5 minutes, more than 10 minutes, more than 15 minutes, more than 20 minutes, more than 30 minutes, more than 40 minutes, more than 50 minutes, more than 60 minutes, more than 70 minutes, more than 80 minutes, more than 90 minutes, more than 100 minutes, more than 110 minutes, more than 120 minutes, more than 140 minutes, or more than 160 minutes.
[0253] One of the most important factors governing the precipitation of the polymer is the temperature of the second suspension. Hydrogen bonds are mainly formed at relatively low temperatures and weaken with increasing temperature. Also, hydrophobic interactions are strengthened at high temperatures. Therefore, a second suspension with a slight temperature increase can help promote the precipitation of the polymer through weakening the hydrogen bonding interactions between the polymer and the aqueous solvent, and strengthening the hydrophobic interactions of the hydrophobic group-containing monomers that contribute to the formation of the polymer.
[0254] In some embodiments, the precipitant may be applied at a temperature between about 20° C. and about 95° C., between about 20° C. and about 90° C., between about 20° C. and about 85° C., between about 20° C. and about 80° C., between about 20° C. and about 75° C., between about 20° C. and about 70° C., between about 20° C. and about 65° C., between about 20° C. and about 60° C., between about 20° C. and about 55° C., between about 20° C. and about 50° C., between about 25° C. and about 95° C., between about 25° C. and about 90° C., between about 25° C. and about 85° C., between about 25° C. and about 80°C, about 25°C to about 75°C, about 25°C to about 70°C, about 25°C to about 65°C, about 25°C to about 60°C, about 25°C to about 55°C, about 25°C to about 50°C, about 30°C to about 95°C, about 30°C to about 90°C, about 30°C to about 85°C, about 30°C to about 80°C, about 30°C to about 75°C, about 30°C to about 70°C, about 30°C to about 65°C, about 30°C to about 60°C, about 30°C to about 55°C, About 30°C to about 50°C, about 35°C to about 95°C, about 35°C to about 90°C, about 35°C to about 85°C, about 35°C to about 80°C, about 35°C to about 75°C, about 35°C to about 70°C, about 35°C to about 65°C, about 35°C to about 60°C, about 35°C to about 55°C, about 40°C to about 95°C, about 40°C to about 90°C, about 40°C to about 85°C, about 40°C to about 80°C, about 40°C to about 75°C, about 40°C The first suspension is added at a temperature of about 70°C, about 40°C to about 65°C, about 40°C to about 60°C, about 45°C to about 95°C, about 45°C to about 90°C, about 45°C to about 85°C, about 45°C to about 80°C, about 45°C to about 75°C, about 45°C to about 70°C, about 45°C to about 65°C, about 50°C to about 90°C, about 50°C to about 85°C, about 50°C to about 80°C, or about 50°C to about 70°C.
[0255] In some embodiments, the precipitating agent is added to the first suspension at a temperature below 95° C., below 90° C., below 85° C., below 80° C., below 75° C., below 70° C., below 65° C., below 60° C., below 55° C., below 50° C., below 45° C., below 40° C., below 35° C., below 30° C., or below 25° C. In some embodiments, the precipitating agent is added to the first suspension at a temperature above 20° C., above 25° C., above 30° C., above 35° C., above 40° C., above 45° C., above 50° C., above 55° C., above 60° C., above 65° C., above 70° C., above 75° C., above 80° C., above 85° C., or above 90° C.
[0256] A high percentage of charged functional groups (e.g., acid-base) in the copolymer that can undergo ion-dipole interactions with water molecules in the aqueous solvent may require the addition of a relatively high concentration or amount of precipitant to the first suspension to form a second suspension with the desired pH range as defined in the present invention. This is due to the fact that (1) since the strength of ion-dipole interactions is stronger than that of hydrogen bonds, the formation of a higher concentration of hydroxonium ions may potentially smooth the separation process of the polymer from the aqueous solvent by increasing the possibility of breaking the stronger ion-dipole interactions, and (2) a high percentage of charged functional groups will require a higher concentration of hydroxonium ions (or hydrogen ions) for protonation, and therefore the resulting change in charge of the polymer (i.e., from negatively charged to uncharged) may be sufficient to induce a structural transition.
[0257] In some embodiments, after addition of the precipitating agent to the first suspension in forming the second suspension, the second suspension is agitated to achieve precipitation of the polymer. In some embodiments, a planetary agitation mixer, stirrer, blender, ultrasonic generator, or combinations thereof is used to agitate the second suspension.
[0258] In some embodiments, prior to adding the precipitant to the first suspension in forming the second suspension, the first suspension is agitated to maximize dissolution of the polymer in the aqueous solvent and allow for better dispersion of the polymer within the first suspension. In some embodiments, a planetary agitator mixer, stirrer, blender, ultrasonic generator, or combinations thereof is used to agitate the first suspension.
[0259] In some embodiments, the second suspension is stirred at a speed of about 150 rpm to about 600 rpm, about 150 rpm to about 550 rpm, about 150 rpm to about 500 rpm, about 150 rpm to about 450 rpm, about 150 rpm to about 400 rpm, about 150 rpm to about 350 rpm, about 200 rpm to about 600 rpm, about 200 rpm to about 550 rpm, about 200 rpm to about 500 rpm, about 200 rpm to about 450 rpm, about 20 The mixture is stirred at a speed of about 0 rpm to about 400 rpm, about 250 rpm to about 600 rpm, about 250 rpm to about 550 rpm, about 250 rpm to about 500 rpm, about 250 rpm to about 450 rpm, about 300 rpm to about 600 rpm, about 300 rpm to about 550 rpm, about 300 rpm to about 500 rpm, about 350 rpm to about 600 rpm, about 350 rpm to about 550 rpm, or about 400 rpm to about 600 rpm.
[0260] In some embodiments, the second suspension is stirred at a speed of less than 600 rpm, less than 580 rpm, less than 560 rpm, less than 540 rpm, less than 520 rpm, less than 500 rpm, less than 480 rpm, less than 460 rpm, less than 440 rpm, less than 420 rpm, less than 400 rpm, less than 380 rpm, less than 360 rpm, less than 340 rpm, less than 320 rpm, less than 300 rpm, less than 280 rpm, less than 260 rpm, less than 240 rpm, less than 220 rpm, less than 200 rpm, or less than 180 rpm. In some embodiments, the second suspension is stirred at a speed of greater than 150 rpm, greater than 170 rpm, greater than 200 rpm, greater than 220 rpm, greater than 240 rpm, greater than 260 rpm, greater than 280 rpm, greater than 300 rpm, greater than 320 rpm, greater than 340 rpm, greater than 360 rpm, greater than 380 rpm, greater than 400 rpm, greater than 420 rpm, greater than 440 rpm, greater than 460 rpm, greater than 480 rpm, greater than 500 rpm, greater than 520 rpm, greater than 540 rpm, greater than 560 rpm, or greater than 580 rpm.
[0261] In some embodiments, the second suspension is allowed to stand for about 1 minute to about 180 minutes, about 1 minute to about 150 minutes, about 1 minute to about 120 minutes, about 1 minute to about 100 minutes, about 1 minute to about 80 minutes, about 1 minute to about 60 minutes, about 3 minutes to about 180 minutes, about 3 minutes to about 150 minutes, about 3 minutes to about 120 minutes, about 3 minutes to about 100 minutes, about 3 minutes to about 80 minutes, about 3 minutes to about 60 minutes, about 5 minutes to about 180 minutes, about 5 minutes to about 150 minutes, about 5 minutes to about 120 minutes, about 5 minutes to about 100 minutes, about 5 minutes to about 80 minutes, about 5 minutes to about 60 minutes, about 10 minutes to about 180 minutes, about 10 minutes to about 150 minutes, about 10 minutes to about 120 minutes, about 10 minutes to about 100 minutes, about 10 minutes to about 80 minutes. The mixture is stirred for about 10 minutes, about 10 minutes to about 60 minutes, about 15 minutes to about 180 minutes, about 15 minutes to about 150 minutes, about 15 minutes to about 120 minutes, about 15 minutes to about 100 minutes, about 15 minutes to about 80 minutes, about 15 minutes to about 60 minutes, about 20 minutes to about 150 minutes, about 20 minutes to about 120 minutes, about 20 minutes to about 100 minutes, about 20 minutes to about 80 minutes, about 20 minutes to about 60 minutes, about 25 minutes to about 150 minutes, about 25 minutes to about 120 minutes, about 25 minutes to about 100 minutes, about 25 minutes to about 80 minutes, about 25 minutes to about 60 minutes, about 30 minutes to about 150 minutes, about 30 minutes to about 120 minutes, about 30 minutes to about 100 minutes, about 30 minutes to about 80 minutes, or about 30 minutes to about 60 minutes.
[0262] In some embodiments, the second suspension is stirred for less than 180 minutes, less than 160 minutes, less than 140 minutes, less than 120 minutes, less than 110 minutes, less than 100 minutes, less than 90 minutes, less than 80 minutes, less than 70 minutes, less than 60 minutes, less than 50 minutes, less than 40 minutes, less than 30 minutes, less than 20 minutes, less than 15 minutes, less than 10 minutes, or less than 5 minutes. In some embodiments, the second suspension is stirred for more than 1 minute, more than 3 minutes, more than 5 minutes, more than 10 minutes, more than 15 minutes, more than 20 minutes, more than 30 minutes, more than 40 minutes, more than 50 minutes, more than 60 minutes, more than 70 minutes, more than 80 minutes, more than 90 minutes, more than 100 minutes, more than 110 minutes, more than 120 minutes, more than 140 minutes, or more than 160 minutes.
[0263] In some embodiments, the planetary agitation mixer includes at least one planetary blade and at least one high-speed dispersion blade. In certain embodiments, the rotation speed of the planetary blade is about 20 rpm to about 200 rpm, about 20 rpm to about 150 rpm, about 30 rpm to about 150 rpm, or about 50 rpm to about 100 rpm. In certain embodiments, the rotation speed of the dispersion blade is about 1,000 rpm to about 4,000 rpm, about 1,000 rpm to about 3,500 rpm, about 1,000 rpm to about 3,000 rpm, about 1,000 rpm to about 2,000 rpm, about 1,500 rpm to about 3,000 rpm, or about 1,500 rpm to about 2,500 rpm.
[0264] In certain embodiments, the ultrasonic generator is an ultrasonic bath, a probe type ultrasonic generator, or an ultrasonic flow cell. In some embodiments, the ultrasonic generator is operated at a power density of about 10 W / L to about 100 W / L, about 20 W / L to about 100 W / L, about 30 W / L to about 100 W / L, about 40 W / L to about 80 W / L, about 40 W / L to about 70 W / L, about 40 W / L to about 60 W / L, about 40 W / L to about 50 W / L, about 50 W / L to about 60 W / L, about 20 W / L to about 80 W / L, about 20 W / L to about 60 W / L, or about 20 W / L to about 40 W / L. In certain embodiments, the ultrasonic generator is operated at a power density of greater than 10 W / L, greater than 20 W / L, greater than 30 W / L, greater than 40 W / L, greater than 50 W / L, greater than 60 W / L, greater than 70 W / L, greater than 80 W / L, or greater than 90 W / L.
[0265] In some embodiments, the ultrasonic generator operates at a power of about 100 W to about 1000 W, about 200 W to about 1000 W, about 300 W to about 1000 W, about 400 W to about 1000 W, about 500 W to about 1000 W, about 500 W to about 900 W, about 500 W to about 800 W, about 500 W to about 700 W, or about 500 W to about 600 W. In some embodiments, the ultrasonic generator operates at a power of less than 1000 W, less than 900 W, less than 800 W, less than 700 W, less than 600 W, less than 500 W, less than 400 W, or less than 300 W. In some embodiments, the ultrasonic generator operates at a power of greater than 100W, greater than 200W, greater than 300W, greater than 400W, greater than 500W, greater than 600W, greater than 700W, or greater than 800W.
[0266] In some embodiments, the polymer is precipitated after the addition of the precipitant to the first suspension when forming the second suspension. In some embodiments, the polymer is precipitated after the addition of the precipitant to the first suspension when forming the second suspension, while the precipitant is left in the second suspension without stirring for a period of time. In some embodiments, the polymer is precipitated after the addition of the precipitant to the first suspension when forming the second suspension, while the second suspension is stirred for a period of time.
[0267] In some embodiments, the second suspension is sieved to separate the precipitated polymer from the remainder of the second suspension (including the aqueous solvent and dissolved precipitant). In some embodiments, filtration, sieving, decantation, or a combination thereof may be used to sieve the second suspension.
[0268] 9 is a flow chart of one embodiment showing the steps of a method 900 for precipitating a polymer as disclosed herein, and subsequent further processing for extraction of the polymer. The remainder of the second suspension, including the aqueous solvent and dissolved precipitant, can be subjected to drying or concentration to remove the aqueous solvent. The recovered precipitant can be reused for further precipitation of other polymers. This allows for the formation of a closed loop recovery process in which the material is repeatedly regenerated and reused, participating in a continuous loop configuration and helping to create a circular economy.
[0269] The method disclosed herein has been developed specifically for the optimization of polymer formulations, i.e., the composition of the polymers of the present invention is governed by the ability of the polymer to precipitate by the addition of a precipitating agent. The use of the method of the present invention in the precipitation of polymers, including copolymers comprising structural units derived from acid group-containing monomers and structural units derived from hydrophobic group-containing monomers, results in high polymer recoveries (>98%).
[0270] Polymer recovery refers to the percentage of the weight of the polymer recovered based on the initial weight of the polymer present in the first suspension before adding the precipitant.This serves as a reflection of the percentage of the polymer recovered and a measure of the effectiveness of the method disclosed herein in precipitating the polymer.The fact that the method disclosed herein provides a high polymer recovery indicates that most of the polymer is precipitated and recovered, and the amount of polymer remaining in the second suspension is negligible.
[0271] The method of the present invention is particularly applicable as part of a battery electrode recycling system to effect precipitation of the polymer binder.
[0272] In some embodiments, the battery can be a primary battery or a secondary battery.Some non-limiting examples of batteries include alkaline batteries, aluminum-air batteries, lithium batteries, lithium-air batteries, magnesium batteries, solid-state batteries, silver oxide batteries, zinc-air batteries, aluminum-ion batteries, lead-acid batteries, lithium-ion batteries, magnesium-ion batteries, potassium-ion batteries, sodium-ion batteries, lithium-air batteries, aluminum-air batteries, zinc-air batteries, sodium-air batteries, silicon-air batteries, zinc-ion batteries, and sodium-sulfur batteries.
[0273] Lithium-ion batteries (LIBs) have become widely used in various applications over the past decades, especially in home appliances, due to their excellent energy density, long cycle life and high discharge performance. With the rapid market development of electric vehicles (EVs) and grid energy storage, LIBs with their high performance and low cost are currently one of the most promising choices for large-scale energy storage devices.
[0274] If the distribution of lithium-ion batteries increases significantly, there is a concern that the market will be flooded with end-of-life (EoL) batteries. Since a huge amount of lithium-ion batteries are expected to reach the end of their life in the future, there is an urgent need to develop an economical recycling process for used lithium-ion batteries to manage used packs and cells. In addition to used batteries, there is also a large amount of waste or scrap electrodes generated during the battery manufacturing process, which needs to be recycled.
[0275] Pyrometallurgical processes are one of the recycling strategies proposed or adopted for the recycling of spent batteries and are particularly suitable for the recovery of cathode components, as cathode materials constitute the main high added value in production.
[0276] The pyrometallurgical process involves heating the electrode at high temperatures above the decomposition temperature of the polymer binder, but ideally below the melting temperature of other electrode components, such as the current collector and electrode active material. This process results in carbonization of the polymer binder, making recycling and / or regeneration of the polymer binder infeasible. Moreover, the combustion process can generate harmful compounds and / or pollutants resulting from the decomposition of the polymer binder. For example, if an electrode containing polyvinylidene fluoride (PVDF) binder material is pyrometallurgical, toxic compounds such as hydrogen fluoride that may pose long-term health risks will be produced. Also, pyrometallurgical processes are highly energy intensive, resulting in huge associated energy costs.
[0277] Current methods for recovering components of the electrode layer of an electrode (e.g., polymer binder and electrode active material) have their own drawbacks and are ineffective for recovering the components of the electrode layer derived from an aqueous slurry. Thus, there is a need to develop a method for recovering the components of the electrode layer derived from an aqueous slurry in a highly efficient and effective manner.
[0278] Thus, the methods of the present invention are particularly applicable as part of a battery electrode recycling system that achieves precipitation of a polymeric binder, where the polymeric binder refers to a polymer disclosed herein. Precipitation of the polymeric binder is accomplished by adding a precipitating agent to a first suspension to form a second suspension, where the first suspension includes an electrode layer and an aqueous solvent, the electrode layer includes a polymeric binder, and the polymeric binder includes a copolymer including structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer.
[0279] The methods disclosed herein may be used following the delamination of an electrode, where the electrode comprises a current collector and an electrode layer comprising a polymeric binder coated on one or both sides of the current collector.
[0280] In some embodiments, the electrode may be a cathode or an anode. In some embodiments, the electrode layer further comprises a metal-containing material, an electrode active material, or a combination thereof.
[0281] In some embodiments, following electrode stripping, the recovered electrode layer is immersed in an aqueous solvent and agitated in forming a first suspension, which can facilitate precipitation of the polymer binder by breaking down the recovered electrode layer into small chucks or pieces, increasing the surface area for a precipitating agent to act on at a later stage.
[0282] In some embodiments, the first suspension comprises a polymeric binder. In some embodiments, the first suspension further comprises a metal-containing material, an electrode active material, or a combination thereof.
[0283] In some embodiments, following peeling of the electrode, the recovered electrode layer is subjected to a precipitation process for about 0.25 minutes to about 20 minutes, about 0.25 minutes to about 15 minutes, about 0.25 minutes to about 10 minutes, about 0.5 minutes to about 20 minutes, about 0.5 minutes to about 15 minutes, about 0.5 minutes to about 10 minutes, about 0.75 minutes to about 20 minutes, about 0.75 minutes to about 15 minutes, about 0.75 minutes to about 10 minutes, or about 0.75 minutes to about 10 minutes in forming the first suspension. The substrate is immersed and stirred in the aqueous solvent for about 1 minute, about 1 minute to about 20 minutes, about 1 minute to about 15 minutes, about 1 minute to about 10 minutes, about 2 minutes to about 20 minutes, about 2 minutes to about 15 minutes, about 2 minutes to about 10 minutes, about 4 minutes to about 20 minutes, about 4 minutes to about 15 minutes, about 4 minutes to about 10 minutes, about 5 minutes to about 20 minutes, about 5 minutes to about 15 minutes, about 5 minutes to about 10 minutes, about 7 minutes to about 18 minutes, or about 7 minutes to about 12 minutes.
[0284] In some embodiments, following stripping of the electrode, the recovered electrode layer is immersed and agitated in the aqueous solvent for less than 20 minutes, less than 19 minutes, less than 18 minutes, less than 17 minutes, less than 16 minutes, less than 15 minutes, less than 14 minutes, less than 13 minutes, less than 12 minutes, less than 11 minutes, less than 10 minutes, less than 9 minutes, less than 8 minutes, less than 7 minutes, less than 6 minutes, less than 5 minutes, less than 4 minutes, or less than 3 minutes in forming the first suspension. In some embodiments, following electrode stripping, the recovered electrode layer is immersed and stirred in the aqueous solvent for greater than 0.25 minutes, greater than 0.5 minutes, greater than 0.75 minutes, greater than 1 minute, greater than 2 minutes, greater than 3 minutes, greater than 4 minutes, greater than 5 minutes, greater than 6 minutes, greater than 7 minutes, greater than 8 minutes, greater than 9 minutes, greater than 10 minutes, greater than 11 minutes, greater than 12 minutes, greater than 13 minutes, greater than 14 minutes, greater than 15 minutes, greater than 16 minutes, greater than 17 minutes, or greater than 18 minutes in forming the first suspension.
[0285] When the electrode layer includes a combination of a polymer binder and an electrode active material, a combination of a polymer binder and a metal-containing material, or a combination of a polymer binder, an electrode active material, and a metal-containing material, the electrode layer that has been broken down into small chucks (which may also be referred to as aggregates in the present invention) by stirring in an aqueous solvent may appear in the first suspension as a partially dissolved complex with a portion of the undissolved polymer binder within the clusters of the electrode active material or the metal-containing material. The basis for the portion of the undissolved polymer binder in the first suspension is believed to be due to the limited access of the polymer binder within the clusters of the electrode active material or the metal-containing material to the aqueous solvent, thus preventing the dissolution of the polymer binder.
[0286] The method of the present invention is particularly applicable to precipitating the polymer binder in the electrode layer produced by the aqueous slurry, which utilizes the polymer binder to adhere the active material particles and the conductive agent together with the current collector to form a continuous electrical conductive path. The polymer binder disclosed herein exhibits enhanced adhesive ability that strengthens the conductive network between the various components in the electrode layer, thus facilitating electron and ion transport to reduce the impedance between the current collector and the electrode material, and has sufficient elasticity to prevent the electrode from swelling due to volume expansion and contraction during charging and discharging.
[0287] The precipitation methods disclosed herein allow for the effective separation of the components of an electrode layer, such as the polymer binder and the electrode active material, by the simple use of a precipitating agent.
[0288] In some embodiments, the polymer binder comprises a copolymer comprising a structural unit derived from an acid group-containing monomer and a structural unit derived from a hydrophobic group-containing monomer. In some embodiments, the proportion of the structural unit derived from the acid group-containing monomer and the structural unit derived from the hydrophobic group-containing monomer present in the polymer binder is independently at least 15 mol % based on the total number of moles of monomer units in the copolymer in the polymer binder, which allows the polymer binder disclosed herein to exhibit excellent dispersibility and stability in water and improve the binding ability of the polymer binder.
[0289] In some embodiments, the battery electrode active material is a cathode active material, and the cathode active material is LiCoO2, LiNiO2, LiNi x Mn y O2, LiCo x Ni y O2, Li 1+z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al zwherein each x is independently 0.1 to 0.9; each y is independently 0 to 0.9; and each z is independently 0 to 0.4. In certain embodiments, each x in the above general formula is independently selected from 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, and 0.9; each y in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2 ,0.225,0.25,0.275,0.3,0.325,0.35,0.375,0.4,0.425,0.45,0.475,0.5,0.525,0.55,0.575,0.6,0.625,0.65,0.675,0.7,0.725,0.75,0.775,0.8,0.825, each z in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, and 0.4. In some embodiments, each x, y, and z in the above general formula is independently spaced apart by 0.01.
[0290] In certain embodiments, the cathode active material is LiCoO2, LiNiO2, LiNi x Mn y O2, Li 1+z Ni x Mn y Co 1-x-y O2(NMC), LiNi x Co y Al zO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, LiFeO2, LiFePO4, LiCo x Ni y each y is independently 0.2 to 0.4; and each z is independently 0 to 0.1. In other embodiments, the cathode active material is not LiCoO2, LiNiO2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, LiFeO2, or LiFePO4. In further embodiments, the cathode active material is not LiNi x Mn y O2, Li 1+z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z O2 or LiCo x Ni y where each x is independently from 0.1 to 0.9; each y is independently from 0 to 0.45; and each z is independently from 0 to 0.2. In certain embodiments, the cathode active material is Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2; -0.2≦x≦0.2, 0≦a<1, 0≦b<1, 0≦c<1, and a+b+c≦1. In some embodiments, the cathode active material has the general formula Li 1+x Ni a Mn b Co c Al (1-a-b-c)Having O2, where 0.33 ≦ a ≦ 0.92, 0.33 ≦ a ≦ 0.9, 0.33 ≦ a ≦ 0.8, 0.4 ≦ a ≦ 0.92, 0.4 ≦ a ≦ 0.9, 0.4 ≦ a ≦ 0.8, 0.5 ≦ a ≦ 0.92, 0.5 ≦ a ≦ 0.9, 0.5 ≦ a ≦ 0.8, 0.6 ≦ a ≦ 0.92 or 0.6 ≦ a ≦ 0.9; 0 ≦ b ≦ 0.5, 0 ≦ b ≦ 0.4, 0 ≦ b ≦ 0.3, 0 ≦ b ≦ 0.2, 0.1 ≦ b ≦ 0.5, 0.1 ≦ b ≦ 0.4, 0.1 ≦ b ≦ 0.3, 0.1 ≦ b ≦ 0.2, 0.2 ≦ b ≦ 0.5, 0.2 ≦ b ≦ 0.4, or 0.2 ≦ b ≦ 0.3; 0 ≦ c ≦ 0.5, 0 ≦ c ≦ 0.4, 0 ≦ c ≦ 0.3, 0.1 ≦ c ≦ 0.5, 0.1 ≦ c ≦ 0.4, 0.1 ≦ c ≦ 0.3, 0.1 ≦ c ≦ 0.2, 0.2 ≦ c ≦ 0.5, 0.2 ≦ c ≦ 0.4, or 0.2 ≦ c ≦ 0.3. In some embodiments, the cathode active material has the general formula LiMPO4, and M is selected from the group consisting of Fe, Co, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the cathode active material is selected from the group consisting of LiFePO4, LiCoPO4, LiNiPO4, LiMnPO4, LiMnFePO4, LiMn x Fe (1-x) PO4 and combinations thereof; 0 < x < 1. In some embodiments, the cathode active material is LiNi x Mn y O4; 0.1 ≦ x ≦ 0.9 and 0 ≦ y ≦ 2. In certain embodiments, the cathode active material is xLi2MnO3·(1 - x)LiMO2, where M is selected from the group consisting of Ni, Co, Mn, and combinations thereof; 0 < x < 1. In some embodiments, the cathode active material is Li3V2(PO4)3, LiVPO4F. In certain embodiments, the cathode active material has the general formula Li2MSiO4, and M is selected from the group consisting of Fe, Co, Mn, Ni, and combinations thereof.
[0291] In certain embodiments, the cathode active material is doped with a dopant selected from the group consisting of Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the dopant is not Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Mg, Zn, Ti, La, Ce, Ru, Si, or Ge. In certain embodiments, the dopant is not Al, Sn, or Zr.
[0292] In some embodiments, the cathode active material is LiNi 0.33 Mn 0.33 Co 0.33 O2(NMC333), LiNi 0.4 Mn 0.4 Co 0.2 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2(NMC532), LiNi 0.6 Mn 0.2 Co 0.2 O2(NMC622), LiNi 0.7 Mn 0.15 Co 0.15 O2, LiNi 0.7 Mn 0.1 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2(NMC811), LiNi 0.92 Mn 0.04 Co 0.04 O2, LiNi 0.8 Co 0.15 Al 0.05 O2(NCA), LiNiO2(LNO), and combinations thereof.
[0293] In other embodiments, the cathode active material is not LiCoO2, LiNiO2, LiMnO2, LiMn2O4, or Li2MnO3. 0.33 Mn 0.33 Co 0.33 O2, LiNi0.4 Mn 0.4 Co 0.2 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.7 Mn 0.15 Co 0.15 O2, LiNi 0.7 Mn 0.1 Co 0.2 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.92 Mn 0.04 Co 0.04 O2, or LiNi 0.8 Co 0.15 Al 0.05 Not O2.
[0294] In certain embodiments, the cathode active material comprises or is a core-shell composite material having a core and shell structure, the core and shell each independently comprising Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li2MnO3, LiCrO2, Li4Ti5O 12 , LiV2O5, LiTiS2, LiMoS2, LiCo a Ni b O2, LiMn a Ni band combinations thereof; where -0.2≦x≦0.2, 0≦a<1, 0≦b<1, 0≦c<1, and a+b+c≦1. In certain embodiments, each x in the above general formula is independently selected from -0.2, -0.175, -0.15, -0.125, -0.1, -0.075, -0.05, -0.025, 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, and 0.2; each a in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, 0.9, 0.925, 0.95 and 0.975; each b in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0. 175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, 0.9, 0.925, 0.95 and 0.975; each c in the above general formula is independently selected from 0, 0.025, 0.0 In some embodiments, each x, a, b, and c in the above formula is independently selected from the group consisting of 0.5, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, 0.9, 0.925, 0.95, and 0.975. In some embodiments, each x, a, b, and c in the above formula independently have an interval of 0.01.In other embodiments, the core and the shell each independently comprise two or more lithium transition metal oxides. In some embodiments, one of the core or the shell comprises only one lithium transition metal oxide, and the other comprises two or more lithium transition metal oxides. The lithium transition metal oxide or oxides in the core and the shell may be the same, or they may be different or partially different. In some embodiments, the two or more lithium transition metal oxides are uniformly distributed in the core. In certain embodiments, the two or more lithium transition metal oxides are not uniformly distributed in the core. In some embodiments, the cathode active material is not a core-shell composite.
[0295] In some embodiments, each of the lithium transition metal oxides in the core and shell is independently doped with a dopant selected from the group consisting of Co, Cr, V, Mo, Nb, Pd, F, Na, Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In certain embodiments, the core and shell each independently comprise two or more doped lithium transition metal oxides. In some embodiments, the two or more doped lithium transition metal oxides are uniformly distributed in the core and / or shell. In certain embodiments, the two or more doped lithium transition metal oxides are not uniformly distributed in the core and / or shell.
[0296] In some embodiments, the cathode active material comprises or is a core-shell composite material comprising a core comprising a lithium transition metal oxide and a shell comprising a transition metal oxide. In certain embodiments, the lithium transition metal oxide is Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2, LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li2MnO3, LiCrO2, Li4Ti5O 12 , LiV2O5, LiTiS2, LiMoS2, LiCoa Ni b O2、LiMn a Ni bO2, and combinations thereof; -0.2≦x≦0.2, 0≦a<1, 0≦b<1, 0≦c<1, and a+b+c≦1. In certain embodiments, x in the above general formula is independently selected from -0.2, -0.175, -0.15, -0.125, -0.1, -0.075, -0.05, -0.025, 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, and 0.2; each a in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0. each b in the above general formula is independently selected from 0, 0.025, 0.05, 0.075, 0.1, 0.125, 0.15, 0.165, 0.175, 0.185, 0.195, 0.205, 0.225, 0.235, 0.245, 0.250, 0.265, 0.275, 0.285, 0.295, 0.305, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, 0.9, 0.925, 0.95, and 0.975; 0.75, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, 0.9, 0.925, 0.95 and 0.975; each c in the above general formula is independently selected from 0, 0.025, 0.0 In some embodiments, each x, a, b, and c in the above formula is independently selected from the group consisting of 0.5, 0.075, 0.1, 0.125, 0.15, 0.175, 0.2, 0.225, 0.25, 0.275, 0.3, 0.325, 0.35, 0.375, 0.4, 0.425, 0.45, 0.475, 0.5, 0.525, 0.55, 0.575, 0.6, 0.625, 0.65, 0.675, 0.7, 0.725, 0.75, 0.775, 0.8, 0.825, 0.85, 0.875, 0.9, 0.925, 0.95, and 0.975. In some embodiments, each x, a, b, and c in the above formula independently have an interval of 0.01.In some embodiments, the transition metal oxide is selected from the group consisting of Fe2O3, MnO2, Al2O3, MgO, ZnO, TiO2, La2O3, CeO2, SnO2, ZrO2, RuO2, and combinations thereof. In certain embodiments, the shell comprises a lithium transition metal oxide and a transition metal oxide.
[0297] In some embodiments, the diameter of the core is about 1 μm to about 15 μm, about 3 μm to about 15 μm, about 3 μm to about 10 μm, about 5 μm to about 10 μm, about 5 μm to about 45 μm, about 5 μm to about 35 μm, about 5 μm to about 25 μm, about 10 μm to about 45 μm, about 10 μm to about 40 μm, or about 10 μm to about 35 μm, about 10 μm to about 25 μm, about 15 μm to about 45 μm, about 15 μm to about 30 μm, about 15 μm to about 25 μm, about 20 μm to about 35 μm, or about 20 μm to about 30 μm. In certain embodiments, the thickness of the shell is about 1 μm to about 45 μm, about 1 μm to about 35 μm, about 1 μm to about 25 μm, about 1 μm to about 15 μm, about 1 μm to about 10 μm, about 1 μm to about 5 μm, about 3 μm to about 15 μm, about 3 μm to about 10 μm, about 5 μm to about 10 μm, about 10 μm to about 35 μm, about 10 μm to about 20 μm, about 15 μm to about 30 μm, about 15 μm to about 25 μm, or about 20 μm to about 35 μm. In certain embodiments, the ratio of the diameter or thickness of the core and the shell is within the range of 15:85 to 85:15, 25:75 to 75:25, 30:70 to 70:30, or 40:60 to 60:40. In certain embodiments, the volume or weight ratio of the core and shell is 95:5, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, or 30:70.
[0298] In some embodiments, the electrode active material is an anode active material, and the anode active material is natural graphite particulate, synthetic graphite particulate, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particulate, SnO, SnO, Li4Ti5O 12 The fine particles are selected from the group consisting of fine particles, Si fine particles, Si-C composite fine particles, and combinations thereof.
[0299] In certain embodiments, the anode active material is doped with a metallic or non-metallic element. In some embodiments, the metallic element is selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, and combinations thereof. In some embodiments, the non-metallic element is B, Si, Ge, N, P, F, S, Cl, I, Se, and combinations thereof.
[0300] In some embodiments, the anode active material comprises or is a core-shell composite material having a core and shell structure, wherein the core and shell are each independently selected from natural graphite particulates, synthetic graphite particulates, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particulates, SnO, SnO, LiTiO 12 The particulate material is selected from the group consisting of fine particles, Si fine particles, Si-C composite fine particles, and combinations thereof.
[0301] In certain embodiments, the core-shell composite material comprises a core comprising a carbonaceous material and a shell coating the carbonaceous material core. In some embodiments, the carbonaceous material is selected from the group consisting of soft carbon, hard carbon, natural graphite particulate, synthetic graphite particulate, mesocarbon microbeads, kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fibers, and combinations thereof. In certain embodiments, the shell is selected from the group consisting of natural graphite particulate, synthetic graphite particulate, hard carbon, soft carbon, mesocarbon microbeads (MCMB), Sn particulate, SnO2, SnO, Li4Ti5O 12 The particulate material is selected from the group consisting of fine particles, Si fine particles, Si-C composite fine particles, and combinations thereof.
[0302] In certain embodiments, the anode active material is not doped with a metallic or non-metallic element, hi some embodiments, the anode active material is not doped with Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, B, Si, Ge, N, P, F, S, Cl, I, or Se.
[0303] In some embodiments, the metal-containing material is selected from the group consisting of ceramic, metal, misch metal, or combinations thereof.
[0304] In some embodiments, the ceramic is AlCeO3, LiAlO2, MgAl2O4, Ce 0.63 Tb 0.37 MgAl 11 O 19 , Sr 0.95 EU 0.02 Dy 0.03 Al2O4, Sr 3.84 EU 0.06 Dy 0.10 Al 14 O 25 , BaFe 12 O 19 , CuFe2O4, CuZnFe2O4, LiFeO2, NiZnFe4O4, SrFe 12 O 19 , YFeO 12 , LiNbO3, KNbO3, Zn(NbO3)2, Cu2Cr2O5, LiTaO3, NiCoO2, YBaCuO, BaZrO3, CaZrO3, PbZrO3, Li2ZrO3, Al2TiO5, Al2O3, BaTiO3, CaTiO3, FeTiO3, PbTiO3, Li2TiO3, Li4Ti5O 12 , SrTiO3, ZnTiO3, Al2CoO4, CoFe2O4, Fe2NiO4, ZnFe2O4, or combinations thereof.
[0305] In some embodiments, the metal is selected from the group consisting of aluminum, bismuth, chromium, cobalt, copper, gold, iron, lead, magnesium, manganese, mercury, nickel, silver, titanium, tin, zinc, boron, phosphorus, sulfur, scandium, cadmium, molybdenum, tungsten, arsenic, beryllium, silicon, vanadium, cerium, zirconium, antimony, or alloys thereof.
[0306] In some embodiments, the misch metal is selected from the group consisting of scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, lutetium, or alloys thereof.
[0307] In some embodiments, the electrode active material and the metal-containing material may be dissolved in the second suspension disclosed herein. When the first suspension includes a combination of a polymeric binder, an electrode active material, and an aqueous solvent, a combination of a polymeric binder, a metal-containing material, and an aqueous solvent, or a combination of a polymeric binder, an electrode active material, a metal-containing material, and an aqueous solvent, adding a precipitant to the first suspension to form the second suspension causes the polymeric binder to precipitate while the electrode active material and / or the metal-containing material begins to dissolve. Furthermore, as the electrode active material and / or the metal-containing material dissolves in the second suspension, any previously undissolved polymeric binder within the clusters of the electrode active material or the metal-containing material may become exposed and thus precipitate in the second suspension. This allows the polymeric binder to be separated from the remainder of the second suspension.
[0308] In some embodiments, the electrode layer may further include other additives to improve electrode properties. In some embodiments, the additives may include conductive agents, surfactants, dispersants, and flexibility enhancing additives. In some embodiments, the additives are not soluble in the aqueous solvent and / or the second suspension disclosed herein.
[0309] In some embodiments, the first suspension may further include a conductive agent, a surfactant, a dispersant, a flexibility enhancing additive, or a combination thereof.
[0310] In other embodiments, the electrode layer further comprises a conductive agent. In other embodiments, the first suspension further comprises a conductive agent. The conductive agent is for improving the electrical conductivity of the electrode. Any suitable material may act as the conductive agent. In some embodiments, the conductive agent is a carbonaceous material. Some non-limiting examples include carbon, carbon black, graphite, expanded graphite, graphene, graphene nanoplatelets, carbon fibers, carbon nanofibers, graphitized carbon flakes, carbon tubes, activated carbon, Super P®, 0-dimensional KS6, 1-dimensional vapor grown carbon fiber (VGCF), mesoporous carbon, and combinations thereof.
[0311] In some embodiments, the conductive agent is not dissolved in the aqueous solvent and / or the second suspension disclosed herein. If the first suspension includes a combination of a polymeric binder, an electrode active material, a conductive agent, and an aqueous solvent, or a combination of a polymeric binder, a metal-containing material, a conductive agent, and an aqueous solvent, or a combination of a polymeric binder, an electrode active material, a metal-containing material, a conductive agent, and an aqueous solvent, when a precipitating agent is added to the first suspension when forming the second suspension, the electrode active material and / or the metal-containing material begin to dissolve in the second suspension, the conductive agent remains solid, and the polymeric binder precipitates. This allows the polymeric binder and the conductive agent to be separated from the remainder of the second suspension, which includes the electrode active material and / or the metal-containing material. Thus, the dissolved electrode active material and the metal-containing material can be extracted from the second suspension and further reused in the subsequent battery manufacturing process.
[0312] In some embodiments, when a polymer, an electrode layer, and an aqueous solvent are involved in the system, the precipitating agent can be mixed with the aqueous solvent to form a first suspension. The electrode layer can then be added to the first suspension to form a second suspension. In other embodiments, when a polymer, an electrode layer, and an aqueous solvent are involved in the system, the electrode layer and the precipitating agent can be added directly to the aqueous solvent to form the first suspension.
[0313] The order of addition of the precipitant, electrode layer and aqueous solvent disclosed in the methods of the present invention has little effect on the variability of polymer recovery, i.e., regardless of the order of addition of the precipitant, electrode layer and aqueous solvent in the methods disclosed herein, it is still possible to effectively precipitate the polymer with a high polymer recovery rate of over 98%.
[0314] The polymer binder applied in the present invention exhibits extremely strong bonding strength. One method for evaluating the strength of adhesion of the polymer binder is by the adhesive strength between the polymer binder and the current collector. It is important for the polymer binder to have good adhesive strength to the current collector in the preparation of battery electrodes, because it promotes the bonding strength of the electrode layer to the current collector, prevents separation, and enhances the mechanical stability of the electrode. In some embodiments, the adhesive strength between the polymer binder and the current collector is from about 2 N / cm to about 6 N / cm, from about 2 N / cm to about 5.8 N / cm, from about 2 N / cm to about 5.6 N / cm, from about 2 N / cm to about 5.4 N / cm, from about 2 N / cm to about 5.2 N / cm, from about 2 N / cm to about 5 N / cm, from about 2 N / cm to about 4.8 N / cm, from about 2 N / cm to about 4.6 N / cm, from about 2 N / cm to about 4.4 N / cm, from about 2 N / cm to about 4.2 N / cm, from about 2 N / cm to about 4 N / cm, Approx. 2N / cm ~ Approx. 3.9N / cm, Approx. 2N / cm ~ Approx. 3.8N / cm, Approx. 2N / cm ~ Approx. 3.7N / cm, Approx. 2N / cm ~ Approx. 3.6N / cm, Approx. 2N / cm ~ Approx. 3.5N / cm, Approx. 2N / cm ~ Approx. 3.4N / cm, Approx. 2N / cm ~Approx. 3.3N / cm, approx. 2N / cm ~ approx. 3.2N / cm, approx. 2N / cm ~ approx. 3.1N / cm, approx. 2N / cm ~ approx. 3N / cm, approx. 2.1N / cm ~ approx. 6N / cm, approx. 2.2N / cm ~ approx. 6N / cm, approx. 2.3N / cm ~ approx. 6N / cm , about 2.4N / cm~about 6N / cm, about 2.5N / cm~about 6N / cm, about 2.6N / cm~about 6N / cm, about 2.7N / cm~about 6N / cm, about 2.8N / cm~about 6N / cm, about 2.9N / cm~about 6N / cm, about 3N / c m ~ about 6N / cm, about 3.1N / cm - about 6N / cm, about 3.2N / cm - about 6N / cm, about 3.3N / cm - about 6N / cm, about 3.4N / cm - about 6N / cm, about 3.5N / cm - about 6N / cm, about 3.6N / cm - about 6N / c m, about 3.7N / cm to about 6N / cm, about 3.8N / cm to about 6N / cm, about 3.9N / cm to about 6N / cm, about 4N / cm to about 6N / cm, about 2.5N / cm to about 5.5N / cm, about 2.5N / cm to about 5N / cm, about 2.5 N / cm to about 4.5 N / cm, about 2.5 N / cm to about 4 N / cm, about 2.5 N / cm to about 3.5 N / cm, about 3 N / cm to about 5 N / cm, about 2.2 N / cm to about 4.2 N / cm, or about 2.2 N / cm to about 5.2 N / cm.
[0315] In some embodiments, the adhesive strength between the polymer binder and the current collector is less than 6 N / cm, less than 5.8 N / cm, less than 5.6 N / cm, less than 5.4 N / cm, less than 5.2 N / cm, less than 5 N / cm, less than 4.8 N / cm, less than 4.6 N / cm, less than 4.4 N / cm, less than 4.2 N / cm, less than 4 N / cm, less than 3.9 N / cm, less than 3.8 N / cm, less than 3.7 N / cm, less than 3.6 N / cm, less than 3.5 N / cm, less than 3.4 N / cm, less than 3.3 N / cm, less than 3.2 N / cm, less than 3.1 N / cm, less than 3 N / cm, less than 2.9 N / cm, less than 2.8 N / cm, less than 2.7 N / cm, less than 2.6 N / cm, less than 2.5 N / cm, less than 2.4 N / cm, less than 2.3 N / cm, or less than 2.2 N / cm. In some embodiments, the adhesive strength between the polymer binder and the current collector is greater than 2 N / cm, greater than 2.1 N / cm, greater than 2.2 N / cm, greater than 2.3 N / cm, greater than 2.4 N / cm, greater than 2.5 N / cm, greater than 2.6 N / cm, greater than 2.7 N / cm, greater than 2.8 N / cm, greater than 2.9 N / cm, greater than 3 N / cm, greater than 3.1 N / cm, greater than 3.2 N / cm, greater than 3.3 N / cm. greater than 3.4N / cm, greater than 3.5N / cm, greater than 3.6N / cm, greater than 3.7N / cm, greater than 3.8N / cm, greater than 3.9N / cm, greater than 4N / cm, greater than 4.2N / cm, greater than 4.4N / cm, greater than 4.6N / cm, greater than 4.8N / cm, greater than 5N / cm, greater than 5.2N / cm, greater than 5.4N / cm, greater than 5.6N / cm or greater than 5.8N / cm.
[0316] In addition, the polymer binder applied in the present invention can develop strong adhesion of the electrode layer to the current collector in the electrode. It is important that the electrode layer has good peel strength from the current collector, since this greatly affects the mechanical stability of the electrode and the cyclability of the battery. Therefore, it is desirable for the electrode to have sufficient peel strength to withstand the rigors of battery manufacturing.
[0317] In some embodiments, the peel strength between the current collector and the electrode layer is about 1.0 N / cm to about 8.0 N / cm, about 1.0 N / cm to about 6.0 N / cm, about 1.0 N / cm to about 5.0 N / cm, about 1.0 N / cm to about 4.0 N / cm, about 1.0 N / cm to about 3.0 N / cm, about 1.0 N / cm to about 2.5 N / cm, about 1.0 N / cm to about 2.0 N / cm, about 1.2 N / cm to about 3.0 N / cm, about 1.2 N / cm to about 2.5 N / cm, about 1.2 N / cm to about 2.0 N / cm, about 1.5 N / cm to about 3.0 N / cm, about 1.5 N / cm to about 2.5 ... m to about 2.5 N / cm, about 1.5 N / cm to about 2.0 N / cm, about 1.8 N / cm to about 3.0 N / cm, about 1.8 N / cm to about 2.5 N / cm, about 2.0 N / cm to about 6.0 N / cm, about 2.0 N / cm to about 5.0 N / cm, about 2.0 N / cm to about 3.0 N / cm, about 2.0 N / cm to about 2.5 N / cm, about 2.2 N / cm to about 3.0 N / cm, about 2.5 N / cm to about 3.0 N / cm, about 3.0 N / cm to about 8.0 N / cm, about 3.0 N / cm to about 6.0 N / cm, or about 4.0 N / cm to about 6.0 N / cm.
[0318] In some embodiments, the peel strength between the current collector and the electrode layer is 1.0 N / cm or more, 1.2 N / cm or more, 1.5 N / cm or more, 2.0 N / cm or more, 2.2 N / cm or more, 2.5 N / cm or more, 3.0 N / cm or more, 3.5 N / cm or more, 4.5 N / cm or more, 5.0 N / cm or more, 5.5 N / cm or more, 6.0 N / cm or more, 6.5 N / cm or more, 7.0 N / cm or more, or 7.5 N / cm or more. In some embodiments, the peel strength between the current collector and the electrode layer is less than 8.0 N / cm, less than 7.5 N / cm, less than 7.0 N / cm, less than 6.5 N / cm, less than 6.0 N / cm, less than 5.5 N / cm, less than 5.0 N / cm, less than 4.5 N / cm, less than 4.0 N / cm, less than 3.5 N / cm, less than 3.0 N / cm, less than 2.8 N / cm, less than 2.5 N / cm, less than 2.2 N / cm, less than 2.0 N / cm, less than 1.8 N / cm, or less than 1.5 N / cm.
[0319] FIG. 10 is a flow chart of one embodiment showing the steps of a method 1000 for precipitating a polymeric binder as disclosed herein and subsequent further processing for extraction of the polymer. The remainder of the second suspension, including the aqueous solvent, dissolved precipitant, and dissolved electrode active material, may be subjected to additional separation and / or extraction processing to further extract the electrode active material and precipitant contained therein. In some embodiments, the recovered polymeric binder may be subjected to neutralization for further reuse in the subsequent battery manufacturing process. This allows the material to be repeatedly regenerated and reused, forming a closed loop recovery process, which can participate in a continuous loop configuration and help create a circular economy.
[0320] The present invention provides a simple method that can be used to precipitate polymer binders of different compositions. Since the separation of the polymer binder and other electrode layer components constitutes a key step in battery recycling, the method disclosed herein provides a technical solution in meeting the demands of battery recycling. The method of the present invention avoids both the complicated separation steps and the contamination of the polymer binder, allowing for excellent material recovery (i.e., high polymer recovery rate) and significantly reducing the time required to precipitate the polymer binder.
[0321] The following examples are presented to illustrate embodiments of the present invention, but are not intended to limit the present invention to the specific embodiments presented. All parts and percentages are by weight unless otherwise indicated. All numerical values are approximate. When numerical ranges are given, it should be understood that embodiments outside the stated ranges may still fall within the scope of the present invention. The specific details described in each example are not construed as necessary features of the present invention.
[0322] (example) The pH value of the second suspension was measured with an electrode-type pH meter (ION2700, Eutech Instruments).
[0323] Polymer recovery refers to the weight ratio of recovered polymer based on the initial weight of polymer present in the first suspension before the addition of the precipitant.
[0324] The adhesive strength of the dried polymer binder layer was measured with a tensile tester (DZ-106A, obtained from Dongguan Zonhow Test Equipment Co.Ltd., China). This test measures the average force in Newtons required to peel the polymer binder layer from the current collector at an angle of 180°. The average roughness depth (Rz) of the current collector is 2 μm. The current collector was coated with the polymer binder and allowed to dry, resulting in a polymer binder layer with a thickness of 10 μm to 12 μm. The coated current collector was then placed in a constant temperature environment of 25°C and humidity of 50 to 60% for 30 minutes. A piece of adhesive tape (3M; USA, model number 810) with a width of 18 mm and a length of 20 mm was affixed to the surface of the polymer binder layer. The polymer binder piece was clamped in the tester, the tape was folded back on itself at 180°, placed in the movable jaw, and pulled at room temperature at a peel rate of 300 mm per minute. The maximum peel strength was recorded as the adhesive strength. The measurement was repeated three times and the average value was calculated.
[0325] The peel strength of the dried electrode layer was measured with a tensile tester (DZ-106A, obtained from Dongguan Zonhow Test Equipment Co.Ltd., China). This test measures the average force in Newtons required to peel the electrode layer from the current collector at an angle of 180°. The current collector has an average roughness depth (Rz) of 2 μm. A strip of adhesive tape (3M; USA; model number 810) measuring 18 mm wide and 20 mm long was attached to the surface of the cathode electrode layer. The cathode strip was clamped in the tester, and the tape was folded back on itself at 180°, placed in the movable jaw, and pulled at a peel speed of 200 mm per minute at room temperature. The maximum peel force measured was taken as the peel strength. The measurement was repeated three times and the average value was calculated. (Example 1) Preparation of the first suspension A) Preparation of the polymer
[0326] 16 g of sodium hydroxide (NaOH) was added to a round bottom flask containing 380 g of distilled water. The combination of materials was stirred at 80 rpm for 30 minutes to obtain a first mixture.
[0327] 36.04 g of acrylic acid (AA) was added to the first mixture. The combination of materials was further stirred at 80 rpm for 30 minutes to obtain a second mixture.
[0328] 19.04 g of acrylamide (AM) was dissolved in 10 g of DI water to form an AM solution. Then, 29.04 g of the AM solution was added to the second mixture. The combination of materials was further heated to 55° C. and stirred at 80 rpm for 45 minutes to form a third mixture.
[0329] 12.92 g of acrylonitrile (AN) was added to the third mixture. The combination of materials was further stirred at 80 rpm for 10 minutes to obtain a fourth mixture.
[0330] Additionally, 0.015 g of a water-soluble free radical initiator (ammonium persulfate, APS; obtained from Aladdin Industries Corporation, China) was dissolved in 3 g of DI water, and 0.0075 g of a reducing agent (sodium bisulfite; obtained from Tianjin Damao Chemical Reagent Factory, China) was dissolved in 1.5 g of DI water. 3.015 g of the APS solution and 1.5075 g of the sodium bisulfite solution were added to the fourth mixture. The combination of materials was stirred at 200 rpm at 55° C. for 24 hours to obtain a fifth mixture.
[0331] After complete reaction, the temperature of the fifth mixture was lowered to 25°C. 3.72g NaOH was dissolved in 400g DI water. Then, 403.72g sodium hydroxide solution was added dropwise to the fifth mixture over 1 hour to adjust the pH to 7.31 to form a sixth mixture. The polymer was prepared by filtration using a 200μm nylon mesh. The solid content of the polymer was 9.00wt%. The adhesive strength between the polymer and the current collector was 3.27N / cm. The components of the polymer of Example 1 and their respective proportions are shown in Table 1 below. B) Formation of the First Suspension
[0332] 5.56 g of polymer was added to a round bottom flask containing 44.55 g of aqueous solvent (distilled water). The mixture was stirred at 80 rpm for 10 minutes to obtain 50.11 g of a first suspension. The solids content of the first suspension was 0.99 wt%. Polymer Recycling A) Preparation of precipitant
[0333] 98 g of sulfuric acid was dissolved in 1 L of distilled water to prepare a 1M aqueous sulfuric acid solution. B) Polymer precipitation
[0334] 1M sulfuric acid solution was added to the first suspension to form a second suspension with pH 4.24. This second suspension was stirred at 200 rpm for 10 minutes at 25° C. Then, the polymer was precipitated. After the precipitation of the polymer, the treated second suspension was removed through a filter paper to recover the precipitated polymer. The recovered polymer was dried in an oven at atmospheric pressure at 80° C. for 5 hours, resulting in a polymer recovery of 98.58%. The dried polymer could then be further reused. The polymer recovery and the pH of the second suspension were measured and are shown in Table 1 below. Preparation of the first suspension of Example 2
[0335] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 45.04 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.60 g of a first suspension. Recycling of polymers in Example 2
[0336] Recycling of the polymer was carried out as in Example 1, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 2.96. Preparation of the first suspension of Example 3
[0337] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.52 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.08 g of a first suspension. Example 3 Polymer Recycling
[0338] Recycling of the polymer was carried out in a similar manner to Example 1, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 2.07.
[0339] The polymer recycle of Example 3 was repeated by stirring the second suspension at 25° C. and 200 rpm for 60 and 120 minutes, respectively. The second suspension stirred for 60 minutes gave a polymer recovery of 99.42%, whereas the second suspension stirred for 120 minutes gave a polymer recovery of 99.43%. There is no indication that increasing the stirring time of the second suspension significantly increases the polymer recovery. Preparation of the first suspension of Example 4
[0340] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.68 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.24 g of a first suspension. Example 4 Polymer Recycling
[0341] Recycling of the polymer was carried out as in Example 1, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 1.01. Preparation of the first suspension of Example 5
[0342] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.53 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.09 g of a first suspension. Recycling of polymers in Example 5
[0343] Recycling of the polymer was carried out as in Example 1, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 2.05, and the second suspension was stirred at 200 rpm and 50° C. for 10 minutes. Preparation of the first suspension of Example 6
[0344] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.59 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.15 g of a first suspension. Recycling of polymers in Example 6
[0345] Recycling of the polymer was carried out as in Example 1, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 1.95, and the second suspension was stirred at 200 rpm and 90° C. for 10 minutes. Example 7 Preparation of the first suspension A) Preparation of the polymer
[0346] 5.13 g of lithium hydroxide was dissolved in 3.85 g of DI water. Then, 8.98 g of the lithium hydroxide solution was added to a 500 mL round bottom flask containing 289.17 g of distilled water. This combination of materials was stirred at 200 rpm for 30 minutes to obtain a first mixture.
[0347] Additionally, 31.54 g of AA was added to the first mixture. The combination of materials was further stirred at 200 rpm for 30 minutes to obtain a second mixture.
[0348] 13.52 g of AM was dissolved in 51.67 g of DI water. Then, 65.19 g of the AM solution was added to the second mixture. This combination of materials was further stirred at 200 rpm for 30 minutes to obtain a third mixture.
[0349] Then, 67.60 g of AN was added to the third mixture. The combination of materials was stirred at 200 rpm for 40 minutes to obtain a fourth mixture.
[0350] The fourth mixture was heated to 60° C. and stirred at 60 rpm for 45 minutes. 0.23 g of APS was dissolved in 82.68 g of DI water and 0.04 g of sodium bisulfite was dissolved in 17.22 g of DI water. 17.26 g of the sodium bisulfite solution was added to the fourth mixture and the combination of materials was stirred for 10 minutes. 82.91 g of the APS solution was added dropwise to the mixture over 3 hours to form the fifth mixture. The fifth mixture was further stirred at 200 rpm at 65° C. for 20 hours.
[0351] After the reaction was completed, the temperature of the fifth mixture was lowered to 40° C., 5.62 g of lithium hydroxide (dissolved in 116.64 g of DI water) was added to the fifth mixture, and the pH was adjusted to 7.44 to form a sixth mixture. The temperature of the sixth mixture was lowered to 30° C., and the polymer was prepared by filtration using a 200 μm nylon mesh. The solid content of the polymer was 14.93 wt %. The adhesive strength between the polymer and the current collector was 3.41 N / cm. The components of the polymer of Example 7 and their respective ratios are shown in Table 1 below. B) Formation of the First Suspension
[0352] 3.35 g of polymer was added to a round bottom flask containing 46.20 g of aqueous solvent (distilled water). The mixture was stirred at 80 rpm for 10 minutes to obtain 49.55 g of a first suspension. The solids content of the first suspension was 1.01 wt %. Polymer Recycling A) Preparation of precipitant
[0353] 98 g of sulfuric acid was dissolved in 1 L of distilled water to prepare a 1M aqueous sulfuric acid solution. B) Polymer precipitation
[0354] 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 3.99. This second suspension was stirred at 200 rpm for 10 minutes at 25° C. Then, the polymer was allowed to precipitate. After the precipitation of the polymer, the treated second suspension was removed through a filter paper to recover the precipitated polymer. The recovered polymer was dried in an oven at atmospheric pressure at 80° C. for 5 hours, resulting in a polymer recovery of 98.73%. The dried polymer could then be further reused. The polymer recovery and the pH of the second suspension were measured and are shown in Table 1 below. Preparation of the first suspension of Example 8
[0355] A first suspension was prepared as in Example 7, except that 46.10 g of 3.35 g of polymer was added to distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.45 g of a first suspension. Recycling of polymers in Example 8
[0356] Recycling of the polymer was carried out as in Example 7, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 3.00. Preparation of the first suspension of Example 9
[0357] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 47.07 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.42 g of a first suspension. Recycling of polymers in Example 9
[0358] Recycling of the polymer was carried out in a manner similar to that of Example 7, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 2.12. Preparation of the first suspension of Example 10
[0359] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.22 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.57 g of a first suspension. Example 10 Polymer Recycling
[0360] Recycling of the polymer was carried out as in Example 7, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 1.07. Preparation of the first suspension of Example 11
[0361] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.46 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.81 g of a first suspension. Recycling of polymers in Example 11
[0362] Recycling of the polymer was carried out in a manner similar to that of Example 7, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 1.13, and the second suspension was stirred at 200 rpm and 50° C. for 10 minutes. Preparation of the first suspension of Example 12
[0363] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.78 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.13 g of a first suspension. Recycling of polymers in Example 12
[0364] Recycling of the polymer was carried out in a manner similar to that of Example 7, except that 1 M aqueous sulfuric acid was added to the first suspension to form a second suspension with a pH of 1.15, and the second suspension was stirred at 200 rpm and 90° C. for 10 minutes. Preparation of the first suspension of Example 13
[0365] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.63 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.19 g of a first suspension. Recycling of polymers in Example 13
[0366] The polymer was recycled as in Example 1, except that in the preparation of the precipitant, 37 g of hydrochloric acid was dissolved in 1 L of distilled water to give a 1 M hydrochloric acid solution, and in the precipitation of the polymer, the 1 M hydrochloric acid solution was added to the first suspension to form a second suspension with a pH of 1.22. Preparation of the first suspension of Example 14
[0367] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.32 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.67 g of a first suspension. Recycling of polymers in Example 14
[0368] The polymer was recycled as in Example 7, except that in the preparation of the precipitant, 37 g of hydrochloric acid was dissolved in 1 L of distilled water to give a 1 M hydrochloric acid solution, and in the precipitation of the polymer, the 1 M hydrochloric acid solution was added to the first suspension to form a second suspension with a pH of 1.18. Preparation of the first suspension of Example 15
[0369] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.76 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.32 g of a first suspension. Recycling of polymers in Example 15
[0370] The polymer was recycled as in Example 1, except that in the preparation of the precipitant, 139 g of formic acid was dissolved in 1 L of distilled water to obtain a 3 M formic acid solution, and in the precipitation of the polymer, the 3 M formic acid solution was added to the first suspension to form a second suspension with a pH of 1.07. Preparation of the first suspension of Example 16
[0371] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.36 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.71 g of a first suspension. Recycling of polymers of Example 16
[0372] The polymer was recycled as in Example 7, except that in the preparation of the precipitant, 139 g of formic acid was dissolved in 1 L of distilled water to obtain a 3 M formic acid solution, and in the precipitation of the polymer, the 3 M formic acid solution was added to the first suspension to form a second suspension with a pH of 0.83. Preparation of the first suspension of Example 17
[0373] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.69 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.25 g of a first suspension. Recycling of polymers in Example 17
[0374] The polymer was recycled as in Example 1, except that in the preparation of the precipitant, 139 g of formic acid was dissolved in 1 L of distilled water to obtain a 3 M formic acid solution, and in the precipitation of the polymer, the 3 M formic acid solution was added to the first suspension to form a second suspension with a pH of 2.92. Preparation of the first suspension of Example 18
[0375] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.49 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.84 g of a first suspension. Recycling of polymers in Example 18
[0376] The polymer was recycled as in Example 7, except that in the preparation of the precipitant, 139 g of formic acid was dissolved in 1 L of distilled water to obtain a 3 M formic acid solution, and in the precipitation of the polymer, the 3 M formic acid solution was added to the first suspension to form a second suspension with a pH of 2.97. Preparation of the first suspension of Example 19
[0377] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.73 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.29 g of a first suspension. Recycling of polymers in Example 19
[0378] The polymer was recycled as in Example 1, except that in the preparation of the precipitant, 577 g of citric acid was dissolved in 1 L of distilled water to give a 3 M citric acid solution, and in the precipitation of the polymer, the 3 M citric acid solution was added to the first suspension to form a second suspension with a pH of 0.90. Preparation of the first suspension of Example 20
[0379] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.25 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.60 g of a first suspension. Recycling of polymers in Example 20
[0380] The polymer was recycled as in Example 7, except that in the preparation of the precipitant, 577 g of citric acid was dissolved in 1 L of distilled water to give a 3 M citric acid solution, and in the precipitation of the polymer, the 3 M citric acid solution was added to the first suspension to form a second suspension with a pH of 1.09. Preparation of the first suspension of Example 21
[0381] The first suspension was prepared in the same manner as in Example 1, except that in preparing the polymer, 36.04 g of AA was replaced with the same weight of 2-ethylacrylic acid in preparing the second mixture, and in forming the first suspension, 5.56 g of polymer was added to 44.58 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.14 g of the first suspension. Recycling of polymers in Example 21
[0382] The polymer was recycled as in Example 1, except that a 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.14. Preparation of the first suspension of Example 22
[0383] The first suspension was prepared in the same manner as in Example 1, except that in preparing the polymer, 36.04 g of AA was replaced with the same weight of crotonic acid in preparing the second mixture, and in forming the first suspension, 5.56 g of polymer was added to 44.67 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.23 g of the first suspension. Recycling of the polymer of Example 22
[0384] Recycling of the polymer was carried out as in Example 1, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.21. Preparation of the first suspension of Example 23
[0385] The first suspension was prepared in the same manner as in Example 7, except that in preparing the polymer, 31.54 g of AA was replaced with the same weight of 2-ethylacrylic acid in preparing the second mixture, and in forming the first suspension, 3.35 g of polymer was added to 46.48 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.83 g of the first suspension. Recycling of the polymer of Example 23
[0386] The polymer was recycled as in Example 7, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.04. Preparation of the first suspension of Example 24
[0387] The first suspension was prepared in the same manner as in Example 7, except that in preparing the polymer, 31.54 g of AA was replaced with the same weight of crotonic acid in preparing the second mixture, and in forming the first suspension, 3.35 g of polymer was added to 46.44 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.79 g of the first suspension. Recycling of polymers in Example 24
[0388] The polymer was recycled as in Example 7, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.17. Preparation of the first suspension of Comparative Example 1
[0389] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.63 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.19 g of a first suspension. Recycling of the polymer of Comparative Example 1
[0390] The polymer was recycled as in Example 1, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 5.93. Preparation of the first suspension of Comparative Example 2
[0391] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.56 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.12 g of a first suspension. Recycling of the polymer of Comparative Example 2
[0392] Recycling of the polymer was carried out as in Example 1, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 4.92. Preparation of the first suspension of Comparative Example 3
[0393] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.47 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.82 g of a first suspension. Recycling of the polymer of Comparative Example 3
[0394] The polymer was recycled as in Example 7, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 6.01. Preparation of the first suspension of Comparative Example 4
[0395] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.40 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.75 g of a first suspension. Recycling of the polymer of Comparative Example 4
[0396] The polymer was recycled as in Example 7, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 4.96. Preparation of the first suspension of Comparative Example 5
[0397] A first suspension was prepared as in Example 1, except that 5.56 g of polymer was added to 44.68 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.24 g of a first suspension. Recycling of the polymer of Comparative Example 5
[0398] The polymer was recycled as in Example 1, except that in the preparation of the precipitant, 139 g of formic acid was dissolved in 1 L of distilled water to obtain a 3 M formic acid solution, and in the precipitation of the polymer, the 3 M formic acid solution was added to the first suspension to form a second suspension with a pH of 3.46. Preparation of the first suspension of Comparative Example 6
[0399] A first suspension was prepared as in Example 7, except that 3.35 g of polymer was added to 46.53 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 49.88 g of a first suspension. Recycling of the polymer of Comparative Example 6
[0400] The polymer was recycled as in Example 7, except that in the preparation of the precipitant, 139 g of formic acid was dissolved in 1 L of distilled water to obtain a 3 M formic acid solution, and in the precipitation of the polymer, the 3 M formic acid solution was added to the first suspension to form a second suspension with a pH of 3.39. Preparation of the first suspension of Comparative Example 7
[0401] The first suspension was prepared in the same manner as in Example 1, except that in preparing the polymer, polyacrylic acid (PAA) was used as the polymer, and in forming the first suspension, 5.56 g of PAA was added to 44.97 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.53 g of the first suspension. The solids content of the first suspension was 1.00 wt%. Recycling of the polymer of Comparative Example 7
[0402] The polymer was recycled as in Example 1, except that a 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.24. Preparation of the first suspension of Comparative Example 8
[0403] The first suspensions were prepared in the same manner as in Example 1, except that in the preparation of the polymer, in the preparation of the second mixture, 61.20 g of AA was added, in the preparation of the third mixture, no AM was added, in the preparation of the fourth mixture, 6.80 g of AN was added, and in forming the first suspension, 5.56 g of polymer was added to 44.88 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.44 g of the first suspension. Recycling of the polymer of Comparative Example 8
[0404] Recycling of the polymer was carried out as in Example 1, except that 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.18. Preparation of the first suspension of Comparative Example 9
[0405] The first suspension was prepared in the same manner as in Example 1, except that in preparing the polymer, polyacrylamide (PAM) was used as the polymer, and in forming the first suspension, 5.56 g of PAM was added to 44.47 g of distilled water and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.03 g of the first suspension. The solid content of the first suspension was 1.00 wt%. Recycling of the polymer of Comparative Example 9
[0406] The polymer was recycled as in Example 1, except that a 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.15. Preparation of the first suspension of Comparative Example 10
[0407] The first suspension was prepared in the same manner as in Example 1, except that in the preparation of the polymer, carboxymethylcellulose (CMC; BSH-12, DKS Co. Ltd., Japan) was used as the polymer, and in the formation of the first suspension, 0.50 g of CMC was added to 49.50 g of distilled water, and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.00 g of the first suspension. The solid content of the first suspension was 1.00 wt%. Recycling of the polymer of Comparative Example 10
[0408] Recycling of the polymer was carried out as in Example 1, except that a 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.02. Preparation of the first suspension of Comparative Example 11
[0409] The first suspension was prepared in the same manner as in Example 1, except that in preparing the polymer, styrene butadiene rubber (SBR, 45 wt% in water; AL-2001, NIPPON A&L INC., Japan) was used as the polymer, and in forming the first suspension, 1.11 g of SBR was added to 48.89 g of distilled water, and the mixture was stirred at 80 rpm for 10 minutes to obtain 50.00 g of the first suspension. The solid content of the first suspension was 1.00 wt%. Recycling of the polymer of Comparative Example 11
[0410] Recycling of the polymer was carried out as in Example 1, except that a 1M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.06. Example 25 Preparation of the first suspension A) Preparation of the polymer binder
[0411] The polymer binder was prepared in a manner similar to that of Example 7. The components of the polymer binder of Example 25 and their respective proportions are shown in Table 2 below. B) Preparation of aggregates
[0412] A first blend was prepared by mixing 9.32 g of polymer binder (solid content 14.93 wt %) with 19.70 g of cathode active material (NMC532; obtained from Shandong Tianjiao New Energy Co., Ltd., China) under stirring with an overhead stirrer at 25° C. for about 15 minutes. The first blend was then dried in an electric oven at 70° C. to form an aggregate. The drying time was about 45 minutes. C) Formation of the first suspension
[0413] 5 g of the aggregate was added to a round bottom flask containing 60 g of aqueous solvent (distilled water). The mixture was stirred at 80 rpm for 10 minutes to obtain 65 g of a first suspension. Recycling of polymer binders A) Preparation of precipitant
[0414] 295 g of sulfuric acid was dissolved in 1 L of distilled water to form a 3M aqueous sulfuric acid solution. B) Precipitation of the polymer binder
[0415] A 3M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 0.89. This second suspension was stirred at 200 rpm at 90°C for 2 hours. The increased stirring time and temperature are intended to dissolve the NMC532 more efficiently. The polymer binder was then precipitated and NMC532 was dissolved in the second suspension. After the precipitation of the polymer binder and dissolution of NMC532, the treated second suspension was filtered through a filter paper to recover the precipitated polymer binder. The recovered polymer binder was dried in an oven at atmospheric pressure at 80°C for 5 hours, resulting in a polymer recovery of 99.10%. This dried polymer binder can be further reused. The polymer recovery and pH of the second suspension were measured and are shown in Table 2 below. Preparation of the first suspension of Example 26
[0416] The first suspension was prepared in the same manner as in Example 25, except that in the preparation of the aggregate, 9.24 g of the polymer binder (solid content 14.93 wt %) and 22.7 g of Al2O3 were mixed at 25° C. with stirring for about 15 minutes with an overhead stirrer to prepare the first admixture. Recycling of polymer binders in Example 26
[0417] Recycling of the polymeric binder was carried out as in Example 25, except that in the preparation of the precipitant, 110 g of hydrochloric acid was dissolved in 1 L of distilled water to form a 3M hydrochloric acid solution, and in the precipitation of the polymeric binder, the 3M hydrochloric acid solution was added to the first suspension to form a second suspension with a pH of 1.23. Preparation of the first suspension of Example 27
[0418] The first suspension was prepared in the same manner as in Example 25, except that in the preparation of the aggregate, 6.59 g of the polymer binder (solid content 14.93 wt %) and 17.99 g of Al were mixed at 25° C. with stirring for about 15 minutes with an overhead stirrer to prepare the first admixture. Recycling of polymer binders in Example 27
[0419] Recycling of the polymer binder was carried out as in Example 25, except that a 3M aqueous sulfuric acid solution was added to the first suspension to form a second suspension having a pH of 1.41. Preparation of the first suspension of Example 28
[0420] The first suspension was prepared in a manner similar to that of Example 25. Recycling of polymer binders in Example 28
[0421] Recycling of the polymeric binder was carried out in a manner similar to that of Example 25, except that in the preparation of the precipitant, 577 g of citric acid was dissolved in 1 L of distilled water to form a 3 M citric acid solution, and in the precipitation of the polymeric binder, the 3 M citric acid solution was added to the first suspension to form a second suspension with a pH of 1.58. Preparation of the first suspension of Example 29
[0422] The first suspension was prepared in the same manner as in Example 25, except that in the preparation of the aggregate, 9.32 g of the polymer binder (14.93 wt % solids) and 19.70 g of LCO were mixed with stirring at 25° C. with an overhead stirrer for about 15 minutes to prepare the first admixture. Recycling of polymer binders in Example 29
[0423] Recycling of the polymer binder was carried out in the same manner as in Example 25, except that a 3M aqueous sulfuric acid solution was added to the first suspension to form a second suspension having a pH of 1.10. Preparation of the first suspension of Example 30
[0424] The first suspension was prepared in the same manner as in Example 25, except that in the preparation of the aggregate, 9.32 g of the polymer binder (14.93 wt % solids) and 19.70 g of LFP were mixed with stirring at 25° C. with an overhead stirrer for about 15 minutes to prepare the first admixture. Recycling of polymer binders in Example 30
[0425] Recycling of the polymer binder was carried out as in Example 25, except that a 3M aqueous sulfuric acid solution was added to the first suspension to form a second suspension having a pH of 1.06. Example 31 Preparation of the first suspension A) Preparation of the polymer binder
[0426] The polymer binder was prepared in a manner similar to that of Example 1. The components of the polymer binder of Example 31 and their respective proportions are shown in Table 2 below. B) Preparation of aggregates
[0427] A first admixture was prepared by mixing 11.23 g of polymer binder (solid content 9.00 wt %) with 19.20 g of cathode active material (NMC532; obtained from Shandong Tianjiao New Energy Co., Ltd., China) under stirring with an overhead stirrer at 25° C. for about 15 minutes. The first admixture was then dried in an electric oven at 70° C. to form an aggregate. The drying time was about 45 minutes. C) Formation of the first suspension
[0428] 5 g of the aggregate was added to a round bottom flask containing 60 g of aqueous solvent (distilled water). The mixture was stirred at 80 rpm for 10 minutes to obtain 65 g of a first suspension. Recycling of polymer binders A) Preparation of precipitant
[0429] 295 g of sulfuric acid was dissolved in 1 L of distilled water to form a 3M aqueous sulfuric acid solution. B) Precipitation of the polymer binder
[0430] A 3M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.13. The second suspension was stirred at 200 rpm at 90° C. for 2 hours. The polymer binder was then precipitated and NMC532 was dissolved in the second suspension. After the precipitation of the polymer binder and dissolution of NMC532, the treated second suspension was filtered through a filter paper to recover the precipitated polymer binder. The recovered polymer binder was dried in an oven at atmospheric pressure at 80° C. for 5 hours, resulting in a polymer recovery of 99.21%. The dried polymer binder can be further reused. The polymer recovery and pH of the second suspension were measured and are shown in Table 2 below. Preparation of the first suspension of Example 32
[0431] The first suspension was prepared in the same manner as in Example 31, except that in the preparation of the aggregate, 11.23 g of the polymer binder (solid content 9.00 wt %) and 22.7 g of Al2O3 were mixed at 25° C. with stirring for about 15 minutes with an overhead stirrer to prepare the first admixture. Recycling of polymer binders in Example 32
[0432] Recycling of the polymeric binder was carried out as in Example 31, except that in the preparation of the precipitant, 110 g of hydrochloric acid was dissolved in 1 L of distilled water to form a 3M hydrochloric acid solution, and in the precipitation of the polymeric binder, the 3M hydrochloric acid solution was added to the first suspension to form a second suspension with a pH of 0.97. Preparation of the first suspension of Example 33
[0433] The first suspension was prepared in the same manner as in Example 31, except that in the preparation of the aggregate, 11.23 g of the polymer binder (solid content 9.00 wt %) and 17.99 g of Al were mixed at 25° C. with stirring for about 15 minutes using an overhead stirrer to prepare the first admixture. Recycling of polymer binders in Example 33
[0434] Recycling of the polymer binder was carried out as in Example 31, except that 3M aqueous sulfuric acid was added to the first suspension to form a second suspension having a pH of 1.24. Preparation of the first suspension of Example 34
[0435] The first suspension was prepared in a manner similar to that of Example 31. Recycling of polymer binders in Example 34
[0436] Recycling of the polymeric binder was carried out in a manner similar to that of Example 31, except that in the preparation of the precipitant, 577 g of citric acid was dissolved in 1 L of distilled water to form a 3 M citric acid solution, and in the precipitation of the polymeric binder, the 3 M citric acid solution was added to the first suspension to form a second suspension at pH 1.19. Preparation of the first suspension of Example 35
[0437] The first suspension was prepared in the same manner as in Example 31, except that in the preparation of the aggregate, 11.23 g of the polymer binder (solid content 9.00 wt %) and 19.20 g of LCO were mixed with stirring at 25° C. with an overhead stirrer for about 15 minutes to prepare the first admixture. Recycling of polymer binders in Example 35
[0438] Recycling of the polymer binder was carried out in the same manner as in Example 31, except that a 3M aqueous sulfuric acid solution was added to the first suspension to form a second suspension having a pH of 1.02. Preparation of the first suspension of Example 36
[0439] The first suspension was prepared in the same manner as in Example 31, except that in the preparation of the aggregate, 11.23 g of the polymer binder (solid content 9.00 wt %) and 19.20 g of the LFP were mixed with stirring at 25° C. with an overhead stirrer for about 15 minutes to prepare the first admixture. Recycling of polymer binders in Example 36
[0440] Recycling of the polymer binder was carried out in the same manner as in Example 31, except that a 3M aqueous sulfuric acid solution was added to the first suspension to form a second suspension having a pH of 0.99. Example 37 Preparation of the first suspension
[0441] A cathode layer was obtained from a used lithium ion battery. The polymer binder in the cathode layer was prepared in the same manner as in Example 25. 4.48 g of the ground cathode layer was added to a round bottom flask containing 60 g of aqueous solvent (distilled water). The mixture was stirred at 80 rpm for 10 minutes to obtain 64.48 g of a first suspension. Recycling of polymer binders A) Preparation of precipitant
[0442] 295 g of sulfuric acid was dissolved in 1 L of distilled water to form a 3M aqueous sulfuric acid solution. B) Precipitation of the polymer binder
[0443] A 3M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.22. The second suspension was stirred at 200 rpm at 90 °C for 2 hours. The increased stirring time and temperature were intended to dissolve the NMC532 more efficiently. The polymer binder was then precipitated and the NMC532 was dissolved in the second suspension. After the precipitation of the polymer binder and dissolution of the NMC532, the treated second suspension was passed through a filter paper to recover the conductive agent and the precipitated polymer binder. The remaining treated second suspension can be further extracted to further extract the electrode active material and the precipitant contained therein. The recovered polymer binder was dried in an oven at 80 °C for 5 hours under atmospheric pressure, resulting in a polymer recovery rate of 99.32%. Example 38 Preparation of the first suspension A) Preparation of the polymer binder
[0444] A cathode layer was obtained from a used lithium ion battery. The polymer binder in the cathode layer was prepared in the same manner as in Example 31. 4.38 g of the ground cathode layer was added to a round bottom flask containing 60 g of aqueous solvent (distilled water). The mixture was stirred at 80 rpm for 10 minutes to obtain 64.38 g of a first suspension. Recycling of polymer binders A) Preparation of precipitant
[0445] 295 g of sulfuric acid was dissolved in 1 L of distilled water to form a 3M aqueous sulfuric acid solution. B) Precipitation of the polymer binder
[0446] A 3M sulfuric acid solution was added to the first suspension to form a second suspension with a pH of 1.36. The second suspension was stirred at 200 rpm at 90 °C for 2 hours. The increased stirring time and temperature were intended to dissolve the NMC532 more efficiently. The polymer binder was then precipitated and the NMC532 was dissolved in the second suspension. After the precipitation of the polymer binder and dissolution of the NMC532, the treated second suspension was passed through a filter paper to recover the conductive agent and the precipitated polymer binder. The remaining treated second suspension can be further extracted to further extract the electrode active material and the precipitant contained therein. The recovered polymer binder was dried in an oven at 80 °C for 5 hours under atmospheric pressure, resulting in a polymer recovery rate of 99.01%.
[0447] [Table 1-1]
[0448] [Table 1-2]
[0449] [Table 2]
[0450] The present invention has been described with respect to a limited number of embodiments, and the specific features of one embodiment should not be attributed to other embodiments of the invention. The method of some embodiments may include numerous steps not mentioned herein. The method of other embodiments does not include, or is substantially free of, any steps not recited herein. Modifications and variations from the described embodiments exist. The appended claims are intended to include all such modifications and variations within the scope of the present invention. The invention as originally claimed in the present application is set forth below. [1] 1. A method for precipitating a polymer by adding a precipitating agent to a first suspension to form a second suspension, the first suspension comprising a polymer and an aqueous solvent, the polymer comprising a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer. [2] The method according to [1], wherein the copolymer further comprises a hydrophilic group-containing monomer selected from the group consisting of an amide group-containing monomer, a hydroxyl group-containing monomer, or a combination thereof, and the hydrophobic group-containing monomer is selected from the group consisting of a nitrile group-containing monomer, an ester group-containing monomer, an epoxy group-containing monomer, a fluorine group-containing monomer, or a combination thereof. [3] The method according to [1], wherein the molar ratio of the structural units derived from the acid group-containing monomer to the structural units derived from the hydrophobic group-containing monomer in the copolymer is from about 0.1 to about 3, and the proportion of the structural units derived from the hydrophobic group-containing monomer is from about 15 mol % to about 85 mol %, based on the total number of moles of monomer units of the copolymer in the polymer. [4] The acid group-containing monomer is selected from the group consisting of a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphonic acid group-containing monomer, or a combination thereof, and the pK a The method according to [1], wherein the R is about 2.5 to about 7. [5] The carboxylic acid group-containing monomer is selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid, 2-butylcrotonic acid, cinnamic acid, maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, tetraconic acid, 2-ethylacrylic acid, isocrotonic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentyl Acrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,The method according to [4], wherein the maleic anhydride is selected from the group consisting of 3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, bromomaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, difluoromaleic acid, nonyl hydrogen maleate, decyl hydrogen maleate, dodecyl hydrogen maleate, octadecyl hydrogen maleate, fluoroalkyl hydrogen maleate, maleic anhydride, methylmaleic anhydride, dimethylmaleic anhydride, acrylic anhydride, methacrylic anhydride, methacrolein, methacryloyl chloride, methacryloyl fluoride, methacryloyl bromide, and combinations thereof. [6] The method of [4], wherein the sulfonic acid group-containing monomer is selected from the group consisting of vinyl sulfonic acid, methyl vinyl sulfonic acid, allyl vinyl sulfonic acid, allyl sulfonic acid, methallyl sulfonic acid, styrene sulfonic acid, 2-sulfoethyl methacrylic acid, 2-methylprop-2-ene-1-sulfonic acid, 2-acrylamido-2-methyl-1-propanesulfonic acid, 3-allyloxy-2-hydroxy-1-propanesulfonic acid, and combinations thereof. [7] The method of [4], wherein the phosphonic acid group-containing monomer is selected from the group consisting of vinyl phosphonic acid, allyl phosphonic acid, vinylbenzyl phosphonic acid, acrylamido alkyl phosphonic acid, methacrylamido alkyl phosphonic acid, acrylamido alkyl diphosphonic acid, acryloyl phosphonic acid, 2-methacryloyloxyethyl phosphonic acid, bis(2-methacryloyloxyethyl)phosphonic acid, ethylene 2-methacryloyloxyethyl phosphonic acid, ethyl-methacryloyloxyethyl phosphonic acid, and combinations thereof. [8] The method according to [1], wherein the proportion of structural units derived from an acid group-containing monomer in the polymer is from about 15 mol % to about 85 mol %, based on the total number of moles of monomer units in the copolymer. [9] The method according to [2], wherein the nitrile group-containing monomer is selected from the group consisting of acrylonitrile, α-halogenoacrylonitrile, α-alkylacrylonitrile, α-chloroacrylonitrile, α-bromoacrylonitrile, α-fluoroacrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-n-hexylacrylonitrile, α-methoxyacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile, α-acetoxyacrylonitrile, α-phenylacrylonitrile, α-tolylacrylonitrile, α-(methoxyphenyl)acrylonitrile, α-(chlorophenyl)acrylonitrile, α-(cyanophenyl)acrylonitrile, vinylidene cyanide, and combinations thereof; and the proportion of structural units derived from the nitrile group-containing monomer is about 15 mol % to about 85 mol %, based on the total number of moles of monomer units in the copolymer in the polymer.
[10] The amide group-containing monomer is selected from the group consisting of acrylamide, methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, Nn-propylmethacrylamide, N-isopropylmethacrylamide, isopropylacrylamide, Nn-butylmethacrylamide, N-isobutylmethacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N-methylolmethacrylamide, N-(methoxymethyl)methacrylamide, N-(ethoxymethyl)methacrylamide, N-(propoxymethyl)methacrylamide, N-(butoxymethyl)methacrylamide, and N,N-dimethylmethacrylamide. amide group-containing monomers selected from the group consisting of N,N-dimethylaminopropyl methacrylamide, N,N-dimethylaminoethyl methacrylamide, N,N-dimethylol methacrylamide, diacetone methacrylamide, diacetone acrylamide, methacryloylmorpholine, N-hydroxyl methacrylamide, N-methoxymethyl acrylamide, N-methoxymethyl methacrylamide, N,N'-methylene-bis-acrylamide (MBA), N-hydroxymethyl acrylamide, and combinations thereof; and the proportion of structural units derived from said amide group-containing monomers is from about 0 mol % to about 35 mol %, based on the total number of moles of monomer units in the copolymer in the polymer.
[11] The method according to [1], wherein the aqueous solvent is water or a solution containing water as a main component and trace components.
[12] The method according to
[11] , wherein the proportion of water in the aqueous solvent is about 51% by weight to about 100% by weight, and the trace components are selected from the group consisting of methanol, ethanol, isopropanol, n-propanol, tert-butanol, n-butanol, acetone, dimethyl ketone, methyl ethyl ketone, ethyl acetate, isopropyl acetate, propyl acetate, butyl acetate, and combinations thereof.
[13] The method according to [1], wherein the precipitating agent is a strong acid, a weak acid, or a combination thereof.
[14] The st...
Claims
1. 1. A method for precipitating a polymer by adding a precipitating agent into a first suspension to form a second suspension, wherein after addition of the precipitating agent to the first suspension in forming the second suspension, the polymer is precipitated; the first suspension comprises a polymer and an aqueous solvent; the polymer comprises a copolymer comprising structural units derived from an acid group-containing monomer and structural units derived from a hydrophobic group-containing monomer; a proportion of the structural units derived from the acid group-containing monomer is 15 mol % to 85 mol % based on the total number of moles of monomer units of the copolymer in the polymer; the hydrophobic group-containing monomer comprises a nitrile group-containing monomer; and a proportion of the structural units derived from the hydrophobic group-containing monomer is 15 mol % to 85 mol % based on the total number of moles of monomer units of the copolymer in the polymer; the precipitating agent is a strong acid, a weak acid, or a combination thereof; the pH of the second suspension is 0.2 to 4.5, and when the precipitating agent is a weak acid, the pH of the second suspension is further 0.5 to 3.
2. The method of claim 1 , wherein the copolymer further comprises a hydrophilic group-containing monomer selected from the group consisting of an amide group-containing monomer, a hydroxyl group-containing monomer, or a combination thereof.
3. 2. The method of claim 1, wherein the molar ratio of structural units derived from said acid group-containing monomer to structural units derived from said hydrophobic group-containing monomer in said copolymer is from 0.1 to 3.
4. The acid group-containing monomer is selected from the group consisting of a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphonic acid group-containing monomer, or a combination thereof; and the pK a The method according to claim 1, wherein the β-
5. The carboxylic acid group-containing monomer is selected from the group consisting of acrylic acid, methacrylic acid, crotonic acid, 2-butylcrotonic acid, cinnamic acid, maleic acid, fumaric acid, itaconic acid, tetraconic acid, 2-ethylacrylic acid, isocrotonic acid, cis-2-pentenoic acid, trans-2-pentenoic acid, angelic acid, tiglic acid, 3,3-dimethylacrylic acid, 3-propylacrylic acid, trans-2-methyl-3-ethylacrylic acid, cis-2-methyl-3-ethylacrylic acid, 3-isopropylacrylic acid, trans-3-methyl-3-ethylacrylic acid, cis-3-methyl-3-ethylacrylic acid, 2-isopropylacrylic acid, Pyracrylic acid, trimethylacrylic acid, 2-methyl-3,3-diethylacrylic acid, 3-butylacrylic acid, 2-butylacrylic acid, 2-pentylacrylic acid, 2-methyl-2-hexenoic acid, trans-3-methyl-2-hexenoic acid, 3-methyl-3-propylacrylic acid, 2-ethyl-3-propylacrylic acid, 2,3-diethylacrylic acid, 3,3-diethylacrylic acid, 3-methyl-3-hexylacrylic acid, 3-methyl-3-t 5. The method of claim 4, wherein the maleic acid is selected from the group consisting of tert-butylacrylic acid, 2-methyl-3-pentylacrylic acid, 3-methyl-3-pentylacrylic acid, 4-methyl-2-hexenoic acid, 4-ethyl-2-hexenoic acid, 3-methyl-2-ethyl-2-hexenoic acid, 3-tert-butylacrylic acid, 2,3-dimethyl-3-ethylacrylic acid, 3,3-dimethyl-2-ethylacrylic acid, 3-methyl-3-isopropylacrylic acid, 2-methyl-3-isopropylacrylic acid, trans-2-octenoic acid, cis-2-octenoic acid, trans-2-decenoic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, α-chloro-β-E-methoxyacrylic acid, methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, bromomaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, difluoromaleic acid, and combinations thereof.
6. 5. The method of claim 4, wherein the sulfonic acid group-containing monomer is selected from the group consisting of vinyl sulfonic acid, methyl vinyl sulfonic acid, allyl vinyl sulfonic acid, allyl sulfonic acid, methallyl sulfonic acid, styrene sulfonic acid, 2-sulfoethyl methacrylic acid, 2-methylprop-2-ene-1-sulfonic acid, 2-acrylamido-2-methyl-1-propanesulfonic acid, 3-allyloxy-2-hydroxy-1-propanesulfonic acid, and combinations thereof.
7. 5. The method of claim 4, wherein the phosphonic acid group-containing monomer is selected from the group consisting of vinyl phosphonic acid, allyl phosphonic acid, vinylbenzyl phosphonic acid, acrylamido alkyl phosphonic acid, methacrylamido alkyl phosphonic acid, acrylamido alkyl diphosphonic acid, acryloyl phosphonic acid, 2-methacryloyloxyethyl phosphonic acid, bis(2-methacryloyloxyethyl)phosphonic acid, ethylene 2-methacryloyloxyethyl phosphonic acid, ethyl-methacryloyloxyethyl phosphonic acid, and combinations thereof.
8. 3. The method of claim 2, wherein the proportion of structural units derived from amide group-containing monomers in the polymer is from 9 mol % to 35 mol %, based on the total number of moles of monomer units in the copolymer.
9. 2. The method of claim 1, wherein the nitrile group-containing monomer is selected from the group consisting of acrylonitrile, α-chloroacrylonitrile, α-bromoacrylonitrile, α-fluoroacrylonitrile, methacrylonitrile, α-ethylacrylonitrile, α-isopropylacrylonitrile, α-n-hexylacrylonitrile, α-methoxyacrylonitrile, 3-methoxyacrylonitrile, 3-ethoxyacrylonitrile, α-acetoxyacrylonitrile, α-phenylacrylonitrile, α-tolylacrylonitrile, α-(methoxyphenyl)acrylonitrile, α-(chlorophenyl)acrylonitrile, α-(cyanophenyl)acrylonitrile, vinylidene cyanide, and combinations thereof; and the percentage of structural units derived from the nitrile group-containing monomer is from 15 mol % to 85 mol %, based on the total number of moles of monomer units in the copolymer in the polymer.
10. The amide group-containing monomer is, for example, acrylamide, methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, N-n-propylmethacrylamide, N-isopropylmethacrylamide, isopropylacrylamide, N-n-butylmethacrylamide, N-isobutylmethacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N-methylolmethacrylamide, N-(methoxymethyl)methacrylamide, N-(ethoxymethyl)methacrylamide, N-(propoxymethyl)methacrylamide, N-(butoxymethyl)methacrylamide, N, 3. The method of claim 2, wherein the percentage of structural units derived from said amide group-containing monomers is selected from the group consisting of N-dimethylaminopropyl methacrylamide, N,N-dimethylaminoethyl methacrylamide, N,N-dimethylol methacrylamide, diacetone methacrylamide, diacetone acrylamide, methacryloylmorpholine, N-hydroxyl methacrylamide, N-methoxymethyl acrylamide, N-methoxymethyl methacrylamide, N,N'-methylene-bis-acrylamide, N-hydroxymethyl acrylamide and combinations thereof; said polymer having a molecular weight of from 0 to 35 mole % based on the total number of moles of monomer units in said copolymer.
11. The method of claim 1 , wherein the aqueous solvent is water or a solution containing water as a major component and trace components.
12. 12. The method of claim 11, wherein the percentage of water in the aqueous solvent is 51% to 100% by weight, and the minor components are selected from the group consisting of methanol, ethanol, isopropanol, n-propanol, tert-butanol, n-butanol, acetone, dimethyl ketone, methyl ethyl ketone, ethyl acetate, isopropyl acetate, propyl acetate, butyl acetate, and combinations thereof.
13. The strong acid is selected from the group consisting of nitric acid, sulfuric acid, hydrochloric acid, perchloric acid, hydrobromic acid, hydroiodic acid, chloric acid, bromic acid, iodic acid, dithioic acid, sulfamic acid, trithioic acid, tetrathioic acid, methanesulfonic acid, p-toluenesulfonic acid, benzenesulfonic acid, trichloroacetic acid, trifluoroacetic acid, oxalic acid, mesoxalic acid, mellitic acid, or a combination thereof; and the pK a The method of claim 1, wherein is −10 to 2.
14. The weak acids include formic acid, acetic acid, glycolic acid, glyoxylic acid, propionic acid, acrylic acid, propiolic acid, lactic acid, 3-hydroxypropionic acid, glyceric acid, pyruvic acid, 3-oxopropionic acid, 2,3-dioxopropionic acid, malonic acid, tartronic acid, dihydroxymalonic acid, mesoxalic acid, glycidic acid, butyric acid, isobutyric acid, crotonic acid, isocrotonic acid, methacrylic acid, vinylacetic acid, tetrolic acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-oxobutanoic acid, acetoacetic acid, 4-oxobutanoic acid, butanedioic acid, methylmalonic acid, fumaric acid, maleic acid, 2-hydroxybutyric acid, 4-hydroxybutyric acid, 2-oxobutanoic acid, acetoacetic acid, 4-oxobutanoic acid, butanedioic acid, methylmalonic acid, fumaric acid, maleic acid, 2-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxybutanoic acid, 4-hydroxybutyric acid, 2-hydroxybutanoic acid, 4-hydroxybutanoic ... and wherein the pK value of said weak acid is selected from the group consisting of sibtanedioic acid, tartaric acid, oxaloacetic acid, dioxosuccinic acid, valeric acid, isovaleric acid, 2-methylbutyric acid, pivalic acid, 3-hydroxyvaleric acid, 4-hydroxypentanoic acid, 3-hydroxyisovaleric acid, glutaric acid, 2-oxoglutaric acid, 3-oxoglutaric acid, 2-furoic acid, tetrahydrofuroic acid, hexanoic acid, hexanedioic acid, citric acid, aconitic acid, isocitric acid, sorbic acid, pimelic acid, benzoic acid, salicylic acid, 4-carboxybenzoic acid, trimesic acid, mellitic acid, malic acid, dithionous acid, phosphoric acid, nitrous acid, orthosilicic acid, or a combination thereof; a The method of claim 1, wherein is 2 to 7.
15. The pH of the second suspension is equal to or greater than the pK a 2. The method of claim 1 , wherein the pH is at least 0.2 pH units lower than the pH of the control.
16. The pH of the second suspension is equal to or greater than the pK a The method of claim 1 , wherein the pH is at least 1 pH unit lower than the pH of the aqueous solution.
17. 2. The method of claim 1, wherein the second suspension is stirred for a time period between 1 minute and 180 minutes, and the precipitating agent is added into the first suspension at a temperature between 20°C and 95°C.
18. 2. The method of claim 1, wherein the nitrile group-containing monomer is selected from the group consisting of α-halogenoacrylonitrile, α-alkylacrylonitrile, and combinations thereof; and the proportion of structural units derived from the nitrile group-containing monomer in the polymer is from 15 mol % to 85 mol %, based on the total number of moles of monomer units in the copolymer.
Citation Information
Patent Citations
JP1971014907Y1
Method for obtaining colloidal particle aggregate
JP1987007429A
Organic sludge dewatering agent
JP1991213200A
Medical image display apparatus and medical image diagnostic apparatus
JP2013009956A
Binder aqueous solution for lithium ion battery, slurry for lithium ion battery electrode and manufacturing method therefor, lithium ion battery electrode, and lithium ion battery
JP2020043064A